Integrating multi-omics reveals the protective effects of Lycium ruthenicum anthocyanins against radiation pneumonitis through gut-lung axis modulation - Kai Deng; Gaoyuan Zhang; Qiang Yan; Shuwen Han; Yunyao Wei; Ying Mei (Tissue and Cell, 2027)

The promotion of oxygen vacancy on Al2O3 gel catalyst for carbonyl sulfide hydrolysis: Anchoring adsorption and regulation of hydroxyl activity - Junge Yun; Cheng Zhao; Han Zheng; Xin Feng; Yanhong Zhao; Ninghan Wei; Zimo Chen; Chuanqi Lu; Shan Nie; Zhiyi Deng; Zhihang Chen (Fuel, 2027)

Propolis extract microcapsules maintain peach fruit quality during ambient storage by modulating oxidative homeostasis - Lizhi Deng; Yingying Yang; Ranran Xu; Jiahua Zhou; Han Wang; Jingxuan Lu; Lingling Liu; Weibo Jiang; Baogang Wang (Journal of Stored Products Research, 2027)

Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Carboxymethyl chitosan enhances the biocontrol efficacy of Papiliotrema laurentii against Penicillium digitatum by regulating energy metabolism - Chao Liu; Liangjun Xiao; Xianyu Liu; Siqi Xia; Le Yang; Rongyu Du; Han Ye; Xiahong He; Fang Wang; Jia Deng (Postharvest Biology and Technology, 2026)

Heavy metals in different coastal ecosystems of Zhanjiang, China: Pollution assessment and source identification - Yawen Wei; Zhentong Yao; Qian Liu; Qi Huang; Tianqin Yin; Xue Deng; Xuemei Xu; Hong Chen; Jianbo Han (Journal of Geochemical Exploration, 2026)

Drought legacy effects on soil carbon and microbial responses to rewetting across sampling campaigns and soil depths in a subtropical forest - Jiangtao Zeng; Zheng Peng; Yu He; Shihui Han; Lei Liu; Xianzheng Zeng; Jiangbin Xu; Zhiyi Cao; Qi Deng; Guoyi Zhou (CATENA, 2026)

Knockout of kdm4aa inhibits early embryonic development in zebrafish via downregulating cyp26a1 - Rui Deng; Xinqing Cai; Hui Jiang; Yuting Luo; Weiran Chai; Bingshe Han; Junfang Zhang (Molecular Genetics and Genomics, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Molecular mechanism of medium environment-mediated flaxseed oil body interface reconstruction driving β-carotene encapsulation - Shan Zhang; Jie Shi; Bingyu Han; Peng Chen; Yashu Chen; Qianchun Deng (Food Hydrocolloids, 2026)

A novel fully coupled thermal-hydraulic-mechanical-chemical model for hot dry rock reservoirs based on the non-conforming grid - Kaituo Jiao; Dongxu Han; Daobing Wang; Jingfa Li; Yujie Chen; Yajun Deng; Bofeng Bai; Bo Yu (Computers and Geotechnics, 2026)

Soybean residue incorporation enhances soil CO₂ emissions by increasing nutrient availability and alleviating microbial phosphorus limitation - Xiongde Dong; Yutong Xiao; Mai-He Li; Shijie Han; Yating Deng; Yanyan Yu; Feirong Ren; Junqiang Zheng (Applied Soil Ecology, 2026)

A conditional generative diffusion model enables joint retrieval of rice LAI and LCC - Heguang Sun; Huanming Mai; Bo Han; Yi Zhang; Zhongyu Jin; Changsheng Li; Wenqian Tang; Zifan Shen; Ziheng Feng; Xiaoyu Song; Yubin Lan; Wen Du; et al. (Computers and Electronics in Agriculture, 2026)

Modal analysis of propeller wake destabilization and energy transport via Tomo-PIV - Chun-yu Guo; Ming-chen Gao; Yang Han; Yi-jie Sun; Wen-xuan Huang; Deng-wei Du (Ocean Engineering, 2026)

Anisotropy of magnetic susceptibility in the Late Cretaceous Shanyang Basin, Central China: Implications for hydrological variability and dinosaur habitat stability - Yuqi Han; Fei Han; Chen Wen; Huafeng Qin; Huapei Wang; Qiang Wang; Xinying Zhou; Chenglong Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Optimizing sediment microbial fuel cells to enhance reductive removal and mitigate desorption of copper(II) on cathode - Yaqing Xu; Fengquan Li; Chenlu Li; Wenhui Zhong; Cheng Han; Yunbin Jiang; Ying Li; Huan Deng (Journal of Water Process Engineering, 2026)

Solar evaporator innovation with more precise control of structural and constituent characteristics through three-dimensional printing: A critical review - Ying Chen; Shihai Deng; Shuai Peng; Na You; Chaoqi Wang; Pengkang Jin; Jie Han (Journal of Environmental Chemical Engineering, 2026)

Recent advancements in photocatalysts for water purification - Yi Zhao; Junxiang Yang; Gang Xu; Shidong Zhang; Deng Long; Xinglin Yu; Jianglong Kong; Zheng Han; Wentao Li; Sihan Ma (Journal of Environmental Chemical Engineering, 2026)

Straw return enhances soil multifunctionality and maize yield through shifts in bacterial community structure - Shijie Deng; Yang Yu; Yubo Hao; Yubo Jiang; Guoyi Lv; Yiteng Zhang; Linjing Han; Meng Cheng; Shuo Zhang; Chunrong Qian (Field Crops Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Rosa roxburghii-derived Mg-doped carbon dots as bioactive nanoregulators in hydrogel scaffolds: orchestrating Nrf2/NF-κB signaling for enhanced periodontal repair in diabetes - Xuedong Deng; Lingxiang Sun; Xi Chen; Zheng Wang; Yilin Ping; Wen Ze Han; Lu Wang; Tingting Wu; Yifan Zhao; Bing Li; Xiuping Wu (Chemical Engineering Journal, 2026)

Reactivity-dependent and buffer-mediated gelation of biofluid-triggerable hydrogels applied in tissue sealing and repair - Guotai Li; Xiaoting Peng; Fangze Guo; Chunli Ma; Xuyang Deng; Danyang Wang; Yanjing Ji; Tongfeng Han; Min He; Dongjie Zhang; Qihui Zhou (Chemical Engineering Journal, 2026)

Hydrogel-mediated antimicrobial and immunomodulatory therapy for promoting scar-free healing of deep burns - Kangran Han; Haixia Yang; Daidi Fan; Jianjun Deng (Chemical Engineering Journal, 2026)

A Study on the Effects of Modified Coal Gangue Ceramsite on Soil Water Retention and Maize Growth under Drought Stress Based on Pot Experiment - Kun Zhang; Xin Yan; Jiazhang Han; Yubin Li; Hui Deng (Water, Air, & Soil Pollution, 2026)

Estimating heavy metal content in agricultural soils using soil physicochemical properties and UAV-based hyperspectral imagery - Hongxu Guo; Yihan Qiu; Kai Yang; Fan Wu; Dongbin Chen; Yirong Deng; Cunliang Han; Jun Wang; Zaoquan Huang (Precision Agriculture, 2026)

Metagenomic profiling of resistome and mobilome dynamics in diverse freshwater aquaculture modes - Xiaoxi Deng; Yu Wang; Huifen Zhu; Yongyong Guo; Qidong Wang; Jian Han; Ke Yu; Bingsheng Zhou (Water Research, 2026)

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

Assessing multidimensional changes in human settlements across urban regeneration paradigms: A case study of Wuhan, China - Meng-Tian Han; Qian Cao; Hai-Yun Xu; Xiang-Wen Deng; Lun-Che Wang; Jun Wan (Sustainable Cities and Society, 2026)

Enhanced formation of copper ferrocyanide on amidoxime-modified polyacrylonitrile for highly efficient recovery of Rb+ and Cs+ - Nannan Zhang; Xuhui Ma; Lijun Meng; Senjian Han; Lina Xu; Xunliang Wang; Shiqiang Wang; Tianlong Deng; Zhenyu Liao (Journal of Water Process Engineering, 2026)

Identification of potential markers for detecting milk adulteration in two donkey breeds with cow milk using a proteomics approach - Wei Si; Chunxia Deng; Binghao Fan; Rongbo Fan; Rongwei Han; Qijing Du; Hongning Jiang; Yongxin Yang (International Dairy Journal, 2026)

The effect of harvest time across different climatic regions on the accumulation of phenolic compounds in Marselan grapes and wines - Wangze Li; Hefang Li; Qingxiao Han; Yu Deng; Jiahao Zhang; Yulin Fang; Keqin Chen; Kekun Zhang (Food Chemistry, 2026)

Selective partitioning of plant proteins during emulsification impairs foam stability: conformational changes of aqueous-phase residues relative to animal proteins - Yiqiu Deng; Wanjun Han; Yiting Lin; Xiuhang Chai; Fengxiang Chen; Yuanfa Liu (Food Hydrocolloids, 2026)

Molecular characterization and expression analysis of three complement genes: C4B, C6 and C7 in Mastacembelus armatus under Aeromonas veronii infection - Kaifeng Wang; Ziyan Deng; Shengyue Lin; Min Zhang; Guojun Cai; Zihang Xie; Chong Han; Qiang Li (Fish & Shellfish Immunology, 2026)

DEM-assisted design and experimental evaluation of a front-end dispersion feeder for walnut-kernel grading in food processing lines - Jianian Li; Hanjian Deng; Wanghan Zhang; Ai Xiang; Han Yang; Yingjie Yu (Food and Bioproducts Processing, 2026)

Plastic mulching and crop type govern the vertical distribution and composition of microplastics in a major agricultural irrigation system - Xuezheng Yu; Weiying Feng; Liu Wang; Yuxin Deng; Chia Min Ho; Yunping Han; Qingfeng Miao; Meng Zhao; José Manuel Gonçalves; Sundaravelpandian Kalaipandian (Environmental Research, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Cactus-mimetic ZnO nanohybrids: Topography-engineered high efficiency of mechanical bactericidal activity - Wei Deng; Hai Zhang; Congwen Liu; Xiaochen Han; Xiaoling Xu; Zuowan Zhou (Chemical Engineering Journal, 2026)

Anti-fouling ultrafiltration membranes from oxidatively functionalized end-of-life reverse osmosis membranes for mariculture wastewater treatment - Lin Wang; Wenhao Li; Xiangkai Kong; Yifei Zhang; Yuanyuan Tang; Zengyu Ma; Yuhong Zhao; Lina Xu; Senjian Han; Shiqiang Wang; Tianlong Deng (Chemical Engineering Journal, 2026)

Molybdate ion adsorption enhances the chlorine corrosion resistance of NiFe-LDH to stabilize the oxidation mechanism of alkaline seawater - Ziyi Jia; Weiwei Bao; Taotao Ai; Jie Han; Zhifeng Deng; Hongfeng Dong; Junjun Zhang (Chemical Engineering Journal, 2026)

Corrigendum to “Deep learning-enhanced wear-resistant antimicrobial polyurea-based ionogels for real-time firefighter motion tracking in extreme environments” [Chem. Eng. J. 524 (2025) 169444] - Tinghui Deng; Bai Wang; Dongshu Chen; Siyu Han; Jie Ren; Shujun Liu; Jianshe Hu (Chemical Engineering Journal, 2026)

Water-resistant electroluminescent devices with temperature tolerance and mechanical cyclic stability based on hydrophobic nanocellulose - Fang Deng; Ya Lu; Haoyu Sun; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2026)

Nonlinear response and damage evolution mechanisms of subsea tunnels in fault zones under static-dynamic loading - Yunchen Deng; Han Luo; Junhong Huang; Yi Luo; Hangli Gong; Xinping Li; Kaiwen Song; Xuyi Wang; Nana Wang (Marine Georesources & Geotechnology, 2026)

Genome-wide AP2/ERF analysis identifies HmaERF87 as a positive regulator of Hydrangea macrophylla leaf spot resistance - Shuyuan Chen; Xintong Liu; Chengwei Zhang; Ziqin Zhang; Huijie Chen; Yong Han; Shuangshuang Chen; Jing Feng; Guangling Wang; Chang Li; Zedong Wu; Yanming Deng (Plant Cell Reports, 2026)

A unified solution to the low-mass X-ray binary diversity puzzle: saturated magnetic braking coupled with irradiation-driven winds - Zhu-Ling Deng; Xiang-Dong Li; Bo Wang; Philipp Podsiadlowski; Yong Shao; Dong-Dong Liu; Zhan-Wen Han (Science Bulletin, 2026)

Novel insights into the flotation enhancement of fine cassiterite via hydrophobic solid microbubbles: experimental and interfacial interaction force aspects - Zhiguo Han; Shimei Li; Jiushuai Deng; Jianying Deng; Dingquan Xing; Chang Liu; Zhongyi Bai (Process Safety and Environmental Protection, 2026)

Density functional theory-based prediction of novel degradation pathways of PFAS in advanced reduction processes - Haojie Xu; Xinyu Liu; Yaxin Li; Yongjun Han; Yiran Deng; Juanbao Wang; Zhenyu Xu; Hu Zhao; Jiabei Qi; Qingzhu Zhang; Xiangli Shi (Process Safety and Environmental Protection, 2026)

Epsilon-supervised contrastive learning with boundary-gradient sampling open-set fault diagnosis for industrial processes - Qiang Zhao; Mingyu Li; Guangyang Deng; Yinghua Han (Process Safety and Environmental Protection, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Clinically prevalent transposons contribute to erm gene dissemination in the field soil under pseudo-persistent erythromycin contamination - Ziming Han; Yu Zhang; Xiao Luan; Haodi Feng; Yang Wang; Ye Deng; Chengzhi Hu; Min Yang (Journal of Hazardous Materials, 2026)

Development of a multi-criteria indicator for product life cycle decision-making - Yong Han Kim; Sidi Deng; Thomas Maani; Matthew J. Triebe; Nehika Mathur; John W. Sutherland (Journal of Cleaner Production, 2026)

Rhamnolipid@Ag bio-nanofluids for enhanced oil recovery: Multiscale experimental and molecular mechanism elucidation - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Journal of Cleaner Production, 2026)

Weathering-driven clay mineral evolution regulates altitudinal shifts in carbon stabilization within seasonally frozen soils - Zerun Shen; Lulu Zhao; Han Yang; Anbei Deng; Fuxing Liu; Liuling Cheng; Fuwen Jia; Liao Yang; Genming Luo; Zhong-Qiang Chen; Shucheng Xie (Geochimica et Cosmochimica Acta, 2026)

Improvement of surface hydrophilicity by nanometer oxides to promote aluminum-water reaction to generate hydrogen - Gen-Wang Ma; Xiao-Han Guo; Wei-Zhuo Gai; Yang Yang; Jie Zhang; Zheng-hui Pan; Zhen-Yan Deng (Fuel, 2026)

Impact of high voltage electrostatic field under varied storage temperatures: Focusing on protein oxidation and structural changes in chicken muscle - Aijuan Ma; Lisheng Li; Xiaohui Kong; Shuangshuang Jin; Shaolin Deng; Xia Wang; Xiaomei Sun; Xinglian Xu; Minyi Han (Food Research International, 2026)

A behavior-calibrated framework for prioritizing pesticide co-residue burdens in routine monitoring: Method development and a district-level pilot study in Shanghai - Bo Ding; Xiaoxing Lu; Hua Deng; Yuting Zhang; Junyi Shen; Ruobing Han; Jixing Yang (Food and Humanity, 2026)

Corrigendum to “A ready-to-use RNA delivery platform modulated by metal ions” [Chem. Eng. J. 506 (2025) 1–15 (160170)] - Zhaojian Qin; Yongzhuo Jiang; Peng Tao; Haifeng Liu; Han Zhong; Xiaoyi Ding; Runze Zhao; Yi Lu; Lifeng Zhang; Xiaomin Chen; Hongxin Zhuang; Jiao Wu; et al. (Chemical Engineering Journal, 2026)

Stabilizing aqueous LiMn2O4 cathodes through Na+-mediated lattice anchoring and electronic regulation - Yi Wu; Siliang Liu; Zihong Zhang; Yueyong Du; Shengfeng Zhou; Han Wu; Jinfeng Zhang; Wenjie Huang; Qiang Lu; Kai Li; Zongliang Zhang; Yida Deng; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Deep learning-enhanced wear-resistant antimicrobial polyurea-based ionogels for real-time firefighter motion tracking in extreme environments” [Chem. Eng. J. 524 (2025) 169444] - Tinghui Deng; Bai Wang; Dongshu Chen; Siyu Han; Jie Ren; Shujun Liu; Jianshe Hu (Chemical Engineering Journal, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Hepatic Transcriptomics Reveals Sexually Dimorphic Expression of IGF/IGFR Genes Underlying Growth Differences in Spinibarbus hollandi - Sixun Li; Mengmeng Wu; Min Zhang; Zihang Xie; Jie Lai; Lilin Zhan; Ziyan Deng; Guojun Cai; Jian Gong; Chong Han; Qiang Li (Marine Biotechnology, 2026)

Sexually dimorphic expression and hormonal responsiveness of steroidogenic Cyp genes during gonadal differentiation in mandarin fish - Jieming Zhang; Shengyue Lin; Ziyan Deng; Weijian Chen; Guojun Cai; Min Zhang; Lilin Zhan; Chong Han; Jian Gong; Qiang Li (Fish Physiology and Biochemistry, 2026)

Exploring root-mediated Erwinia amylovora invasion mechanism in Korla fragrant pear (Pyrus sinkiangensis) - Lili Han; Yue Sun; Xin Deng; Jiehua Wang; Feng Zhang; Weimin Chen; Rong Lei (European Journal of Plant Pathology, 2026)

Accuracy evaluation of image velocimetry methods for river surface flow measurement using satellite video - Xiaolin Han; Qiang Zhong; Jinghong Deng; Yi Xiao; Fujun Wang (Environmental Fluid Mechanics, 2026)

Effects of cathodic protection potential on soil greenhouse gas emissions and electroactive microbial communities - Chenlu Li; Ying Li; Wenhui Zhong; Cheng Han; Yunbin Jiang; Yongcui Deng; Huan Deng (Applied Soil Ecology, 2026)

Sandstone alternation as revealed by spheroidal weathering in the Carboniferous Taiyuan Formation of Shimenzhai Area, Liujiang Basin - Shiqiang Xia; Hongwen Deng; Zhen Liu; Nadeem Ahmad; Taotao Yan; Wei Wu; Quan Li; Guiyu Dong; Haigang Lao; Xiaoying Han; Bin Gao (Applied Geophysics, 2026)

Iterative 3D Implicit Orebody Modeling Based on Automatic Refinement of Off-Surface Points - Xiancheng Mao; Yuanqian Nie; Zhankun Liu; Hao Deng; Jin Chen; Xiaowen Han (Natural Resources Research, 2026)

Multi-omics unravels energy trade-offs and osmoregulatory strategies in Hyriopsis cumingii under salinity stress - Xiuyan Yang; Chuchu Sai; Han Huang; Wanqi Tan; Yunzhao Lu; Robert Mkuye; Chuangye Yang; Yongshan Liao; Qingheng Wang; Yuewen Deng (Aquaculture, 2026)

The sugar-sensing kinase OSK3-mediated destabilization of OsbZIP58 promotes pre-harvest sprouting in rice under high temperature - Heng Xu; Yuhong Tan; Fudeng Huang; Zhiping Deng; Ningning Zhang; Meihao Sun; Hua Zhang; Heng Zhang; Tao Song; Fulin Wang; Yu Han; Junmin Wang; et al. (Molecular Plant, 2026)

Anomalous contaminant transport in fractured porous media: Insight from asynchronous hydraulic changes in fractures and rock matrix - Lei Ma; Di Han; Qiankun Luo; Yaping Deng; Yunhai Fang; Chao Zhang; Jiazhong Qian (Journal of Contaminant Hydrology, 2026)

Functional characterization of a previously unknown gene governing metamorphosis in Bombyx mori - Tao Lu; Zhiping Xing; Hui Dong; Yuping Deng; Zhipeng Li; Han Gao; Xiaojing Liu; Bo Hu; Anjiang Tan (Insect Biochemistry and Molecular Biology, 2026)

Phosphoric acid-triggered phosphorus transformation: Structural regulation and long-term phosphorus release mechanism of biochar slow-release phosphate fertilizer - Peng Liang; Jiayi Han; Xiaochen Liu; Zihe Deng; Fei Tian; Zhansheng Wu (Environmental Research, 2026)

An AI-guided framework for discovery and evolution of sulfotransferases enables efficient sulfotyrosine bioproduction - Pan Zhang; Yan Chen; Zishuo Zeng; Ziyan He; Han Yu; Junfeng Shen; Ying Han; Huaxiang Deng; Xiaozhou Luo; Xinran Wang (Chemical Engineering Journal, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

Graphitization-driven interfacial polarization and conductivity in core–shell Fe3O4@hydrochar composites achieving high-performance electromagnetic wave absorption - Lin Wang; Yingshan Deng; Zurong Zhu; Dan Michelle Wang; Dafu Chen; Guanghui Bai; Zhongyi Feng; Yao Han; Yueyao Liu; Jinxia Zhai; Chengyun Ning; Zhengao Wang (Chemical Engineering Journal, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

LED light quality–driven growth and metabolism in spirulina maxima: A mechanistic foundation for two-phase optimization - Shuai Jin; Yibin Deng; Mengqi Xiao; Tonghui Deng; Qinliang Jiang; Song Xia; Bing Yan; Pei Han (Algal Research, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Spatiotemporal distribution characteristics and eutrophication status of nutrients in Qinzhou Bay, South China Sea over the past 22 years - Yatong Han; Yan Deng; Chaoxing Ren; Guilan Gao (Frontiers in Marine Science, 2026)
Introduction Elevated nitrogen and phosphorus inputs from human activities have driven coastal eutrophication. Although Qinzhou Bay has long been influenced by anthropogenic disturbances, long-term systematic studies on its nutrient dynamics remain scarce. Methods Based on long-term monitoring data spanning 22 years (2003-2024), this study systematically elucidates the interannual trends, spatiotemporal distribution patterns, and eutrophication status of nutrients in Qinzhou Bay. Results The concentrations of dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphate (DIP) showed an overall upward trend amid interannual fluctuations, yet were characterized by markedly distinct, phase-specific dynamics. The average DIN concentration was at its lowest during 2003-2005, increased sharply over the subsequent seven years, then exhibited a clear declining trend from 2014 to 2022. In the most recent two years, however, the concentration rose again, reaching the peak level for the entire period. The average DIP concentration remained at the lowest level from 2003 to 2014, followed by a marked increase during 2015-2020. Notably, a substantial rise in DIP concentration occurred again in the recent period from 2021 to 2024. Spatially, the distributions of nitrogen and phosphorus were highly overlapping, both showing a decreasing gradient from the inner to the outer bay, with a more pronounced gradient for nitrogen. Principal component analysis confirmed that terrestrial input is the primary driver controlling nutrient distribution. Eutrophication assessment indicated that the bay-head area remained in a eutrophic state for 18 of the past twenty-two years. Discussion These regular changes in nutrients are closely related to the historical development of China's economy and environmental governance. This study provides a long-term case for understanding the historical evolution of nutrients in key bays, and complements the comparative understanding with existing long-term studies.

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Microbial functional shifts under decades-long warming and nitrogen deposition accelerate carbon turnover in desert grassland topsoils - Qun Gao; Qi Qi; Zhengxiong Liang; Sihang Deng; Suo Liu; Zhencheng Ye; Xue Guo; Yi Zhu; Guodong Han; Haiyan Ren; Yunfeng Yang (Soil Biology and Biochemistry, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The application of Cryptococcus laurentii induced by carboxymethyl chitosan remodeled the microbiome of fruit peel and reduced postharvest green mould in grapefruit - Le Yang; Liangjun Xiao; Xianyu Liu; Chao Liu; Han Ye; Rongyu Du; Xiahong He; Fang Wang; Jia Deng (Postharvest Biology and Technology, 2026)

Novel hydroxamic acid collectors with enhanced collecting performance via synergistic electron-donating and hydrophobic effects - Chaozheng Deng; Yancan Zhang; Wei Sun; Haisheng Han (Minerals Engineering, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

A global meta-analysis reveals that plastic mulch enhances crop yields at the cost of soil quality loss and nitrogen-cycle disruption driven by microplastic residues - Xiaoming Li; Shaoyuan Feng; Xuewen Gong; Yu Guo; Qi Lu; Han Guo; Qianyun Deng; Zijian Wang; Zhiming Qi; Youliang Zhang (Field Crops Research, 2026)

Modulating the strength-bulk balance in bamboo chemical thermomechanical pulp via lignin-carbohydrate interactions: Constructing carbon‑carbon and hydrogen bonds - Jian Jiao; Xiu Wang; Ting Jiao; Shanming Han; Hongbin Li; Yongjun Deng; Guigan Fang; Chen Su (Chemical Engineering Journal, 2026)

Integrated end-to-end continuous-flow platform for the process intensification and kilogram-scale production of TADF emitters - Xiaoyan Li; Shoujia Zhu; Ying Wei; Yang Li; Zheng Zhang; Hao Li; Yugang Chen; Yun Deng; Xinxin Han; Quanyou Feng; Linghai Xie (Chemical Engineering Journal, 2026)

High-temperature-stable CNT/SiC ultrafine fibers with superior electromagnetic-wave-absorbing performance via CNT-driven multiple lossy phase modulation - Xiaohan Wu; Yu Deng; Xiaoshan Zhang; Nana Xu; Tao Liu; Peiyuan Zhang; Tianqi You; Songhe Zhang; Cheng Han; Bing Wang; Yingde Wang (Chemical Engineering Journal, 2026)

Based on the “biotin-streptavidin” system to construct exosome- linked hydrogel for promoting healing of chronic wounds in obesity by regulating the NF-κB pathway - Lingxiang Sun; Wenze Han; Yilin Ping; Xi Chen; Xuedong Deng; Zheng Wang; Jingjing Deng; Jian Zhou; Tingting Wu; Yifan Zhao; Xiuping Wu; Bing Li (Chemical Engineering Journal, 2026)

Cyclophosphamide-induced iron homeostasis imbalance triggers ovarian toxicity through ferroptosis of ovarian granulosa cells in a mitophagy crosstalk manner - Bo Xu; Xiaoqiang Luo; Tengjiao He; Yu Deng; Yitong Shang; Hang Han; Xufeng Fu (Chemico-Biological Interactions, 2026)

Characterization of Plant Residue Decomposition and Uranium Release from U–Cd-Contaminated Plants - Han jiangyue; Zhang haojie; Tan jinlong; Xie yuqi; Chen binbin; Deng qinwen (Water, Air, & Soil Pollution, 2026)

Integrated petrographic and statistical analysis of the Late Paleozoic Taiyuan and Shanxi formations, Northern China Block: Implications for depositional environments and provenance - Lei Xue; Haijun Wang; Muhammad Rizwan; Ke Han; Mintao Dong; Hualong Yu; Rukui Lu; Chao Deng; Xin Cheng (Carbonates and Evaporites, 2026)

TSUD: A deep learning-based approach for slope unit delineation in Loess Yuan landforms - Fan Liu; Tianyu Zhang; Yahong Deng; Faqiao Qian; Yan Wang; Xue Han; Jingkang Feng (Journal of Geographical Sciences, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Single-cell transcriptomics and multimodal molecular profiling revealed the oncogenesis and tumor microenvironment of cardiac myxoma - Xinyi Yu; Yibo Shi; Mingjie Xie; Kailong Deng; Zean Fu; Shuang Hao; Yu Pei; Zhenxing Liang; Longhui Guo; Jia Li; Jingchao Zhang; Xinwei Han (Science China Life Sciences, 2026)

Reinforced stepwise dissociation of water molecules via U 5f-O 2p-Ti 3d gradient orbital coupling for photoelectrochemical water splitting - Xiaochuan Deng; Tong Liu; Xudong Wu; Qijue Lin; Hanlin Liu; Han Yang; Xun Yang; Maoyin Wang; Kaiguo Chen; Jiayu Dai; Tao Chen; Wenkun Zhu (Science Bulletin, 2026)

Arsenic recovery by UV/sulfite/iodide system: Dual roles of carbonate/bicarbonate - Xilong Zhou; Haoxiang Zhong; Jianing Han; Qiaozhi Li; Ziqi Zheng; Meifang Li; Hui Wang; Ying Fang; Jiaqin Deng; Xinjiang Hu (Journal of Cleaner Production, 2026)

Distribution of microplastics and microorganisms and their relationship in high-salinity soil - Yuping Ma; Jing Bian; Jianguo Liu; Yunping Han; Weiying Feng; Yuxin Deng; Xuezheng Yu; Jun Zhang; Haiping Li; Yingnan Cao (Journal of Environmental Sciences, 2026)

The Shaweitaizi river-blocking landslide and its impacts on landscape evolution in the downstream of the Jinsha River - Chenglin Ye; Jianhui Deng; Fei Chen; Liang Liang; Jianhua Han; Hua Li (Geomorphology, 2026)

Homogeneous selection and immigration limitation jointly shape brewing- suitable microbiomes in distillery workshops across Maotai town - Shuang Han; Qing He; Youcui Yang; Juan Shen; Chunyan Long; Xiaofei Zou; Haoting Yan; Guang Feng; Gangxiang Fei; Lu Qiao; Kai Feng; Mingqian Liu; et al. (Food Research International, 2026)

Effect and mechanism of prophage lysogeny on antimicrobial resistance and virulence of Staphylococcus aureus from retail meat - Wenyuan Zhou; Wenjuan Li; Yeling Han; Aiping Deng; Yajie Li; Lei Yuan; Dan Xiong; Guoqiang Zhu; Zhenquan Yang (Food Research International, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Efficient ultraviolet emission via Ce3+-doped lead-free double perovskite nanocrystals for multicolor and full-spectrum luminescence - Zewen Wang; Xiaowei Deng; Xu Chen; Weilong Qin; Meng Wang; Yongjie Zai; Mochen Jia; Ying Liu; Zhuangzhuang Ma; Jibin Zhang; Linyuan Lian; Yanbing Han; et al. (Chemical Engineering Journal, 2026)

BTEXS metabolites and lung dysfunction in petrochemical workers: Dose-response relationships and the mediation of oxidative stress - Dongsheng Wang; Rui Ma; Minghui Xiao; Zhaorui Zhang; Han Yang; Yanrong Lv; Shaorui Yu; Xiumei Xing; Shanfeng Dang; Qifei Deng; Xiaoyu Mao; Qiansheng Hu; et al. (Atmospheric Pollution Research, 2026)

Enhancing the solubility and thermostability of nitrilase through surface hydrophobic residue engineering - Ziyi Li; Yina Ren; Yuxuan Jiang; Chenlan Yan; Yiqi Deng; Yiyi Li; Zhemin Zhou; Laichuang Han (Systems Microbiology and Biomanufacturing, 2026)

Characterization, expression and evolution analysis of NLRC3 , NLRC5 and NLRX1 in Mastacembelus armatus under Aeromonas veronii infection - Shengyue Lin; Kaifeng Wang; Weijian Chen; Ziyan Deng; Guojun Cai; Min Zhang; Zihang Xie; Weibin Li; Chong Han; Qiang Li (Journal of Fish Biology, 2026)
NOD‐like receptors (NLRs) serve as crucial innate immune sensors in multicellular organisms, recognizing diverse pathogen‐associated components and regulating immune responses such as nuclear factor kappa B (NF‐κB) signalling and inflammatory pathways. To elucidate the roles of NLRC3 , NLRC5 and NLRX1 in the innate immunity of the Mastacembelus armatus , this study first characterized these genes and examined their response to Aeromonas veronii infection. We identified the three NLR genes from the M. armatus transcriptome and analysed their evolutionary relationships through domain architecture and maximum likelihood (ML) phylogenetic reconstruction. All three NLR proteins contained conserved NACHT and leucine‐rich repeat (LRR) domains, and ML phylogenetic analysis grouped M. armatus with other Synbranchiformes and Perciformes, consistent with established taxonomy. Tissue expression profiling in healthy fish revealed constitutive expression of all three genes across nine examined tissues, with significantly higher levels in gills, suggesting their involvement in frontline mucosal immunity. Temporal expression analysis in spleen, liver and kidney following A. veronii challenge showed distinct organ‐specific patterns: although all three genes were downregulated in the liver, they were significantly upregulated in spleen and kidney, indicating these as primary sites for NLR‐mediated immune responses in M. armatus . Selection pressure analysis using CodeML identified widespread purifying selection across teleost NLRs, alongside multiple positively selected sites in NLRC5 (7 sites in site model, 5 in branch‐site model) and NLRX1 (2 sites in site model, 22 in branch‐site model). These findings provide fundamental insights into NLR‐mediated immunity in M. armatus and contribute to understanding the evolution and function of NLR genes in teleosts.

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Prediction of HRR in tunnel fires under different tunnel inclinations and ambient pressure conditions based on recurrent neural networks - Wei Liu; Tiannan Li; Haoran Li; Han Wu; Lei Deng; Congling Shi (Tunnelling and Underground Space Technology, 2026)

Improvement of the treatment of swine wastewater by rational allocation of readily degradable organic matter - Hui Wang; Hongnan Yang; Yingying Cai; Wenkai Han; Lan Wang; Wenguo Wang; Xiong Wei; Liangwei Deng (Journal of Water Process Engineering, 2026)

Impact of water level fluctuations on lacustrine groundwater discharge and groundwater-borne nutrient import into lakes - Yao Du; Xiaoliang Sun; Jiawen Xu; Huanhuan Shi; Hao Tian; Peng Han; Yamin Deng; Yiqun Gan; Yanxin Wang (Journal of Hydrology, 2026)

Deciphering the environmental fate of halogenated organic compounds in cold seep sediments: Insights from non-targeted analysis and metagenomics across vertical redox gradients - Hao Yu; Xiaoyan Zhang; Yanpeng Liang; Qinglin Mu; Xiaolei Shi; Zhaochao Deng; Jiawang Chen; Jun Cao; Yinan Deng; Zhiqiang Han; Haixin Chen; Chunfang Zhang (Journal of Hazardous Materials, 2026)

Red phosphorus triggers endogenous iron activation of sludge biochar for peroxymonosulfate activation: Unravelling superoxide radical and non-radical degradation mechanisms - Minghui Xiang; Zhikang Deng; Yongfei Ma; Yifan Liu; Xiaoyu Xiang; Han Ding; Ranran Zhang; Hui Lin; Junwei Ma; Yongzhen Ding; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal patterns, human health risks, and driving mechanisms of ARGs in the littoral zones of the largest shallow lake in North China - Kai Deng; Lei Wang; Aiwen Wang; Xun Han; Lining Zhao; Yulong Zhang; Dan Ma; Fei Zheng; Sijun Dong (Journal of Environmental Chemical Engineering, 2026)

Identification and algicidal mechanism of extracellular polysaccharides from Sulfitobacter pseudonitzschiae H46: A novel biocontrol agent for Chattonella marina bloom - Jiaxuan He; Lin Yang; Xin Yin; Jiahui Zhao; Yadan Deng; Jinfeng Ding; Shuai Wang; Bin Han; Li Zheng (Harmful Algae, 2026)

Chitosan and sulfated glucan nanoparticles: A novel strategy for cryopreservation of Lactobacillus plantarum - Tingyue Deng; Xiaowei Shen; Zeyu Han; Jing Liu; Bolin Zhang; Hongfei Zhao (Food Research International, 2026)

Towards high-performance sperm selection: Decoding sperm-biointerface dynamics for next-generation microfluidic sorting platforms - Weiyao Wu; Yifu Wang; Jiarun Xu; Derrick Boateng; Bing Deng; Jianghong Wu; Linbo Han (Chemical Engineering Journal, 2026)

Unlocking high-solid biorefining of corn stover via ball milling: paving the way for profitability - Kaili Ding; Xueyan Liang; Xiwen Jia; Aihua Deng; Haitao Yu; Lujia Han; Jiajie Xu; Weihua Xiao (Chemical Engineering Journal, 2026)

Flow-induced shear enhancement of dynamic lubrication surfaces for combating complex biofouling in biliary stents - Jiaxin Liu; Junchang Guo; Wei Liu; Han Yao; Linjie Guo; Yuan Gao; Bingyang Lu; Luohuizi Li; Huali Yu; Jing Luo; Liansong Ye; Xu Deng; et al. (Chemical Engineering Journal, 2026)

NbB2-Fe self-cascading glucose oxidase-like and peroxidase-like nanoparticles - Sihua Deng; Jiangling Wu; Menglin Li; Yaqing Chen; Yifan Han; Qi Zhou; WenSheng Fu (Chemical Engineering Journal, 2026)

Uncovering hidden VOCs risks in metro halls: A non-targeted screening and health risk during extreme summer heatwaves - Han Wang; Jiyue Wang; Guangming Li; Youyan Chi; Mengsi Deng; Kwok Wai Tham; Chunhui Li (Building and Environment, 2026)

Metagenomic evidence for adaptive P-acquisition strategies to sustain elevated soil microbial biomass P under swine manure fertilization - Yunbin Jiang; Yijie Zhao; Cheng Han; Huan Deng; Kailou Liu; Shangshu Huang; Wenhui Zhong (Soil Ecology Letters, 2026)

Effect of temperate phage SapYZUs891 as a biocontrol agent on the Chinese foodborne multidrug-resistant Staphylococcus aureus isolates - Xiaoxing Fan; Zhilan Yao; Yuhong Wu; Wenjuan Li; Yeling Han; Xuan Li; Aiping Deng; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Archives of Microbiology, 2026)

Differential enrichment mechanisms of organic matter in middle-upper Triassic lacustrine mudstone, north Kuqa depression (Tarim Basin, China): An integrated approach utilizing inorganic and organic geochemical evidence - Dejiang Li; Qun Zhao; Lingyu Zhao; Yanpeng Chen; Ze Deng; Xiangchun Chang; Bingbing Shi; Runye Han; Shangbin Wang (Acta Geochimica, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Synergistic pyrogenic carbon-microbial dehalogenator taking the “forever” out of “forever chemicals” - Kaikai Zhang; Jiayu Deng; Wei-Han Lin; Caide Huang; Deyi Hou (Water Research, 2026)

Unveiling melatonin-induced defense mechanisms in postharvest kiwifruit against Botrytis cinerea through multi-omics analysis - Xianyu Liu; Liangjun Xiao; Chao Liu; Dengjuan Tian; Le Yang; Rongyu Du; Han Ye; Xiahong He; Fang Wang; Jia Deng (Postharvest Biology and Technology, 2026)

Genome-wide identification and expression analyses reveal cell wall degradation gene family networks in kiwifruit softening - Zhan Shi; Shenzhong Gao; Fabi Shen; Han Yang; Yongsheng Liu; Yinan Yao; Jikai Liu; Lijun Wang; Yongfeng Gao; Peng Shu; Heng Deng (Plant Science, 2026)

Association between serum metal exposure in early pregnancy and preterm birth: Mediation by inflammatory blood cell parameters - Wenjun Yao; Luodan Zhang; Ziyi Wang; Weiguo Yao; Wanxin Wu; Fa Zeng; Maozhen Han; Peng Zhu; Fangbiao Tao; Fang Deng; Jian V. Zhang; Binbin Huang (Journal of Hazardous Materials, 2026)

Identifying active nitrate-assimilating bacteria that alleviate secondary salinization in facility soil driven by carbon source availability - Qian Wang; Ran Liu; Cheng Chu; Yunbin Jiang; Huan Deng; Xinqi Huang; Cheng Han; Wenhui Zhong (Journal of Cleaner Production, 2026)

Nitric oxide-releasing porphyrinic metal-organic frameworks as a promising antimicrobial material against foodborne pathogens - Han Deng; Yi Liu; Yang Yi; Liang Ke; Wenhao Hu; Changqing Han; Hongxun Wang; Huajuan Wang; Min Zhou (Innovative Food Science & Emerging Technologies, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Fluorinated amino covalent organic frameworks for efficient adsorption of per- and polyfluoroalkyl substances in water - Fanke Tong; Ruitong Zhang; Deyan Li; Han Qu; Xiang Li; Qiang Gao; Delin Qi; Shubo Deng; Wei Wang (Environmental Research, 2026)

Rehabilitation of damaged ECC–NC composite column using UHPC jacket - Xianzhi Zeng; Haishen Wang; Zhongqi Han; Peng Pan; Kailai Deng (Engineering Structures, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Traditional cupping-inspired sampling of skin interstitial fluid combined with gold nanobipyramids for multicolor visual detection of miRNAs - Qing Xiong; Chuxiang Hu; Siqi Li; Lisong Pang; Benson K. Kosgei; Xiaoyu Deng; Zhixin Li; Ray P.S. Han; Yingzhou Tao; Shaohua Xu (Chemical Engineering Journal, 2026)

Heat blocking mechanism and performance evaluation of flame-retardant modified bacterial cellulose aerogel for lithium-ion battery thermal runaway propagation prevention - Xiangming Hu; Zhijun Zhang; Yurui Deng; Zhiyuan Yang; Yajie Luo; Lihua Jiang; Mengdan Zhang; Longfei Han; Yuan Cheng (Chemical Engineering Journal, 2026)

Acid etching boosting low-temperature catalytic performance for propane oxidation over Mn-based spinel oxide catalyst - Long Zhang; Peiqi Chu; Yuxin Han; Yahan Wang; Shaohan Lian; Meng Guo; Erhong Duan; Yuxi Liu; Hongxing Dai; Jiguang Deng (Chemical Engineering Journal, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Asymmetric Propagation of Hydraulic Fractures in Coal–Rock Composite Formations: Insights Based on Stress Sensitivity of Coal - Zhaolong Ge; Changzheng Lu; Qinglin Deng; Zhe Zhou; Shuo Dai; Jing Han; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Optimizing environmental surveillance for early detection of zoonotic pathogens via fecal shedding modeling - Xin Du; Zhiqiang Deng; Yuqing Long; Fenglan He; Chunlong Zhu; Chun Han; Hui Li; Songzhe Fu (Water Research, 2026)

Synergistic virulence of H9N2 AIV and APEC co-infection in laying hens involves a critical role for macrophage-mediated hyper-inflammation via the MAPK/NF-κB axis - Jinjie Han; Wenchi Chang; Zhaoyue Jing; Dong Xiao; Tiantian Ji; Junyang Fang; Mengzhao Song; Wei Li; Jingyu Wang; Wen Deng (Veterinary Microbiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

POINT: a web-based platform for pharmacological investigation enhanced by multi-omics networks and knowledge graphs - Zihao He; Liu Liu; Dongchen Han; Kai Gao; Lei Dong; Xiaoning Qi; Dechao Bu; Peipei Huo; Zhihao Wang; Xuan Fan; Jingming Sun; Shuangshuang Lei; et al. (Science Bulletin, 2026)

Heuristic resistance-driven graph approach for preferential flow pathway identification in 3D discrete fracture networks - Lei Ma; Jixian Li; Yaping Deng; Di Han; Haichun Ma; Xuelin Cui; Jiazhong Qian (Journal of Hydrology, 2026)

Sterilization efficacy of aluminum ion based Fenton-like solution - Gen-Wang Ma; Xiao-Han Guo; Qiang Xie; Wei-Zhuo Gai; Yang Yang; Hongxia Chen; Zhen-Yan Deng (Journal of Environmental Chemical Engineering, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

EnBoT-SORT: Hierarchical fusion-association tracking with pseudo-sample generation for dense thermal infrared UAVs - Jinxin Guo; Weida Zhan; Yu Chen; Depeng Zhu; Yichun Jiang; Xiaoyu Xu; Deng Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multifunctional nano-enabled films and coatings for food packaging: a review of advances in active protection and intelligent monitoring - Yi Liu; Huajuan Wang; Han Deng; Ting Min; Hongxun Wang; Yang Yi; Zhiyong Song; Min Zhou (Food Research International, 2026)

Protein “memory effect” induced by a heat transfer-directed precooling strategy enhances milk cream foam stability - Yiqiu Deng; Xiuhang Chai; Wanjun Han; Yuanfa Liu; Wengao Wang (Food Research International, 2026)

Per- and polyfluoroalkyl substances induce cytotoxicity in NCI–H446 cells through modulating proliferation, apoptosis, and m6A methylation - Liping Wei; Xinlu Sun; Zisu Deng; Simei Chen; Kexin Han; Lili Wen; Liming Tan; Tingting Miao (Food and Chemical Toxicology, 2026)

In-situ fabrication of magnetic prussian blue composites for highly selective rubidium recovery from high-salinity brine - Zheng Li; Zilong Chen; Chi Ma; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Desalination, 2026)

Rapid predictions of platinum degradation in cathode catalyst layers based on Ostwald ripening theory and numerical insights - Yu-Han Xu; Wen-Zhen Fang; Kai-Bo An; Zi-Hao Xuan; Deng-Ke Hu; Yi Zhu; Wen-Quan Tao (Chemical Engineering Journal, 2026)

Summertime characteristics and in-situ photochemistry of volatile organic compounds in a high-altitude region in central China: Implications of regional transport - Zhaoqi Wang; Chunmian Yang; Haibin Huang; Mengjie Deng; Jiapeng Ran; Xiaoxiao Li; Xiaofen Pei; Han Yue; Hairong Cheng (Atmospheric Research, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Development of an optimum long-term refueling strategy for Moltex stable salt reactor - Seungug Jae; Puran Deng; Han Gyu Lee; Won Sik Yang; Thanh Hua; Yan Cao; Rory O’Sullivan (Annals of Nuclear Energy, 2026)

Highly virulent Aerococcus viridans activates the RIPK3 signaling pathway, inducing necroptosis and inflammation in bovine mammary epithelial cells and murine mammary tissue - Siyu Meng; Maolin Xu; Xian Deng; Zimeng Zhu; Herman W. Barkema; John P. Kastelic; Eduardo R. Cobo; Bo Han; Gang Liu (Veterinary Microbiology, 2026)

Host protein interactome profiling of Akabane virus glycoprotein Gc reveals specific mitochondrial genes regulate viral replication - Han Gao; Menghua Deng; Mengna Deng; Canyuan Li; Dengshuai Zhao; Xiangxiang Tan; Shengfeng Chen; Limei Qin; Keshan Zhang (Veterinary Microbiology, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Global grain crops non-CO2 greenhouse gas emissions and mitigation potential integrating food security and climate change scenarios - Yunxiao Gao; Ze Han; Zhihui Li; Xiangzheng Deng (Resources, Conservation and Recycling, 2026)

Spatial variability of lacustrine groundwater discharge at basin scale - Xiaoliang Sun; Yao Du; Jing Wu; Jiawen Xu; Hao Tian; Peng Han; Yamin Deng; Yiqun Gan; Yanxin Wang (Journal of Hydrology, 2026)

Geogenic ammonium enrichment driven by groundwater recharge pattern in quaternary alluvial-lacustrine aquifers of the central Yangtze River Basin - Shuai Shen; Yao Du; Yamin Deng; Jingwei Zhang; Yilin Zhao; Zhihui Han; Teng Ma (Journal of Hydrology, 2026)

Chronic nanoplastics exposure drives lung cancer progression through ATF3/PCK2 axis-mediated rewiring of truncated gluconeogenesis - Qian Li; Wenwen Meng; Chengting Xie; Fei Wang; Yating Deng; Keying Chen; Yi Li; Yuqiao Li; Yixian Wen; Jing Zhu; Tingli Han; Xuemei Chen; et al. (Journal of Hazardous Materials, 2026)

Radical-Net: A chemistry-enhanced transformer for elementary radical reactions in pollutant chemistry - Zhi Huang; Jiang Yu; Wei He; Pengxinyue Huang; Siwei Deng; Hongbin Jiang; Jie Yu; Chun Yang; Cheng Han; Yinying Jiang; Weiwei Zhu; Yucheng Liu (Journal of Hazardous Materials, 2026)

Contributions from source enrichment and late hydrothermal activity to the formation of the No. 782 REE-Nb-Zr deposit, NE China - Zeen Han; Guozhan Xu; Mingqian Wu; Deyou Sun; Xiaohui Zeng; Bizheng Yang; Xingmin Zhang; Weipeng Liu; Changzhou Deng (Journal of Geochemical Exploration, 2026)

Antibiotics in northern China's largest shallow wetland lake: Occurrence, bioaccumulation, ecological risk, and indicator screening - Kai Deng; Lining Zhao; Meiyu Li; Xueyou Liang; Xiaobo Wang; Jinze Han; Yulong Zhang; Ryoiti Kiyama; Sijun Dong (Journal of Environmental Sciences, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

A novel aqueous synthesis of anion exchange membranes for fuel cells - Xia Liu; Zhongshan Feng; Cuiwen Deng; Quan Yang; Minhao Wang; Xinjie Zhang; Yi Hu; Yufan Zheng; Juan Zeng; Bencai Lin; Juanjuan Han (Fuel, 2026)

Revealing the mechanism of nitrogen migration during the pyrolysis of 3-amine caprolactam: Integrated experimental and DFT simulation studies - Zhenqing Han; Jun Shen; Yun Guo; Shengxiang Deng; Sha Wang; Haiyong Peng; Chen Zhang (Fuel, 2026)

Physicochemical attributes and stabilization mechanism of emulsions stabilized by microfluidized soybean by-products - Jia Liu; Qiaomei Wang; Luyao Shi; Lu Han; Zaifei Zheng; Peng Wang; Ahmed S.M. Saleh; Daozi Deng; Zhigang Xiao; He Liu; Chunfang Ma (Food Structure, 2026)

Modulating the multiscale structure and digestibility of OSA starch by phenolic acid substituents and heating process - Ran-Ran Deng; Ran Feng; Han Tao; Bao Zhang (Food Chemistry, 2026)

Ferroptosis triggered by gill dysbiosis mediates immune failure in grass carp overwintering syndrome - Yang Feng; Senyue Liu; Xiaoli Huang; Yi Geng; Chengyan Mou; Han Zhao; Jian Zhou; Qiang Li; Yongqiang Deng (Fish & Shellfish Immunology, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Strip tillage enhances the synergy of higher maize yield, less energy consumption, and lower carbon footprint in high latitude areas of Northeastern China - Mengyao Han; Haotian Chen; Yan Zhang; Zhijia Gai; Baifu Jiang; Lijun Cai; Chunjiang Wang; Aixing Deng; Weijian Zhang; Zhenwei Song (European Journal of Agronomy, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Rational design of type-I p-CuO/n-NUS-8 heterojunctions for highly selective photocatalytic CO2 reduction to CH4 - Xin Huang; Zuoyi Wang; Ying Jiang; Wenwen Wen; Shixia Chen; XinXin Han; Jingwen Chen; Shuguang Deng; Jun Wang (Chemical Engineering Journal, 2026)

Instant gel-forming microcapsules based on micronized-κ-carrageenan for bitter taste quenching bioinspired by the passion fruit seed - Jiao Song; Linjie Tian; Shuyu Deng; Yifei Zhang; Junzhi Lin; Zhiping Guo; Hongyan Ma; Dingkun Zhang; Li Han; Zhimin Ci (Carbohydrate Polymers, 2026)

Programmable and multi-stimuli responsive hydrogel actuator mediated by nanocellulose with intrinsic self-sensing capacity - Ya Lu; Shengnan Li; Fang Deng; Yiying Yue; Shuijian He; Shaohua Jiang; Mingqiang Ye; Yihui Zhou; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2026)

Enhancement of microalgal carbon fixation via synergistic interactions with a facultative autotrophic bacterium Cytobacillus KQ-2 - Dandan Yao; Yunhui Li; Zhiqian Han; Ding Tan; Meng Wang; Huan Deng; Hui Wang; Yun Liu (Bioresource Technology, 2026)

Linkages between enhanced soil cellobiohydrolase activity and nutrient status-driven shifts in cbhI-harboring fungal community under long-term swine manure fertilization - Yangyang Li; Cheng Han; Huan Deng; Wenhui Zhong; Kailou Liu; Shangshu Huang; Yunbin Jiang (Applied Soil Ecology, 2026)

Comparison of soil enzyme activity and stoichiometry between urban park and forest in the Pearl River Delta region, China - Han Sheng; Xu Li; Luis Carlos Ramos Aguila; Fasih Ullah Haider; Shu-Yi-Dan Zhou; Guopeng Wu; Chushu Meng; Yunxuan Deng; Juxiu Liu (Applied Soil Ecology, 2026)

Design and experimental evaluation of a multi-configuration ultrasonic driller for multi-angle drilling on extraterrestrial complex terrain - Naiwen Deng; Xingwang Zhang; Yong Pang; Guangchao Han; Wei Bai (Advances in Space Research, 2026)

“Soft” and “Hard” governance instrument configuration structures and water governance effectiveness: a case study of the river chief system - Haijiao Du; Qunzhao Deng; Jintao Li; Zhijian Wu; Bofu Zheng; Han Liang (Environment, Development and Sustainability, 2025)

Research on the IMOACO Path Planning Algorithm for Rescue AUVs - Zhongchao Deng; Yuang Gao; Shilin Han; Xiaokai Mu; Guiqiang Bai; Yifan Xue; Zhongben Zhu; Hongde Qin (Journal of Marine Science and Engineering, 2025)
To address the challenges faced by autonomous underwater vehicles (AUVs) in search and rescue missions—specifically, vulnerability to ocean current interference and low task efficiency in complex marine environments—this paper proposes an Improved Multi-objective Ant Colony Optimization (IMOACO) algorithm. By incorporating ocean current dynamics and energy constraints, a current-guided multi-objective evaluation function and state transition function are constructed to guide AUVs to preferentially follow downstream paths. On this basis, the entropy weight method is integrated to enhance the heuristic function and pheromone update strategy of the Ant Colony Optimization (ACO), and a dynamic priority strategy is employed to optimize the traversal sequence of multiple objectives. Grid-based simulations using real nautical charts and field trials with the “Xinghai 300R” AUV demonstrate that the proposed method significantly improves path smoothness and mission efficiency, with the IMOACO algorithm achieving a 34.7% increase in multi-objective search efficiency. The results indicate that this method is well-suited for multi-objective search and rescue missions in environments with strong ocean current disturbances, offering strong potential for practical engineering applications.

A physics-informed hybrid neural network for interpretable and accurate fish growth prediction in recirculating aquaculture systems - Daode Zhang; Zhiwei Xie; Wupeng Deng; Enshun Lu; Shihao Zhang; Han Gao (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Study on the carbonation environment characteristics of highway tunnels based on long-term field testing - Xingbo Han; Mohan Li; Zhi Chen; Peiyuan Wang; Nianbing Deng; Haiting Yang; Fei Ye (Tunnelling and Underground Space Technology, 2025)

Evaluating quasi-elastic behavior in granular Materials: Insights from cyclic loading tests - Pingxin Xia; Qingqing Fu; Wen Deng; Xiaoshuang Li; Maosen Han; Tiande Wen (Soil Dynamics and Earthquake Engineering, 2025)

Late Ediacaran to early Cambrian tectono–depositional pattern of the western upper Yangtze Block, SW China: Implications for the break–up of the Pannotia supercontinent - Jinmin Song; Xin Jin; Zhiwu Li; Benjian Zhang; Lingli Zhao; Yi Ding; Di Yang; Yuehao Ye; Han Wang; Haoshuang Deng; Bin Wang; Jiamin Xue; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Comprehensive life cycle carbon emission estimation of coalfield spontaneous combustion using time series thermal infrared remote sensing - Jinchang Deng; Bobo Shi; José L. Torero Cullen; Yong Xue; Liying Han (Journal of Cleaner Production, 2025)

Impact of regionally transported biomass burning on carbonaceous aerosol characterization, contribution and degradation in Pu'er, Southwest China - Jianwu Shi; Wenjun Rao; Chenyang Zhao; Li Deng; Xinyu Han; Wei Du; Jianhong Huang; Senlin Tian; Ping Ning; Jiming Hao; Yaoqian Zhong (Journal of Environmental Sciences, 2025)

Chili-mediated aroma-taste interactions improve saltiness and umami perception in reduced-salt beef sauce - Qiang Liu; Min Wang; Zaifei Zheng; Zixuan Wang; Tianlong Han; Yuting Hou; Meilin Deng; Dengyong Liu (International Journal of Gastronomy and Food Science, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Efficient radiocobalt removal from seawater and radioactive liquid waste using a radiation-stable layered metal sulfide ion exchanger - Fei Han; Aocheng Yuan; Zhi Zhang; Qingquan Deng; Jiaoting Li; Shuibo Wu; Mingdong Zhang; Jingli Mu (Desalination, 2025)

Green synthesis and functionalization of rice husk-derived SiO₂ nanoparticles for scale inhibition: A multiscale study combining experiments, molecular dynamics simulations, and quantum chemical calculations - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Quercetin-loaded milk-derived extracellular vesicles for the treatment of inflammatory bowel disease by alleviating senescence-associated cell cycle arrest - Runrun Wan; Tingting Cao; Meng Deng; Chengbiao Hu; Caixiao Liu; Yijuan Han; Na Zhao; Qiaoning Wang; Xueru Li; Xiangdong Wang; Chenghu Hu; Zhang Yuan (Chemical Engineering Journal, 2025)

Barnacle-inspired robust adhesive strategy integrating with surface topological engineering for durable fire protection of polyurethane foam - Fenglin Wu; Shihu Han; Xiaoping Hu; Cong Deng (Chemical Engineering Journal, 2025)

Fast-crosslinking, shape-adaptable, conductive, and dual-antibacterial hydrogels based on oxidized dextran and polyvinyl alcohol-ε-polylysine for infected skeletal muscle healing - Yi Guo; Silu Wang; Haoping Wang; Dian Zhang; Litong Shen; Xiaojuan Han; Xin Zhao; Baolin Guo; Zexing Deng (Carbohydrate Polymers, 2025)

Morphological, histological and multi-omics analysis revealed the molecular response of female western mosquitofish (Gambusia affinis) to levonorgestrel exposure - Kaichun Chen; Tongfu Lu; Weijian Chen; Shengyue Lin; Dingxian Chen; Shuzheng Ye; Weiqian Liang; Sixun Li; Binhua Deng; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

GSDMD deficiency mitigates intestinal damage via macrophage pyroptosis control in experimental NEC - Yihang Yang; Xinyi Yang; Yue Ma; Xinli Liu; Dandan Mo; Cuilian Ye; Qin Deng; Wenli Han; Xionghui Ding; Chunbao Guo (Inflammation Research, 2025)

Mechanical regulation of N2A neural cell behavior by microtissue densification - Yuxia Ma; Xiaoning Han; Wenjuan Zhu; Linhong Deng; Xiang Wang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Tertiary lymphoid structure signatures are associated with survival and immunotherapy response in lung adenocarcinoma - Bing Han; Jikun Deng; Rongmei Fan (Immunologic Research, 2025)

CircNOX4 promotes proliferation and resistance by regulating the hsa-miR-6884-5p/YWHAG Axis and ERK signaling pathway in cholangiocarcinoma - Zhangdi Yan; Lixin Du; Yingdi Han; Kangshuai Li; Guoli Sheng; Xudong Wang; Yunjia Liu; Yuankun Zhang; Jian Deng; Zengli Liu; Yunfei Xu; Zongli Zhang; et al. (Functional & Integrative Genomics, 2025)

Impact of sugarcane cropping duration on soil aggregate stability and erodibility in subtropical regions - Zhihui Deng; Xiaoqian Duan; Jiexin Han; Jingmi Wang; Zhe Lin; Yusong Deng (Journal of Mountain Science, 2025)

Application of pre-stack geostatistical inversion in prediction of thin high-quality conglomerate reservoir in Shawan Depression, Junggar Basin - Zhiguo Cheng; Zeliang Liang; Junfeng Han; Tingting Hu; Gaoshan Deng; Chunming Jia; Jian Guan (Frontiers of Earth Science, 2025)

Characteristics and Impact Mechanisms of Spatiotemporal Patterns of Carbon Emissions in China’s Urban Agglomerations - Qingxi Shen; Yujie Zhu; Zerui Han; Yifan Deng; Ruijing Wen (Chinese Geographical Science, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Study on hydrodynamic characteristics and power generation performance of FPV with a pneumatic breakwater - Peng Li; Penghao Zhang; Qing Wang; Xinyu Han; Zhongbo Deng; Xiaohui Ren; Longrui Fan; Jun Wang; Lei Wang; Yijie Huang (Ocean Engineering, 2025)

An emerging paradigm for scientific decision: the AI evaluation of space science projects - Qiwen Deng; Yanzhong Wen; Chaosen Liu; Xinyang Yue; Jianfei Sun; Yuexia Han (Life Sciences in Space Research, 2025)

Cardiorespiratory benefits of reducing indoor particulate matter depend on immune improvements: Insights into individual heterogeneity from a randomized, double-blind crossover trial - Aojing Han; Wenlou Zhang; Luyi Li; Di Yang; Yetong Zhao; Qisijing Liu; Wanzhou Wang; Shan Liu; Xuezhao Ji; Xiaoming Shi; Jing Huang; Shaowei Wu; et al. (Journal of Hazardous Materials, 2025)

Combined impact of land-use/land-cover and soil property changes on soil erosion in the Yellow River Basin - Yang-Yang Wang; Xin-Xiao Yu; Deng-xing Fan; Guo-Dong Jia; Jian-Zhi Niu; Yong-Han Feng; Yu-Kun Wang (Journal of Environmental Management, 2025)

Construction of OSA-starch and caffeic acid composite system driven by high pressure homogenization: Multiscale structural evolution and digestibility regulation mechanism - Ran-Ran Deng; Ran Feng; Ran Meng; Si-Jie Wu; Han Tao; Bao Zhang (Food Chemistry, 2025)

Deep learning-enhanced wear-resistant antimicrobial polyurea-based ionogels for real-time firefighter motion tracking in extreme environments - Tinghui Deng; Bai Wang; Dongshu Chen; Siyu Han; Jie Ren; Shujun Liu; Jianshe Hu (Chemical Engineering Journal, 2025)

Mycelium-derived self-healing electrodes for high-performance and biodegradable supercapacitors - Zhimin Li; XiaoFang Deng; GuanHui Chen; Ziyu Zhang; Jianshan Han; Xiaoquan Lu (Chemical Engineering Journal, 2025)

Synergistic Mn-doping and MXene coupling in sulfur-deficient In2S3 nanosheets for high-performance sodium-ion batteries - Manman Zhang; Qi An; Haocun Ba; Boxi Wang; Beibei Li; Chengjiang Deng; Liuyuan Ma; Yinghong Lan; Xiaoyan Han; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Synergistic interaction between hydrophilic polyglycerol fatty acid esters and sucrose esters regulates fat crystallization at the water/oil interface in highly unsaturated whipped emulsions - Wanjun Han; Yiqiu Deng; Yiting Lin; Farah Zaaboul; Qiuling Huangfu; Yanwen Sun; Xiuhang Chai; Chin-Ping Tan; Yuanfa Liu (Chemical Engineering Journal, 2025)

In-situ polyimidazole-encapsulated Cu-defective PB composite enables green and selective rubidium recovery from salt lake brine - Chi Ma; Zheng Li; Zhongjing Zhang; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Nanocellulose-assisted construction of conductive gradient hydrogel for remote actuated and self-sensing soft actuator - Ya Lu; Shengnan Li; Yuanyuan Ma; Fang Deng; Yiying Yue; Shaohua Jiang; Mingqiang Ye; Yihui Zhou; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2025)

In situ generation of peracetic acid using phosphotungstic acid: A one-pot strategy for selective delignification of corn stover - Xueyan Liang; Zhen Hao; Xiwen Jia; Kaili Ding; Hui Zhang; Aihua Deng; Haitao Yu; Lujia Han; Weihua Xiao (Bioresource Technology, 2025)

Modeling the propagation time from meteorological to root-zone soil moisture drought: a case study in Jiangxi Province, China - Lele Deng; Han Wang; Xinbo Liu; Bowen Zhu (Theoretical and Applied Climatology, 2025)

Neural Tracking of Race-Related Information During Face Perception - Chenyu Pang; Na Zhou; Yiwen Deng; Yue Pu; Shihui Han (Neuroscience Bulletin, 2025)

PACANet: A Paired-Attention central axis aggregation network for plant population point cloud segmentation and phenotypic trait Extraction—A case study on maize - Xin Yang; Teng Miao; Yitong Tao; Bo Zhang; Xiaotong Wu; Xiaodan Han; Jinshi Yu; Yuncheng Zhou; Hanbing Deng; Ying Wang; Tongyu Xu (Computers and Electronics in Agriculture, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Harnessing deep-sea cold seep microbiomes for reductive dehalogenation: from culturomics and genomics insights - Zhaochao Deng; Yeting Xie; Hao Yu; Xiaoyan Zhang; Tianyang Tan; Wenzhen Kuang; Zhiqiang Han; Yanhong Li; Heng Wang; Ning Zhang; Chunfang Zhang (Water Research, 2025)

Mechanisms of Complanatoside A against extracellular matrix accumulation, inflammation and proliferation of mesangial cells in diabetic nephropathy through network pharmacology and experimental validation - Weiyu Han; Zhewen Deng; Jiaqi Li; Beiting Ma; Zhengxin Lu; Yimu Zhang; Chaoxing Ren; Bo Ma (Tissue and Cell, 2025)

Thermal damage evolution of carbon fiber/epoxy composites for hydrogen storage tanks under fire conditions - Pan-Deng Liu; Bei Li; Xin Ma; Bing Han; Guang-Yin Li; Dong-Lei Sun; Chen Song (Process Safety and Environmental Protection, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Reveal the structure of plants by X-ray imaging and biomedical beamline at SSRF - Guohao Du; Jianfeng Ji; Han Guo; Yanling Xue; Yanan Fu; Biao Deng; Honglan Xie; Tiqiao Xiao (Phytochemistry Letters, 2025)

Seasonal dynamics of the carbonate system and acidification sensitivity in a river-dominated coastal system: the Northern Yellow Sea, China - Yawen Wei; Saiya Xu; Xuemei Xu; Xinyi Wang; Xue Deng; Zhentong Yao; Wei Yang; Kunpeng Zang; Hong Chen; Jianbo Han (Marine Environmental Research, 2025)

Potential for hydroxamic acid modification via electronic effect: A case study of enhanced cassiterite flotation - Zhifeng Zhang; Yao Yu; Junhao Fu; Jian Cao; Chaozheng Deng; Wei Sun; Haisheng Han (Minerals Engineering, 2025)

Soil water infiltration under thickening unsaturated zone: patterns, mechanisms, and quantitative formula - Kuan Liu; Jiaqi Zhai; Yong Zhao; Qingming Wang; Hao Wang; Jipeng Cao; Xudong Li; Yuansheng Pei; Leilei Min; Lichuan Wang; Haodong Deng; Xing Li; et al. (Journal of Hydrology, 2025)

Efficient degradation of dichloromethane by novel cell-immobilized-filled biotrickling filters: Performance and mechanisms - Yaxue He; Xiaoyan Li; Rui Han; Aohan Zhang; Ya Deng; Piet N.L. Lens; Christian Kennes; Zhao Huang; Jianmeng Chen; Guangfeng Yang; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Assessment of the PM characteristics and health risk of heavy metals from household solid fuel combustion on a plateau via multiscale particle analysis - Xinyu Han; Haojie Su; Jianwu Shi; Wei Du; Shihan Deng; Yaoqian Zhong; Senlin Tian; Ping Ning (Journal of Hazardous Materials, 2025)

Facile synthesis of α-Fe2O3/ Fe3O4 hybrid adsorbent with tailored affinity sites for high-efficiency microplastics capture - Che Han; Yujie Wang; Jintao Liu; Qiangyi Deng; Hongmei Zhang; Shuang Xu; Conglu Zhang (Journal of Environmental Chemical Engineering, 2025)

Algal-bacterial granular sludge cultured with different inoculum: The discrepancy of granulation mechanism and greenhouse gas emissions - Xiongcheng Deng; Xiaoying Zheng; Zongshuo Han; Jiaqing Tao; Yunqing Li; Tianxing Hu; Yi Fan; Tao Lin (Journal of Environmental Chemical Engineering, 2025)

Direct radiative effects of aerosols and clouds and their impacts on the ecosystem gross primary productivity in summer at typical sites in China - Xiaoqing Deng; Jing Zhang; Wenhao Xue; Tian Han; Yiwen Lang; Yuqing Liu (Environmental Research, 2025)

Bioavailability and resupply dynamics of thallium in agricultural soils affected by lead-zinc mining: In-situ insights from DGT-DIFS modeling - Siwei Deng; Wenhao Wang; Jiang Yu; Yi Wu; Yin Yu; Meng Xu; Lei Han; Peirou Li; Jie Yu; Zhi Huang; Weiwei Zhu; Xin Yang (Environmental Pollution, 2025)

Gene-metabolite correlations underpin the hepatic fibrosis and metabolic disruption induced by methyltestosterone in juvenile Chinese longsnout catfish (Leiocassis longirostris) - Yang Feng; Yongqiang Deng; Zhao Li; Zheng Wei; Zhongmeng Zhao; Han Zhao; Senyue Liu; Lu Zhang; Yuanliang Duan; Zhipeng Huang; Jun Du; Qiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Z-scheme TiO2@CeO2 nanozyme/sonodynamic combination therapy for breast cancer by immunomodulation of tumor microenvironment - Renyu Liu; Wei Wang; Chengcheng Zhang; Liangfang Shen; Rongrong Zhou; A'meng Han; Di Jing; Zijian Zhang; Xianbo Wu; Liu Deng; You-Nian Liu; Xin Zhang (Chemical Engineering Journal, 2025)

Insights into excitonic dynamics in conformational distorted porphyrinic covalent organic frameworks for efficient selective photooxidation - Wang-Kang Han; Jiayu Li; Kang Deng; Jing-Dong Feng; Ruo-Meng Zhu; Ming-De Li; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Photo-induced aggregation of hole-transport material for enhancing photoelectrochemical performance in sensing ochratoxin - Han-Mei Deng; Ning Yang; Jie Xu; Xin-Ci Geng; Ya-Li Yuan; Ruo Yuan; Ya-Qin Chai (Chemical Engineering Journal, 2025)

Self-doped biochar with adsorbed aqueous nitrogen for efficient activation of peroxymonosulfate to degrade sulfamethoxazole - Han Ding; Zhikang Deng; Yongfei Ma; Xiaoyu Xiang; Minghui Xiang; Zulin Zhang (Chemical Engineering Journal, 2025)

Distributional characteristics and causes of single-layer stratiform clouds over typical region in the southeastern Pacific Ocean - Ximing Deng; Yong Han; Chunsong Lu; Xinxin Xie; Yurong Zhang; Tianwei Lu; Li Dong; Qicheng Zhou (Atmospheric Research, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Temporal trends of the disease burden of renal cell carcinoma from 1992 to 2019 in the US: a population-based analysis - Ruyan Chen; Tian Tang; Jianglong Han; Si Li; Wenmin Liu; Haiyu Deng; Tingting Jian; Zhenming Fu (Cancer Causes & Control, 2025)

Research on Ship Type Decision-Making for General Cargo Ship Owners Under Capacity Iteration: A TOPSIS Method Based on Agent Scoring - Wenjun Han; Xianhua Wu; Huai Deng (Journal of Marine Science and Engineering, 2025)
This study quantifies ship-type performance indicators by training intelligent agents to evaluate and score vessels. The Analytic Hierarchy Process (AHP) is then applied to assess the internal consistency of the collected data, ensuring its authenticity and validity. Subsequently, the entropy weight method is employed to objectively determine the significance of each indicator in ship-type decision-making. Finally, COSCO (China COSCO Shipping Corporation Limited) Shipping’s capacity gap reflects the results of the methodology: the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) technique ranks all feasible ship-type combinations, presenting their relative merits through quantitative results. A standardized grading system is further proposed to evaluate these combinations systematically. Ultimately, the 10 most suitable solutions are identified—none achieving the theoretical maximum rating of Grade 10—demonstrating room for improvement in vessel performance.

Corrigendum to “Harnessing deep-sea cold seep microbiomes for reductive dehalogenation: from culturomics and genomics insights” [Water Research, Volume 285 (2025), 124072] - Zhaochao Deng; Yeting Xie; Hao Yu; Xiaoyan Zhang; Tianyang Tan; Wenzhen Kuang; Zhiqiang Han; Yanhong Li; Heng Wang; Ning Zhang; Chunfang Zhang (Water Research, 2025)

Utilization of oxided tamarind polysaccharide gum as novel selective depressant in the flotation separation of copper-lead-zinc sulfide ore - Tichen Wang; Jiushuai Deng; Hao Zhang; Dingquan Xing; Zhiguo Han; Jie Sheng; Chul B. Park (Process Safety and Environmental Protection, 2025)

Multifunctional microbial inoculation regulates compost product microbiomes, with implications for improving crop health and yield - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Xingxiang Deng; Guixian Xie; Gongwen Luo (Journal of Cleaner Production, 2025)

Oxidative modification and structural characterization of konjac gum and its effect on the flotation separation of chalcopyrite from galena - Tichen Wang; Jiushuai Deng; Dingquan Xing; Zhiguo Han; Yue Gao; Qizheng Qin; Hao Zhang; Hongxiang Xu; Chul B. Park (Journal of Cleaner Production, 2025)

Prophage transduction promotes the transmission of phage resistance interfering with adsorption among Chinese foodborne Staphylococcus aureus - Wenyuan Zhou; Yeling Han; Wenjuan Li; Aiping Deng; Yajie Li; Jiaqian Xu; Guoqiang Zhu; Zhenquan Yang (International Journal of Food Microbiology, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plant and its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Corrigendum to “Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one” [FLORA Volume 326, May 2025, 152724] - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Bridge influence surface identification using a physical informed neural network and its application on load transverse localisation - Lu Deng; Dayong Han; Longwei Zhang; Shuo Wang (Engineering Structures, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

Chlorophyll deficient 5 encodes a DNA helicase and is essential for chloroplast development in rice - Weichi Liu; Xiaonan Han; Jiaxin Wei; Jie Yang; Yingchun Wan; Hongxia Yang; Yao Deng; Nan Wang; Ping Feng; Wenqiang Shen (Theoretical and Applied Genetics, 2025)

Enhancement of soil phosphorus mineralization and phosphorus availability by labile carbon in organic amendments through boosting copiotrophic phosphatase-producing bacteria - Yunbin Jiang; Dexu Kuang; Cheng Han; Huan Deng; Kailou Liu; Shangshu Huang; Wei Li; Wenhui Zhong (Plant and Soil, 2025)

Risk factors for severe lower respiratory tract infection among children under 5 years of age hospitalized with respiratory syncytial virus - Yanjun Wang; Yuanxuan Xiang; Ruohong Jin; Bin Li; Xingxing Feng; Qian Han; Xishu Deng; Yunfang Lu; Chengyan Zhang; Shufang Xiao (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

The microbial network exhibits higher complexity in the rhizosphere than in bulk soils along elevational gradients in the alpine forests - Dungang Wang; Shaojun Deng; Han Yang; Na Li; Qiuhong Feng; Jia Liu; Huajun Yin (Applied Soil Ecology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Global, regional and national burden of lung cancer attributable to PM2.5 air pollution: Trends from 1990 to 2021 with projections to 2045 - Yingfan Deng; Zengbin Li; Pan Zhang; Yang Yang; Yuhan Xie; Yutong Cheng; Shuiyan Yu; Guixian Zhu; Lili Han; Lijun Jia; Wentao Xi; Pei Wang; et al. (Journal of Environmental Management, 2025)

Self-assembly of Zein-based nanoparticles for oral isoliquiritigenin delivery against Salmonella infections - Cang Li; Yu Huang; Yuchen Liu; Zhipeng Li; Yao Deng; Hao Ren; Donghao Zhao; Lu Han; Jian Sun (Innovative Food Science & Emerging Technologies, 2025)

Modes of occurrence of rare earth elements and yttrium in bituminous coals with different ranks from the Hedong Coalfield, northern China - Zhenyu Xu; Xiaomei Wang; Fan Deng; Xingxing Guo; Yuxuan Han; Ke Sheng; Yuanhe Mu; Qin Yang (International Journal of Coal Geology, 2025)

Numerical study and optimal design of ECC–NC composite column - Xianzhi Zeng; Haishen Wang; Peng Pan; Kailai Deng; Zhongqi Han; Longfei Rao (Engineering Structures, 2025)

Unveiling how reconstructed molybdenum oxyanions enhances the alkaline oxygen evolution reaction - Yize Wang; Jie Han; Weiwei Bao; Taotao Ai; Junjun Zhang; Zhifeng Deng; Peng Jiang (Chemical Engineering Journal, 2025)

Chondroitin Sulfate A-Selenium Nanoparticles Activate Autophagy Through the AMPK-mTOR Pathway to Alleviate Oxidative Stress and Mitochondrial Dysfunction to Repair Kashin-Beck Disease Chondrocytes - Huan Deng; Lichun Qiao; Yude Jiang; Abebe Feyissa Amhare; Jing Han (Biological Trace Element Research, 2025)

Valorization of marine crustacean shells waste via fermentation technology: A comprehensive review on derived value-added compounds and enhancing their industrial applications - Samad Tavakoli; Qing Li; Wenyu Han; Huijuan Zhang; Ma Hui; Luming Deng; Armin Mirzapour Kouhdasht; Yuqing Tan; Yongkang Luo; Hui Hong; Kefeng Wu (Waste Management, 2025)

The influence of synergistic interaction between raw milk protein and sodium caseinate on the interfacial stability of raw milk-based whipped emulsion - Yiqiu Deng; Wanjun Han; Xiuhang Chai; Yuanfa Liu (Food Hydrocolloids, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

The role of LNK in mitigating hypertension: inhibition of vascular smooth muscle proliferation and JAK-STAT pathway - Xinxin Han; Shuo Wei; Ali Ahmad; Yibo Cao; Caihong Zhao; Mengyang Yan; Jing Zhao; Xingmei Deng; Hongsu He; Zhihua Sun (Molecular and Cellular Biochemistry, 2025)

Multi-factor interaction perspective: machine learning-based analysis of Ni2⁺ adsorption onto soil - Yingdong Wu; Jiang Yu; Zixin Zeng; Zhi Huang; HongBin Jiang; Pu Wang; Siwei Deng; Lei Han; Xinyue Huangpeng; Yinying Jiang; Weiwei Zhu (Environmental Geochemistry and Health, 2025)

Biomarkers Related to Interferon-γ Pathway in Myocardial Ischemia–Reperfusion Injury and the Potential Molecular Mechanisms - Fang Jia; Wei Jiang; Yan Zhang; Lisha Zhang; Tuo Han; Danmeng Liu; Jiahong Xue; Fuxue Deng (Cardiovascular Toxicology, 2025)

Immunoproteomic analyses identify broadly cross-reactive sporozoite immunogens of Eimeria maxima recognized by antisera from chickens infected with E. maxima, E. necatrix, E. tenella or E. acervulina - Haiwei Gong; Haiying Deng; Feng Song; Tao Han; Xiangqin Wang; Shangyu Feng; Weiyi Chen; Liheng Liu (Veterinary Parasitology, 2025)

Nintedanib abrogates patient vitreous-induced Akt activation and tube formation of human retinal microvascular endothelial cells - Qiang Li; Xiaoping Zhou; Yanhui Yang; Qing Zhang; Zhiyuan Li; Haote Han; Fang Yuan; Hongwei Deng; Hetian Lei; Yajian Duan (Tissue and Cell, 2025)

Hydroxyapatite combined with phosphate-solubilizing bacteria immobilized of Cd and inhibited the absorption of Cd by lettuce - Ke Wang; Junqing Zhang; Weilin Li; Zhongyan Deng; Randa S. Makar; Lunguang Yao; Hui Han (Journal of Environmental Chemical Engineering, 2025)

Seasonal variations, ecological risk, and historical trends of antibiotics in the largest shallow wetland lake in northern China - Kai Deng; Lining Zhao; Yan Zhao; Meiyu Li; Jinze Han; Mengyi Wei; Xiaobo Wang; Yulong Zhang; Sijun Dong (Journal of Environmental Chemical Engineering, 2025)

Acid-base in situ reaction enhanced dispersion of copper ferrocyanide on modified polyacrylonitrile membrane for efficient Cs removal - Lijun Meng; Lihan Liu; Senjian Han; Xuan Zhou; Jiayi Luan; Lina Xu; Shiqiang Wang; Tianlong Deng (Journal of Environmental Chemical Engineering, 2025)

Control of sedimentary and diagenetic processes on the reservoir heterogeneity: A case study of the cretaceous carbonate reservoir in an onshore oilfield, Abu Dhabi - Yuting Peng; Yingxiao Fu; Hangyu Liu; Kaibo Shi; Bo Liu; Rubing Han; Xili Deng (Journal of African Earth Sciences, 2025)

Flavor characteristics and metabolomics of sweet rice wine fermented with different non-Saccharomyces yeasts - Yuhang Deng; Hao Zheng; Maosen Zhao; Changwei Cao; Han Kan; Boxiao Wu; Yun Liu (Food Research International, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

Acid-resistant nanofiltration membrane engineered by sulfonated covalent organic framework for lithium recovery from spent lithium-ion batteries leaching solutions - Yuyang Feng; Yifei Zhang; Feng Guo; Lin Wang; Senjian Han; Lina Xu; Shiqiang Wang; Tianlong Deng (Chemical Engineering Journal, 2025)

Evaluating diurnal cloud cycle and its radiative effects from CMIP6 - Xinyi Han; Jing Su; Xingzhu Deng; Nan Peng; Weiqi Lan (Atmospheric Research, 2025)

Nitrogen addition promotes soil organic phosphorus accumulation through increasing microbial biomass phosphorus in a temperate forest - Zhijie Chen; Yutong Xiao; Xiongde Dong; Zihao Deng; Xueya Zhou; Guoyong Yan; Junhui Zhang; Shijie Han (Plant and Soil, 2025)

Stabilization of arsenic by carbon-based iron-lanthanum composite in aged soil - Zixin Zeng; Jiang Yu; Huan He; Siwei Deng; Jie Yu; Yinying Jiang; Yi Wu; Lei Han; Yingdong Wu (Journal of Soils and Sediments, 2025)

The Association Between Environmental Factors and Longevity in Hezhou, China Based on the Drinking Water Quality - Qucheng Deng; Yaqing Liu; Kaixian Zhu; Xuerong Han; Yang Erpeng; Yonghua Li (Exposure and Health, 2025)

Metagenomic insights into the carbon decomposition of plant and microbial biomass in forests across biomes - Xinyu Cha; Shuohong Zhang; Meixuan Wang; Zhenghu Zhou; Jian Deng; Gang He; Fazhu Zhao; Gaihe Yang; Xinhui Han; Chengjie Ren (Soil Ecology Letters, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

Leukemia inhibitory factor supplementation during in vitro maturation enhances bovine oocyte maturation and somatic cloned embryo development - Heqiang Li; Baobao Zhao; Yang Li; Jingya Wang; Tingting Deng; Qi Zhou; Jieyu Wang; Xinrui Lan; Han Zhang; Suzhu Qing; Yong Zhang; Yongsheng Wang (Animal Reproduction Science, 2025)

Genome-wide identification of CYP450 in Ganoderma lucidum and expression analysis of genes related to ganoderic acid synthesis - Xiaolu Li; Dong Liu; Bangxing Han; Shiping Huang; Hui Deng (Archives of Microbiology, 2025)

Effect of Yeast Selenium on Growth Performance, Muscle Selenium Deposition, and Antioxidant Capacity of Juvenile Cherax quadricarinatus - Ying Han; Chenchen Wang; Jimin Deng; Lizhen Zhong; Xiao Huang; Yuandong Sun; Xiaojuan Cui (Fishes, 2025)
This study aimed to investigate the effects of organic selenium-enriched yeast on the growth performance, muscle selenium deposition, and antioxidant capacity of juvenile Cherax quadricarinatus. Five experimental diets supplemented with 0.00 (control), 1.00, 2.00, 3.00, and 4.00 mg/kg of selenium-enriched yeast were fed to crayfish with an average initial body weight of (6.35 ± 1.66) g for 56 days. On days 0, 14, 28, 42, and 56 of the trial, 10 crayfish from each group were randomly sampled for body weight measurement. On day 28, the body weight of the crayfish fed diets containing 1.00, 2.00, 3.00, and 4.00 mg/kg selenium-enriched yeast was significantly higher (p

Bright and efficient green ZnSeTe-based quantum-dot light-emitting diodes with EQE exceeding 20% - Xiangzhen Deng; Qiaoling Zhao; Han Zhang; Fengjuan Zhang; Huaibin Shen (Science Bulletin, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Overexpression of SlIMP3 regulates sugar metabolism, antioxidant activity, and fruit softening, leading to extended shelf life of tomato fruits - Qiqi Yang; Xianzhe Zheng; Xu Fang; Qiongdan Zhang; Jie Deng; Jiarui Han; Chan Xu; Qiaoli Xie; Wei Deng (Postharvest Biology and Technology, 2025)

Two E-clade protein phosphatase 2Cs enhance ABA signaling by dephosphorylating ABI1 in Arabidopsis - Ya Zhang; Liyuan Han; Junjie Liu; Miao Chang; Chuanling Li; Jian-Xiu Shang; Zhiping Deng; Wenqiang Tang; Yu Sun (Molecular Plant, 2025)

Removal of tetracycline in aqueous solution by metastable aluminum cluster ions - Hai-Yang Jiang; Xiao-Han Guo; Gen-Wang Ma; Wei-Zhuo Gai; Yang Yang; Jie Zhang; Zhen-Yan Deng (Journal of Water Process Engineering, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

NiVFe-LDH nanosheets reinforced MoS2 heterogeneous interface design for glycol-assisted water electrolysis - Suzhao Yang; Jie Han; Weiwei Bao; Taotao Ai; Xueling Wei; Peng Jiang; Zhifeng Deng; Junjun Zhang (Fuel, 2025)

Metabolomics and sensory evaluation reveal the influence of four albino tea cultivars on the quality of processed green tea - Yifan Li; Zhen Han; Miao Wang; Yaxing Yan; Ruihong Ma; Hongping Wang; Wei-Wei Deng (Food Research International, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Rapid and interference-resistant colorimetric detection of viable Staphylococcus aureus in food using a broad host range phage SapYZU04 and MnFeO nanozyme - Aiping Deng; Xuan Li; Xiaoxing Fan; Yajie Li; Yelin Han; Tianzhu Guan; Shuo Wang; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Food Control, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Chiral nanostructured Pd films for efficient electrocatalytic reduction of nitrite to ammonia - Hao Chen; Quanzheng Deng; Tianwei Ouyang; Wanning Zhang; Bin Liu; Lu Han; Shunai Che; Yuxi Fang (Chemical Engineering Journal, 2025)

Uncertainty analysis of two-level heating demand in pastoral areas of eastern Qinghai-Tibet Plateau based on field investigation and numerical simulation - Jinwei Li; Rongjiang Ma; Mengsi Deng; Xiaoling Cao; Xianfeng Liu; Pengxin Zhang; Changyue Hu; Xinke Luo; Yuanwei Han; Ke Zhang; Yitong Luo; Zongyan Li; et al. (Building and Environment, 2025)

Thermoacoustoelasticity for Elastic Wave Propagation in Preheated and Prestressed Solid Rocks - Jian Yang; Li-Yun Fu; Tongcheng Han; Wubing Deng; Bo-Ye Fu (Rock Mechanics and Rock Engineering, 2025)

Functional analysis of the woody oil crop Plukenetia volubilis L. LEC2 homolog PvoB3-69 in promoting regeneration - Jing-jing Yu; Shiling Deng; Jinhui Mo; Han Huang; Zeng-Fu Xu; Yi Wang (Plant Cell Reports, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Performance of cut-off walls under long-term vacuum suction: A case study - Chenchen Xu; Yongtao Hu; Shijie Han; Geng Xueyu; Da Cheng; Ning He; Yongfeng Deng (Marine Georesources & Geotechnology, 2025)

Deciphering the temporal and dose-responsive dynamics of microbial communities in aquaculture mesocosms under florfenicol treatment - Xiaoxi Deng; Chengqian Liang; Yu Wang; Yanni Geng; Jian Han; Ke Yu (Aquaculture, 2025)

YAP1 regulates endometrial receptivity by promoting the plasma membrane transformation and proliferation of bovine endometrial epithelial cells - Han Zhou; Jinxin Zhang; Wen Feng; Nuoer Chen; Talha Umar; Xinyu Feng; Wenjing Liu; Changwei Qiu; Ganzhen Deng (Theriogenology, 2025)

Exogenous NaHS maintains storage quality of Prunus salicina ‘Wushan plum’ by regulating the antioxidant system, endogenous H2S, ethylene and NO metabolism - Saiying Han; Ling Liu; Lilei Wang; Jin Han; Yeru Ai; Huali Wang; Kaifang Zeng; Jian Ming; Lili Deng (Postharvest Biology and Technology, 2025)

Dynamic analysis and optimization of perforated tubing strings in deep-water wells under diverse operating conditions - Qiao Deng; Jiadong Jiang; Dong Yang; Hu Han; Guilin Qi (Ocean Engineering, 2025)

Assessing environmental impacts and carbon emissions of promising electrochemical and traditional methods of COD detection - Yanhe Han; Chun Li; Jialin Wang; Lina Liu; Xuejiao Ma; Yifan Deng (Journal of Water Process Engineering, 2025)

Dynamic response of vegetation to meteorological drought and driving mechanisms in Mongolian Plateau - Shenghang Gao; Shengzhi Huang; Vijay P. Singh; Xiaoya Deng; Limin Duan; Guoyong Leng; Wenwen Guo; Yifei Li; Lin Zhang; Zhiming Han; Qiang Huang (Journal of Hydrology, 2025)

A method for influencing residential land population density by industrial development considering global and local scales: A case study of Wuzhong city, China - Yunxiao Gao; Ruimin Yin; Ying Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Duality of supercritical water pressure on phenol gasification studied by metadynamics simulation and experimental - Deng Zhao; Xuetong Li; Wei Luo; Qingxin Li; Wenming Han; Huashan Wang; Hua Liu; Hui Liu; Shuai Guo; Jiajing Kou (Fuel, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Black carbon in major global source areas from 2000 to 2023: Spatiotemporal variation, vertical distribution, and extreme case analysis - Yurong Zhang; Yong Han; Yan Liu; Ximing Deng; Tianwei Lu; Qicheng Zhou; Li Dong (Environmental Pollution, 2025)

An alternative ignition agent concept based on ionic integrated energetic oxidant - Xiaoxia Li; Peng Ren; Rui Wu; Yu Wang; Peng Deng; Kehua Han; Yu Shang; Shaoli Chen; Weixiong Zhang (Chemical Engineering Journal, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

Evaluating the Impact of an Organic Trace Mineral mix on the Redox Homeostasis, Immunity, and Performance of Sows and their Offspring - Shao-Qing Wang; Zhe Peng; Hua Sun; Yan-Ming Han; Bo Zhang; Lane Pineda; Gavin Boerboom; Lv-hui Sun; Ying Liu; Zhang-Chao Deng (Biological Trace Element Research, 2025)

Mixed eucalyptus plantations in southern subtropical China effectively stabilized the rhizosphere-associated bacterial network and facilitated soil ecological function - Yahui Lan; Han Zhang; Yaqin He; Chenyang Jiang; Jiazhen Deng; Shaoming Ye (Applied Soil Ecology, 2025)

Nature–based nutrient management through returning agricultural organic waste enhances soil aggregate organic carbon stability - Yini Wang; Yanzhong Yao; Bingbing Han; Simon Willcock; Jonathan Storkey; Xunzhuo Dong; Yunyao Zhong; Xiaozhong Wang; Yan Deng; Wei Zhang; Qirui Li; Xinping Chen; et al. (Agriculture, Ecosystems & Environment, 2025)

Targets and Potential Mechanism of Chondroitin Sulfate A-selenium Nanoparticle on Kashin-Beck Disease Chondrocytes - Huan Deng; Feidan Deng; Xinyue Wen; Yude Jiang; Abebe Feyissa Amhare; Lichun Qiao; Miaoqian Li; Ping Wan; Jun Wang; Jing Han (Biological Trace Element Research, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Groundwater storage anomalies projection by optimized deep learning refines groundwater management in typical arid basins - Xiaoya Deng; Guangyan Wang; Feifei Han; Yanming Gong; Xingming Hao; Guangpeng Zhang; Pei Zhang; Qianjuan Shan (Journal of Hydrology, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Optimization strategies for the carbon footprint of aluminum-plastic materials under low-carbon targets - Jingqi Deng; Tingting Hu; Mengqi Han; Yan Liu; Yusen Duan; Dungang Gu; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2025)

Integrated analysis of circular economy policy innovations in developing countries through experts' perspectives - Deng Yaotian; Zheng Han; Ravi Shankar Yadav (Journal of Environmental Management, 2025)

Drivers of civil aviation emissions in China: Considering spatial heterogeneity and interdependence - Simeng Ma; Wenhui Zheng; Bo Han; Zhiqiang Deng; Jinglei Yu; Jingbo Zhao; Chen Zhang; Jian Yu; Philip K. Hopke (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Elucidation of the fine structure and anti–breast tumor activity of a glucomannan from the pseudobulbs of Pleione bulbocodioides - Wan-Qi Deng; Shao-Wei Han; Si-Yuan Shao; Shuai Li (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Biological activities of benzofurans from the fruits of Psoralea corylifolia L. and their mechanism based on network pharmacology and biological verification - Peixin Shi; Xiaohui Yu; Min Zhang; Lin Wang; Linkui Deng; Jun Yin; Na Han (Phytochemistry, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Study on a potential bone char catalyst for high efficiency catalytic pyrolysis of polypropylene plastic - Jiale Liu; Yuyu Li; Wenbei Deng; Yongyang Wu; Dongjiao Chen; Xuesong Zhang; Xian Liu; Lujia Han (Fuel, 2025)

In-depth understanding the pyrolysis behavior of arginine: Combined experiments, ReaxFF molecular dynamics and DFT calculation study - Ziqi Wang; Jun Shen; Xuesong Liu; Sha Wang; Shengxiang Deng; Zhenqing Han; Hai Zhang; Yun Guo (Fuel, 2025)

Designing organic structure-directing agent for cost-effective production of multipore MSE zeolite - Zheru Shi; Lei Wang; Quanzheng Deng; Lu Han; Chaowei Liu; Tao Liu; Chenxin Gong; Wei Deng; Jichang Liu; Yi-An Zhu; Xiaoyun Xiong; Kake Zhu (Fuel, 2025)

Biogenic amines degradation ability of Saccharomyces cerevisiae I45 and Pichia sp. NW5 & LB60 and their application in beer fermentation - Kexin Hong; Chenyu Li; Jingya Ai; Xiaoyu Han; Bing Han; Qiuxing Qin; Huan Deng; Tianyang Wu; Xiaoxuan Zhao; Weidong Huang; Jicheng Zhan; Yilin You (Food Research International, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Caffeic acid enhances the postharvest quality by maintaining the nutritional features and improving the aroma volatiles for nectarine fruit - Jingxuan Lu; Han Wang; Yiqin Zhang; Hongxuan Wang; Lizhi Deng; Luyao Chen; Jiankang Cao; Baogang Wang; Weibo Jiang (Food Chemistry, 2025)

Antibacterial mechanism of atmospheric cold plasma against Pseudomonas fluorescens and Pseudomonas putida and its preservation application on in-packaged red shrimp paste - Jiajie Hu; Yao Zhang; Weicong Pan; Qianyun Han; Yu Wei; Yuwei Li; Yi Hu; Xiaoguo Ying; Andrea Armani; Alessandra Guidi; Shanggui Deng (Food Chemistry, 2025)

Long-term exposure to low-concentration sulfur dioxide and mental disorders in middle-aged and older urban adults - Shenghao Yuan; Yujia Bao; Yongxuan Li; Qingqing Ran; Yanqiu Zhou; Yaqing Xu; Xiaoxi Zhang; Lefei Han; Shi Zhao; Yuzheng Zhang; Xiaobei Deng; Jinjun Ran (Environmental Pollution, 2025)

Optimization scheduling of household integrated energy systems for improving thermal comfort with low cost - Yunlong Wang; Lu Han; Xinlong Deng; Hongjun Gao (Energy and Buildings, 2025)

Integrating karst bare rock index (KBRI) into the CASA model to improve grassland aboveground biomass estimation in karst area, Southwest China - Yanyun Deng; Zhen Han; Wanyang Yu; Jinxin Zhang; Rui Hou; Longshan Zhao (Ecological Modelling, 2025)

N-doped biochar supported Ni-Co alloy catalyst for efficient hydrocracking of enzymatic hydrolysis lignin to monophenols in water - Zifan Wu; Yacong Deng; Fengyu Tian; Yidi Wang; Na Fan; Guangzheng Sun; Yichuan Li; Yuan Pan; Bin Liu; Bin Dong; Han Hu; Yongming Chai (Chemical Engineering Journal, 2025)

Emerging mechanistic insights into liposomal stability: Full process management from production and storage to food application - Xiankang Xu; Fang Tian; Yujie Pan; Tingting Zhang; Leiyu Deng; Hanyun Jiang; Jianzhong Han; Jianhua Liu; Yanrong Zhao; Weilin Liu (Chemical Engineering Journal, 2025)

Comparative chloroplast genomic analysis of an important horticultural plant, Dendrobium sulcatum (Orchidaceae) and phylogenetic position in Dendrobium - Feng-Ping Zhang; Jia-Jun Deng; Ying Guo; Li-Jun Han; Zi-Li Yin (Horticulture, Environment, and Biotechnology, 2025)

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Pilot-scale experimental study on the enhanced natural attenuation of complex organic contaminants based on the recharge of electron acceptors - Shuxuan Wu; Yu Yang; Xu Han; Sheng Deng; Jiayu Kang; Beidou Xi; Yonghai Jiang (Water Research, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Comammox rather than AOB dominated the efficient autotrophic nitrification-denitrification process in an extremely oxygen-limited environment - Yu Xiang; Xiaoming Song; Yilin Yang; Shuai Deng; Liwei Fu; Cheng Yang; Mengli Chen; Jia Pu; Han Zhang; Hongxiang Chai (Water Research, 2025)

Dynamic analysis and experimental testing of a multi-tagline anti-sway and positioning system for slender-beam payload lifting during offshore operations - Maokai Sun; Wanru Deng; Zewen Sun; Guangdong Han; Shenghai Wang; Hongpeng Zhang; Yi Wei; Yuqing Sun; Zhiming Yuan (Ocean Engineering, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Intelligent carrageenan-based composite films containing color indicator-loaded nanoparticles for monitoring fish freshness - Yahong Han; Mingrui Zhou; Jiajie Deng; Cheng Cheng; Zihan Xu; Wenfu Hou; Yang Yi; David Julian McClements; Shuai Chen (Food Packaging and Shelf Life, 2025)

A ready-to-use RNA delivery platform modulated by metal ions - Zhaojian Qin; Yongzhuo Jiang; Peng Tao; Haifeng Liu; Han Zhong; Xiaoyi Ding; Runze Zhao; Yi Lu; Lifeng Zhang; Xiaomin Chen; Hongxin Zhuang; Jiao Wu; et al. (Chemical Engineering Journal, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

The modelling of a multi-tubular packed-bed reactor for ammonia cracking and SOFC waste heat utilization - Bin Miao; Zhihua Deng; Peijie Han; Ning Yan; Zehua Pan; Siew Hwa Chan (Chemical Engineering Journal, 2025)

Dynamic transport of Zn2+ in ionic liquid intercalated V2O5 cathode for high-performance aqueous Zn-ion batteries - Wenzhe Su; Zanyu Chen; Xingkai Wang; Peng Cui; Minjie Yao; Hui Sun; Hong Zhang; Yida Deng; Xiaopeng Han; Wenbin Hu (Chemical Engineering Journal, 2025)

Gradient wood-derived hydrogel actuators constructed by an isotropic-anisotropic structure strategy with rapid thermal-response, high strength and programmable deformation - Ya Lu; Yuanyuan Ma; Fang Deng; Yiying Yue; Shaohua Jiang; Qinglin Wu; Huining Xiao; Jingquan Han (Chemical Engineering Journal, 2025)

Wellbore Strengthening for Addressing Lost Circulation in Fractured Formations: A Comprehensive Review - Jinfa Zhang; Yongcun Feng; Bing He; Han Hu; Jingen Deng (Rock Mechanics and Rock Engineering, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Cadmium Exposure was Associated with Sex-Specific Thyroid Dysfunction: Consistent Evidence from Two Independent Cross-Sectional Studies Based on Urinary and Blood Cadmium Measurements - Ranqi Shao; Liqin Su; Peng Wang; Xu Han; Ting Wang; Jun Dai; Yi Gu; Jiao Luo; Lifang Deng; Jingping Liu (Biological Trace Element Research, 2025)

Predictive Control for Steel Rib Bending Based on Deep Learning - Yijiang Xia; Jinhui Luo; Zhuolin Ou; Xin Han; Junlin Deng; Ning Wu (Journal of Marine Science and Engineering, 2024)
In the shipbuilding industry, the inefficiency of the successive approximation control method in CNC cold-bending machines has hindered productivity in steel bending manufacturing, particularly for rib profiles. This study proposes control methods for cold bending machines based on deep learning models to address this challenge, including CNN and Transformer-CNN (T-CNN), to predict the elastic spring-back rate of cold-processed metal profiles and generate precise control pulses for achieving target bending angles. Experimental validation using real-world datasets collected from a shipyard’s CNC cold bending machine demonstrates that the T-CNN model significantly reduces the number of steps required for each bending operation, achieving a 75% reduction in production time and substantially enhancing processing efficiency. By leveraging the strengths of CNNs and Transformer architectures, the T-CNN model excels at handling long sequence data and capturing global dataset characteristics. Results show that the T-CNN model outperforms traditional control methods and standard CNNs in prediction accuracy, stability, and efficiency, making it a superior choice for cold bending control.

Adaptive mechanisms to hypoxia and hyperoxia in juvenile turbot, Scophthalmus maximus - Yi Chen; Yuntian Zhang; Rongwei Zhang; Hongsheng Deng; Xiangyu Meng; Kotoya Inaba; Tatsu Osato; Xiaoran Zhao; Yuzhe Han; Tongjun Ren (Frontiers in Marine Science, 2024)
In recirculating aquaculture systems (RAS), the impact of dissolved oxygen (DO) fluctuations on turbot is still not fully understood. This study investigated these impacts by selecting 135 turbot (average dry weight: 6.0 ± 0.5 g) and exposing them to three DO levels: hypoxia (4.0 ± 0.5 mg/L), normoxia (7.5 ± 0.5 mg/L), and hyperoxia (23.5 ± 0.5 mg/L). These groups were labeled as LF (low oxygen), NF (normal oxygen), and HF (high oxygen). The study aimed to explore the adaptive mechanisms of turbot under hypoxic and hyperoxic conditions, using microbiome, transcriptome, and hematological analyses over a 40-day period. The results suggest that hyperoxia significantly enhances turbot growth without compromising the composition of intestinal microbiome, whereas hypoxia markedly impairs growth and induces alterations in intestinal microbiome. Transcriptomic analysis revealed various pathways implicated in adaptation to both hypoxic and hyperoxic conditions, encompassing amino acid metabolism, protein metabolism, lipid metabolism, carbohydrate metabolism, the PPAR signaling pathway, etc. However, pathway changes are not completely consistent. For instance, pancreatic secretion is crucial for hyperoxia adaptation, while the HIF1α pathway plays a key role in hypoxia adaptation and tissue repair. Furthermore, genes ATP6 , HIF1 , HSP90 , and CYP450 exhibited high expression levels during hypoxia, whereas Hbae5 and Man-SL showed elevated expression during hyperoxia. In hematological indicators, there are ways to help adapt to hypoxia and hyperoxia, including increased red blood cell (RBC) and hemoglobin (HGB) counts; gas and ion balance; elevated blood urea nitrogen (BUN) and malondialdehyde (MDA); increased polyphenol oxidase (PPO) and lysozyme (LZM) activity. Although turbot have adaptive mechanisms to both hypoxia and hyperoxia, extended exposure to hypoxia detrimentally affects growth, whereas hyperoxia facilitates it. These findings provide significant insights into the adaptive mechanisms of turbot in response to fluctuating DO levels.

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

Self-correcting deep learning for estimating rice leaf nitrogen concentration with mobile phone images - Jinmin Li; Liangsheng Shi; Xiaohu Mo; Xiaolong Hu; Chenye Su; Jingye Han; Xianzhi Deng; Shuai Du; Shenji Li (Computers and Electronics in Agriculture, 2024)

Study on the field monitoring, assessment and influence factors of pipe friction resistance in rock - Zhiyun Deng; Xinrong Liu; Yafeng Han; Peng Ding; Bin Xu; Weisheng Du (Tunnelling and Underground Space Technology, 2024)

Degradation of sulfamethoxazole in a falling film dielectric barrier discharge system: Performance, mechanism and toxicity evaluation - Han Zhang; Siyu Deng; Luxiang Zhu; Yanan Liu (Science of The Total Environment, 2024)

Organic manure rather than chemical fertilization improved dark CO2 fixation by regulating associated microbial functional traits in upland red soils - Qian Wang; Mengmeng Liu; Jingshi Huang; Cheng Han; Yunbin Jiang; Huan Deng; Kailou Liu; Wenhui Zhong (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Surface carbonate dynamics in a temperate coastal system in the Northern Yellow Sea, China - Yawen Wei; Wei Yang; Xue Deng; Taikun Jin; Fuxu Cui; Kuishuang Shao; Zongcai He; Hong Chen; Jianbo Han; Xuemei Xu (Regional Studies in Marine Science, 2024)

Study on cooling efficiency and mechanism of lithium-ion battery thermal runaway inhibition by additives enhanced water mist based on boiling heat transfer theory - Xiangming Hu; Zhiyuan Yang; Yurui Deng; Ming Li; Qingsong Wang; Hongbin Wei; Xiaoxuan Wei; Guoyu Han (Process Safety and Environmental Protection, 2024)

Transcription factor CcbHLH66 regulates mandarin fruit coloration via modulating the expression of chlorophyll degradation related genes CcRCCR and CcNYC - Huali Wang; Qian Liu; Shufang Deng; Jialin Chen; Jin Han; Rong Zhu; Kaifang Zeng; Lili Deng (Postharvest Biology and Technology, 2024)

VvRF2b interacts with VvTOR and influences VvTOR-regulated sugar metabolism in grape - Shuang Xia; Ying Zhao; Qiaoyun Deng; Xiaoyu Han; Xiuqin Wang (Plant Science, 2024)

Overexpression of GmSRC2 confers resistance to Phytophthora sojae in soybean - Sushuang Deng; Yu Zhang; Xiaowan Fang; Han Gou; Ruidong Sun; Huidong Xuan; Haitang Wang; Jinming Zhao; Han Xing; Na Guo (Plant Science, 2024)

Identification and characterization of ATP-binding cassette transporters involved in chlorantraniliprole tolerance of model insect Drosophila melanogaster and agricultural pest Spodoptera frugiperda - Lixiang Wang; Bin Wen; Shaoyi Guo; Yujie Han; Zhongyuan Deng; Qian Ding; Xianchun Li (Pesticide Biochemistry and Physiology, 2024)

Innovative multi-tagline anti-swing and positioning system: Dynamic analysis and experimental validation for slender-beam payloads in offshore environments - Maokai Sun; Shenghai Wang; Wanru Deng; Binteng Gu; Guangdong Han; Zhiming Yuan; Haiquan Chen; Yuqing Sun (Ocean Engineering, 2024)

Early–Middle Jurassic magmatism, stratigraphy, and deformation in North and Northeast China: A prelude to the thinning of the North China Craton and subducted Izanagi Plate, and a Coda to the Mongol-Okhotsk Ocean - Zongyuan Tang; Chenchang Chen; Guochun Zhao; Deyou Sun; Jie Li; Changzhou Deng; Han Zheng (Lithos, 2024)

Sponge-based FeS activated persulfate coupled with biodegradation for highly efficient removal of tetracycline: Batch and column validation - Shou Mei; Mengyao Han; Jintao Hao; Yuxuan Ye; Yuwei Deng; Luxin Liang; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Zhenbin Wu; Fei Pan (Journal of Water Process Engineering, 2024)

Design and optimization of an integrated UF-NF membrane process for treating rare earth refining wastewater - Yiwen Wang; Shuanglin Gui; Qinliang Jiang; Pei Han; Hong Wang; Jianping Deng; Tao Chen; Jianxin Li (Journal of Water Process Engineering, 2024)

Soil phosphorus compared to nitrogen limitation increases the uncertainty of subsoil organic carbon sequestration in Pinus massoniana mixed forests - Fenghua Tang; Yunchao Zhou; Piaoyun Deng; Jirong Feng; Yuexiong Mao; Yaoxiong Wang; Qianbin Cao; Zhengui Han; Lulu Meng; Yunxing Bai (Journal of Environmental Management, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Effect of Cd2+ and Cu2+ on Desulfovibrio vulgaris strain ATCC 7757: Insights from sulfur isotope fractionation - Qinglin Zhuang; Chuling Guo; Siyu Zhang; Meihui Ren; Yanping Deng; Chaoping Wang; Han Ye; Zhi Dang (Journal of Environmental Chemical Engineering, 2024)

Variations in volatile components and biological activities of essential oils from Citrus aurantium ‘changshanhuyou’ at different growth and ripening stages - Han Wang; Xinyue Zhou; Yong Deng; Ruyu Zhang; Kai Fu; Jiabao Huang; Qiong Huang; Cheng Zeng; Donghong Liu; Wenjun Wang (Food Research International, 2024)

Double-network conductive hydrogel for non-contact respiratory monitoring - Shuhang Deng; Xiaoran Ming; Guilong Yan; Li Wang; Zhenyu Li; Jingyu Chen; Jingjuan Lai; Dong Li; Dong Xiang; Chunxia Zhao; Hui Li; Xuezhong Zhang; et al. (Chemical Engineering Journal, 2024)

Thermal stability of PVDF-HFP based gel electrolyte for high performance and safe lithium metal batteries - Xiaoxuan Wei; Yurui Deng; Xiangming Hu; Zhiyuan Yang; Guoyu Han; Hengxu Xu; Zhijun Zhang (Chemical Engineering Journal, 2024)

Chemical characteristics, sources, and formation mechanisms of PM2.5 before, during, and after the Spring Festival in a plateau city of Southwest China - Jianwu Shi; Li Deng; Wei Du; Xinyu Han; Yaoqian Zhong; Wenjun Rao; Haitao Xie; Feng Xiang; Ping Ning; Senlin Tian (Atmospheric Environment, 2024)

Ocean acidification aggravates the toxicity of deltamethrin in Haliotis discus hannai: Insights from immune response, histopathology and physiological responses - Xiaojing Lv; Qinyou Deng; Lizhu Chen; Xin Wang; Yijing Han; Guiqing Wu; Yongliang Liu; Haiyue Sun; Xuan Li; Jinxia He; Xiangquan Liu; Dinglong Yang; et al. (Aquatic Toxicology, 2024)

Positive cooperativity in synergistic activation of Wnt proteins - Clemence Bonnet; Christiana S. Han; Sophie X. Deng; Jie J. Zheng (Molecular Biology Reports, 2024)
Background Wnt proteins are crucial for embryonic development, stem cell growth, and tissue regeneration. Wnt signaling pathway is activated when Wnt proteins bind to cell membrane receptors. Methods and results We employed a luciferase reporter assay in HEK293STF cells to measure Wnt protein-induced signaling. We observed that Wnt3a uniquely promotes the Wnt/β-catenin pathway through positive cooperativity. Additionally, MFH-ND, a molecular mimic of Wnt ligands, markedly increased Wnt3a-induced signaling in a dose-responsive manner. This suggests that various Wnt ligands can synergistically enhance Wnt pathway activation. Conclusions The study suggests the likelihood of various Wnt ligands coexisting in a single signalosome on the cell membrane, providing new insights into the complexities of Wnt signaling mechanisms.

Erratum to: Identification of Saline Soybean Varieties Based On Trinocular Vision Fusion and Deep Learning - Hang Liu; Qiong Wu; Guangxia Wu; Dan Zhu; Limiao Deng; Xiaoyang Liu; Zhongzhi Han; Longgang Zhao (Journal of Crop Health, 2024)

Identification of Saline Soybean Varieties Based On Trinocular Vision Fusion and Deep Learning - Hang Liu; Qiong Wu; Guangxia Wu; Dan Zhu; Limiao Deng; Xiaoyang Liu; Zhongzhi Han; Longgang Zhao (Journal of Crop Health, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Geology and S-Pb isotope geochemistry of the Hatu gold deposit in West Junggar, NW China: Insights into ore genesis and metal source - Shen Han; Zhenju Zhou; Xiaohua Deng; Yanshuang Wu; Xi Chen; Abulimiti Aibai; Yong Wang; Xiaoyu Jia; Yanjing Chen (Acta Geochimica, 2024)

High-Resolution 3D Geological Modeling of Three-Phase Zone Coexisting Hydrate, Gas, and Brine - Han Yu; Ju Wang; Wei Deng; Zenggui Kuang; Tingwei Li; Zhangshu Lei (Journal of Marine Science and Engineering, 2024)
Three-dimensional geological modeling is essential for simulating natural gas hydrate (NGH) productivity and formulating development strategies. Current approaches primarily concentrate on the single-phase modeling of either hydrate or free gas layers. However, an increasing number of instances suggest that the three-phase coexistence zone, which includes hydrate, gas, and water, is common and has become a focal point of international research, as this type of reservoir may present the most viable opportunities for exploitation. At present, there exists a significant gap in the research regarding modeling techniques for such reservoirs. This study undertakes a comprehensive modeling investigation of the three-phase zone reservoir situated in the sand layer of the Qiongdongnan Basin. By employing deterministic complex geological modeling techniques and integrating existing seismic and logging data, we have developed a three-phase coexistence zone model that precisely characterizes the interactions between geological structures and utilizes them as auxiliary constraints. This approach effectively mitigates the potential impact of complex geological conditions on model accuracy. Through a comprehensive analysis of 105 seismic profiles, we enhanced the model’s accuracy, resulting in the creation of a three-phase coexistence zone model comprising 350,000 grids. A comparison between the modeling results and well data indicates a relatively small error margin, offering valuable insights for future development efforts. Furthermore, this method serves as a reference for modeling hydrates in marine environments characterized by three-phase coexistence on a global scale.

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

Development of specific molecular markers for medicinal peony (Paeonia lactiflora) with double flower - Jinqiu Liao; Shuai Zhang; Qunqun Yang; Zhenge Han; Xuexue Deng; Ruiwu Yang; Yuanyuan Jiang; Li Zhang (Journal of Genetics, 2024)

Evaluation of urban underground space via automated constraint identification and hybrid analysis - Fei Deng; Tianxiao Cheng; Yu Huang; Zhiyi Chen; Qingding Han (Tunnelling and Underground Space Technology, 2024)

Identifying groundwater ammonium hotspots in riverside aquifer of Central Yangtze River Basin - Shuai Shen; Jingwei Zhang; Yao Du; Teng Ma; Yamin Deng; Zhihui Han (Science of The Total Environment, 2024)

Long-term evolution of soil quality in citrus orchard terrace system: A whole life cycle perspective - Han Zheng; Yaojun Liu; Ziqing Deng; Haiqun Yuan; Jiale Ye; Zilv Chen; Peiyao Xiao; Taoxi Li; Jian Duan; Jie Zhang; Zhongwu Li (Science of The Total Environment, 2024)

Numerical analysis of propeller cavitation and pressure fluctuations around the INSEAN E779A propeller in a non-uniform wake - Chengzao Han; Yun Long; Linfeng Deng; Bin Ji; Xinping Long (Ocean Engineering, 2024)

Climate change contributed to the disappearance of the latest Cretaceous dinosaurs in the Shanyang Basin, Central China - Fei Han; Yuqi Han; Xinying Zhou; Huapei Wang; Huafeng Qin; Qiang Wang; Chenglong Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Visible-light-sensitive microrobots using H2O as fuel for highly efficient capture and precise detection of nanoplastics - Zhiqin Geng; Tangtang Deng; Bohan Gu; Xinting Qian; Rui Li; Linfen Duan; Junyang Li; Weiqing Han; Lulu Qu; Kajia Wei (Journal of Hazardous Materials, 2024)

Impacts of shifting from single-species pine forests to distinct agroforestry models on soil fertility, exchangeable cations, and microbial functions - Saif Ullah; Xiaomei Han; Rongyan Deng; Izhar Ali; Wannian Li; Yuanyuan Xu; Mei Yang (Journal of Environmental Management, 2024)

Chemometrics and sensomics-assisted identification of key odorants responsible for retort odor in shelf-stored green tea infusion: A case study of Biluochun - Jie-Qiong Wang; Ying Gao; Zhi-Hui Feng; Si-Han Deng; Jian-Xin Chen; Fang Wang; Yi-Fan Li; Ying-Bin Zhang; Jun-Feng Yin; Liang Zeng; Wei-Biao Zhou; Yong-Quan Xu (Food Research International, 2024)

Characterization, in vitro elderly digestion, and organoids cell uptake of curcumin-loaded nanoparticles - Leiyu Deng; Ruijie Wang; Xiankang Xu; Hanyun Jiang; Jianzhong Han; Weilin Liu (Food Chemistry, 2024)

Characterisation of a colourimetric biosensor SapYZUM13@Mn3O4-NH2 reveals the mechanisms underlying its rapid and sensitive detection of viable Staphylococcus aureus in food - Yeling Han; Wenyuan Zhou; Yuhong Wu; Aiping Deng; Lei Yuan; Yajun Gao; Huaxiang Li; Zhirong Wang; Bo Wang; Guoqiang Zhu; Zhenquan Yang (Food Chemistry, 2024)

Constraining the evaporative loss of zinc during impact processes using terrestrial impact glasses - Zheng-Yu Long; Frédéric Moynier; Marine Paquet; James M.D. Day; Linru Fang; Tu-Han Luu; Dimitri Rigoussen; Kun-Feng Qiu; Jun Deng; Christian Koeberl (Earth and Planetary Science Letters, 2024)

Exploring the mechanism of alkali metal K-catalyzed biomass char gasification using in-situ DRIFTS and molecular simulation - Deng Zhao; Yu Wang; Guanwei Wang; Wenming Han; Hua Liu; Huashan Wang; Hui Liu; Shuai Guo (Chemical Engineering Journal, 2024)

Synergistic electronic regulation and piezocatalytic effect in CoTiO3-BaTiO3 heterojunction for boosting fenton-like oxidation toward pollutants degradation - Jiahao Wei; Xinyue Sun; Fan Li; Ziwen Deng; Dandan Han; Junbo Gong (Chemical Engineering Journal, 2024)

Regulation of N Zn O bonds via carbonized polymer dots in polyaniline composite cathode for high performance stable aqueous Zn-ion batteries - Bao-Hong Xu; Yi-Han Song; Guo-Duo Yang; Jia-Yu Zhang; Yu-Qi Liu; Jie-Qiong Liu; Qi-Meng Zhang; Xing-Long Wu; Ming-Xiao Deng; Hai-Zhu Sun (Chemical Engineering Journal, 2024)

Metabolic engineering of Escherichia coli for de novo production of 5-hydroxyvalerate via L-lysine α-oxidase pathway - Guodong Wang; Yuanwei Wang; Yingshuai Wu; Shitong Dong; Han Zhao; Hongyu Deng; Yonghua Chen; Wenzhu Song; Ruiming Wang; Chunling Ma (Bioresource Technology, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Pseudomonas syringae pv. coronafaciens, causing a new bacterial halo blight disease on oat (Avena sativa L.) in China - Jianjun Wang; Ruochen Zhang; Hongshan Deng; Xueqin Han; Xuekai Wei; Malik Kamran; James F. White; Guiqin Zhao; Chunjie Li (European Journal of Plant Pathology, 2024)

Photoelectron-transfer-effect grafting: Validation of a generalized strategy for fluorescence and photoelectrochemical dual-mode detection of hydrogen sulfide - Xiao-Jie Yu; Xiao-Yan Wan; Yu-Ting Shen; Deng-Bao Zhang; Xian-Jing Zhou; De-Man Han; Feng-Zao Chen (Analytica Chimica Acta, 2024)

Effective Determination of Diosmin Using Nitrogen Doped Carbon Dots as Probe Based on Internal Filtering Effect - Xian Chen; Menghan Zhang; Lang Zheng; Xiaoqin Deng; Qiang Chen; Wendi Han; Zhengjun Huang; Shaohuang Weng (Journal of Fluorescence, 2024)

A bifunctional amylopullulanase of Streptococcus suis ApuA contributes to immune evasion by interaction with host complement C3b - Jiajia Xu; Jiaqi Zhu; Weiyao Han; Siqi Pang; Simin Deng; Long Chen; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2024)

Variations in the oxidation potential of PM2.5 in an old industrial city in China from 2015 to 2018 - Zhaoqi Wang; Mengjie Deng; Shen Zhang; Zhihao Zhang; Caijiao Hu; Han Yue; Haibin Huang; Dengtai Wang; Xiaoxiao Li; Hairong Cheng (Science of The Total Environment, 2024)

Ensemble learning algorithms to elucidate the core microbiome's impact on carbon content and degradation properties at the soil aggregate level - Fengwu Zhou; Yunbin Jiang; Cheng Han; Huan Deng; Zongren Dai; Zimeng Wang; Wenhui Zhong (Science of The Total Environment, 2024)

Spatiotemporal variations and source on black carbon over Chongqing, China: Long-term changes and observational experiments - Yurong Zhang; Yong Han; Li Dong; Ximing Deng; Dan Ye; Shiyong Shao (Science of The Total Environment, 2024)

Underestimation of calcium carbonate saturation state in marginal seas due to the disregard of calcium ion addition: A case study of the Bohai sea, China - Yawen Wei; Nan Zheng; Xuemei Xu; Xue Deng; Liang Xue; Zhentong Yao; Hong Chen; Jianbo Han (Marine Environmental Research, 2024)

Ammonia oxidizing bacteria (AOB) denitrification and bacterial denitrification as the main culprit of high N2O emission in SBR with low C/N ratio wastewater - Dongxu Wang; Jingni Zhang; Wenkai Han; Peike Wu; Liangwei Deng; Wenguo Wang (Journal of Environmental Management, 2024)

Selective recovery of transition metals from spent lithium-ion batteries leachate with Ni synergistic extraction system - Yaxing Han; Ji Chen; Hailian Li; Yuefeng Deng (Journal of Environmental Chemical Engineering, 2024)

Simultaneous extraction of five heavy metal ions from root vegetables via dual-frequency ultrasound-assisted enzymatic digestion - Min Yuan; Xinyan Huan; Xiaojun Yang; Menghan Fan; Jiaqi Yin; YingQing Ma; Bo Deng; Hui Cao; Yiyi Han; Fei Xu (Food Chemistry, 2024)

Algorithm for the treatment of boundary conditions in NMM-SPH coupling models: Interface element-wise boundary particle scheme - Wenshuai Han; Shuhong Wang; Lijun Deng; Wenfang Liu; Wenpan Sun (Computers and Geotechnics, 2024)

Multi-polar group cationic collector HTTPD: Mechanistic insights into selective flotation of bastnaesite - Chang Liu; Longhua Xu; Jiushuai Deng; Zhiguo Han; Jia Tian; Donghui Wang; Kai Xue; Zhoujie Wang; Kaiqian Shu (Chemical Engineering Journal, 2024)

Gradient variations in rhizospheric soil exchangeable cations across a forest-steppe transect - Jiaxin Han; Ruzhen Wang; Jordi Sardans; Heyong Liu; Peng He; Huanhuan Deng; Weiyi Ma; Josep Peñuelas; Xingguo Han; Yong Jiang (CATENA, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Determination of contamination, source, and risk of potentially toxic metals in fine road dust in a karst region of Southwest China - Yingsen Zhang; Xinwei Lu; Xiufeng Han; Tong Zhu; Bo Yu; Zhenze Wang; Kai Lei; Yufan Yang; Sijia Deng (Environmental Geochemistry and Health, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

Central role of Sigma-1 receptor in ochratoxin A-induced ferroptosis - Wenying Chen; Lingyun Han; Ruiran Yang; Hongwei Wang; Song Yao; Huiqiong Deng; Shuangchao Liu; Yao Zhou; Xiao Li Shen (Archives of Toxicology, 2024)

Petrogenesis of Neoarchean granitic gneisses from the Daqishan area of the Dabie orogen and implications for the early crustal evolution of the Northern Yangtze Craton - Lingyao Kong; Xiang Xing; Qingsen Han; Hua Luo; Pan Guo; Xin Deng; Jun Wan; Chao Chen; Chengxin Liu (International Geology Review, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Insight into the differential response of functional denitrifiers to novel formulated organic amendments in soybean agroecosystem - Ugochi Uzoamaka Egbeagu; Yue Zhang; Yuanhang Wang; Ayodeji Bello; Liting Deng; Yu Sun; Yue Han; Liyan Zhao; Shuai Shi; Huajing Liu; Xiuhong Xu (Rhizosphere, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Emission characteristics of lead and particulate matter from lead and zinc smelters in China - Jiawei Zhang; Xiaohui Sun; Qingru Wu; Jianguo Deng; Zhijian Li; Minneng Wen; Liwen Xu; Yongzheng Gu; Tao Han; Lei Feng; Lei Duan (Journal of Hazardous Materials, 2024)

Constructing porous ZnFC-PA/PSF composite spheres for highly efficient Cs+ removal - Senjian Han; Chao Gao; Wenfeng Yan; Yafei Guo; Shiqiang Wang; Tianlong Deng (Journal of Environmental Sciences, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Effects of polysaccharides on colonic targeting and colonic fermentation of ovalbumin-ferulic acid based emulsion - Hesheng Liu; Zhenzhen Huang; Ting Xin; Lihong Dong; Mei Deng; Lipeng Han; Fei Huang; Dongxiao Su (Food Chemistry, 2024)

Characterisation of a SapYZU11@ZnFe2O4 biosensor reveals its mechanism for the rapid and sensitive colourimetric detection of viable Staphylococcus aureus in food matrices - Wenyuan Zhou; Aiping Deng; Xiaoxing Fan; Yeling Han; Yajun Gao; Lei Yuan; Xiangfeng Zheng; Dan Xiong; Xuechao Xu; Guoqiang Zhu; Zhenquan Yang (Food Microbiology, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Cryopreservation-enhanced differentiation capacity of embryogenic cultures of Castanea mollissima - Shuangxian Liu; Liang Lin; Biao Han; Junchao Ma; Hugh W. Pritchard; Xiaojian Hu; Min Deng; Hongying Chen (Cryobiology, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Quiescent Adult Neural Stem Cells: Developmental Origin and Regulatory Mechanisms - Han Meng; Yu Huan; Kun Zhang; Xuyang Yi; Xinyu Meng; Enming Kang; Shengxi Wu; Wenbing Deng; Yazhou Wang (Neuroscience Bulletin, 2024)
The existence of neural stem cells (NSCs) in the adult mammalian nervous system, although small in number and restricted to the sub-ventricular zone of the lateral ventricles, the dentate gyrus of the hippocampus, and the olfactory epithelium, is a gift of evolution for the adaptive brain function which requires persistent plastic changes of these regions. It is known that most adult NSCs are latent, showing long cell cycles. In the past decade, the concept of quiescent NSCs (qNSCs) has been widely accepted by researchers in the field, and great progress has been made in the biology of qNSCs. Although the spontaneous neuronal regeneration derived from adult NSCs is not significant, understanding how the behaviors of qNSCs are regulated sheds light on stimulating endogenous NSC-based neuronal regeneration. In this review, we mainly focus on the recent progress of the developmental origin and regulatory mechanisms that maintain qNSCs under normal conditions, and that mobilize qNSCs under pathological conditions, hoping to give some insights for future study.

Emergency room visits (ERVs) among occupational groups associated with ambient conditions in Taiwan - Ayushi Sharma; Kang Yajing; Min-Chun Lin; Liwen Deng; Yu-Kai Lin; Lin-Han Chianghsieh; Fung-Chang Sung; Yu-Chun Wang (International Archives of Occupational and Environmental Health, 2024)

The characteristics of nutrient distribution and influencing factors in the Chukchi Plateau and adjacent waters - Zhixin Ni; Han Zhang; Minxia Zhang; Tuanjie Li; Shengyong Li; Xin Chen; Ling Zhang; Yuan Gao; Changshu Chen; Zhongyuan Wang; Wei Deng; Hai zhou Zhang (Frontiers in Marine Science, 2024)
The Arctic is one of the regions under the most dramatic climate change. Global warming has led to elevated freshwater inflow into the western Arctic Ocean and significantly altered nutrient structure and biogeochemical cycling. In this work, inorganic dissolved nutrients in the Chukchi Plateau (CP) and adjacent regions were investigated to further understand their characteristics and influencing factors. Results showed that relatively high nutrient concentrations occurred in the water masses with salinity >32 psu, especially there was a nutrient-rich layer influenced by Winter Pacific Water in the water column (15.10±1.96, 2.23±0.26, and 23.46±6.64 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively). Contrarily, lower nutrient concentrations occurred in the mixing water of the upper layer (1.76±1.04, 1.15±0.16 and 3.76±2.29 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively) with a low DIN/P ratio (1.44±0.59), suggesting DIN has become the potentially biological limiting factor. Furthermore, the freshening and deepening of the upper layer driven by the Beaufort Gyre has hindered the nutrient transport from underlying layer into the upper layer. A maximum chla was observed at 36‒75 m water depth, and the phytoplankton biomass decreased from the western to the eastern CP, accompanied by a decreased contribution of micro-sized chla but an increased contribution of small-sized chla (74.0±0.1%). The phytoplankton resource use efficiency for DIN was estimated as (3.2±4.6)×10 -3 , which was primarily influenced by the physicochemical parameters of water and also largely regulated by the size structure of phytoplankton.

Associations of long-term exposure to low-level PM2.5 and brain disorders in 260,922 middle-aged and older adults - Ne Qiang; Yujia Bao; Yongxuan Li; Na Zhang; Yanqiu Zhou; Xiaobei Deng; Lefei Han; Jinjun Ran (Chemosphere, 2024)

Unlocking the potential of surface modification with phosphate on ball milled zero-valent iron reactivity:Implications for radioactive metal ions removal - Sheng Deng; Yu Yang; Xu Han; Qiyuan Liu; Mingxiao Li; Jing Su; Yonghai Jiang; Beidou Xi; YuHui Liu (Water Research, 2024)

Projecting future critical material demand and recycling from China's electric passenger vehicles considering vehicle segment heterogeneity - Zhenyu Dong; Han Hao; Xin Sun; Dengye Xun; Hao Dou; Jingxuan Geng; Ming Liu; Yunfeng Deng; Fuqua Zhao; Zongwei Liu (Resources, Conservation and Recycling, 2024)

Movement of ACC oxidase 3 mRNA from seeds to flesh promotes fruit ripening in apple - Ting Wang; Yi Zheng; Chen Xu; Yulin Deng; Xinyi Hao; Zicheng Chu; Ji Tian; Yi Wang; Xinzhong Zhang; Zhenhai Han; Ting Wu (Molecular Plant, 2024)

Life cycle environmental hotspots analysis of typical electrochemical, mechanical and electrical energy storage technologies for different application scenarios: Case study in China - Yanxin Li; Xiaoqu Han; Lu Nie; Yelin Deng; Junjie Yan; Tryfon C. Roumpedakis; Dimitrios-Sotirios Kourkoumpas; Sotirios Karellas (Journal of Cleaner Production, 2024)

Quantitative assessment of the impact factors upon remediation performance of the PRB technique in conjunction with pumping/recharge - Han Xiao; Yu Yang; Xiangjian Xu; Sheng Deng; Xu Han; Fu Xia; Yonghai Jiang (Groundwater for Sustainable Development, 2024)

Enhancing the flavour quality of Laiyang pear wine by screening sorbitol-utilizing yeasts and co-fermentation strategies - Qiaoyun Deng; Shuang Xia; Xiaoyu Han; Yilin You; Weidong Huang; Jicheng Zhan (Food Chemistry, 2024)

Polygonum minus: A tropical medicinal herb with vast applications in food, agricultural, and medicinal fields - Zhongming Yang; Xi Deng; Zhongguo Yang; Mingzhao Han; Norsharina Ismail; Kim Wei Chan; Ahmad Faizal Abdull Razis; Norhaizan Mohd Esa; Ket Li Ho; Md Zuki Abu Bakar (Food Bioscience, 2024)

Identifying a sustainable rice-based cropping system via on-farm evaluation of grain yield, carbon sequestration capacity and carbon footprints in Central China - Zhiming Deng; Xiaojian Ren; Jiayi Han; Kehui Cui; Kaiyan Han; Qian Yue; Jiyong Zhou; Zhongbing Zhai; Dongliang Xiong; Shen Yuan; Jianliang Huang; Shaobing Peng (Field Crops Research, 2024)

Modulating oxygen vacancies in MXene/MoO3-x smart fiber by defect engineering for ultrahigh volumetric energy density supercapacitors and wearable SERS sensors - Yiting Sun; Tiehu Li; Xin Liu; Yanying Han; Yuhui Liu; Amir Zada; Weibin Deng; Zeqi Yuan; Alei Dang (Chemical Engineering Journal, 2024)

Preparation of (S)-epichlorohydrin using a novel halohydrin dehalogenase by selective conformation adjustment - Xiao-Jian Zhang; Meng-Yu Huang; Xin-Xin Peng; Min Cao; Han-Zhong Deng; Yi-Chuan Gong; Xiao-Ling Tang; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2024)

Detection method for water-bearing structure in tunnel by DC resistivity based on directional indicating variable mesh - Lichao Nie; Zhaoyang Deng; Zhi-Qiang Li; Tingyi Wang; Lei Han; Yuancheng Li (Tunnelling and Underground Space Technology, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

The unequal impacts of extremely high temperatures on households’ adaptive behaviors: Empirical evidence from fine-grained electricity consumption data - Han Shi; Bo Wang; Yueming Lucy Qiu; Nana Deng; Baichen Xie; Bin Zhang; Shijun Ma (Energy Policy, 2024)

Dynamic analysis on an asymmetric spatial dumbbell-type model - Weipeng Hu; Bo Tang; Zhengqi Han; Pingwei Deng; Zichen Deng (Advances in Space Research, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Air pollution mixture associated with oxidative stress exacerbation and symptoms deterioration in allergic rhinitis patients: Evidence from a panel study - Jinhui Li; Haisheng Wu; Weiwei Xing; Xin Li; Zheshen Han; Renyue Ji; Zhengyi Deng; Minji Jung; Shengzhi Sun; Benjamin I. Chung; Andres Cardenas; Marvin E. Langston (Science of The Total Environment, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

A circular single-stranded DNA mycovirus infects plants and confers broad-spectrum fungal resistance - Xianhong Wang; Ioly Kotta-Loizou; Robert H.A. Coutts; Huifang Deng; Zhenhao Han; Ni Hong; Karim Shafik; Liping Wang; Yashuang Guo; Mengmeng Yang; Wenxing Xu; Guoping Wang (Molecular Plant, 2024)

Co-migration behavior of toluene coupled with trichloroethylene and the response of the pristine groundwater ecosystems – A mesoscale indoor experiment - Shuxuan Wu; Yu Yang; Zhifei Ma; Fan Feng; Xiangjian Xu; Sheng Deng; Xu Han; Beidou Xi; Yonghai Jiang (Journal of Hazardous Materials, 2024)

A novel plasmonic Z-scheme photocatalyst for solar-light-driven degradation of naphthalene in seawater: Degradation pathways and mechanism insight - Jize Liu; Xiaotong Xu; Shuang Song; Jiayi Xu; Yan Deng; Wenchao Yang; Jianbo Han (Journal of Environmental Chemical Engineering, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Chemical looping-based catalytic CH4 decomposition and successive coke gasification with CO2 on ordered mesoporous NiMCeOx (M = Co, Zr, La) - Sang Beom Han; Min Sung Kim; Yuchen Deng; Kyun Yeon Kang; Jae-Soon Choi; Eunjoo Jang; Jong Wook Bae (Chemical Engineering Journal, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

HOXB9 promotes laryngeal squamous cell carcinoma progression by upregulating MMP12 - Chuanhui Sun; Hua Deng; Qiuying Li; Peng Wang; Yujiang Chen; Yanan Sun; Changsong Han (Functional & Integrative Genomics, 2024)

Centurial deposition records of polychlorinated biphenyls and organochlorine pesticides in sediment cores from a plateau deep-water lake of China: Significance of anthropogenic impacts, transformation signals and ecological risks revealed by full congener analysis - Xuexin Han; Lei Xu; Aixin Deng; Peng Xing; Yan Xu (Science of The Total Environment, 2024)

Acid rain reduced soil carbon emissions and increased the temperature sensitivity of soil respiration: A comprehensive meta-analysis - Weichao Liu; Jingbo Fang; Yaoyue Liang; Xing Wang; Qi Zhang; Jinduo Wang; Mengfan He; Wenjie Wang; Jian Deng; Chengjie Ren; Wei Zhang; Xinhui Han (Science of The Total Environment, 2024)

Spatio-temporal variations of lacustrine groundwater discharge and related nutrient fluxes in a typical lake in front of hillocks - Yiqun Gan; Xiaoliang Sun; Jing Wu; Yao Du; Yamin Deng; Peng Han; Yanxin Wang (Journal of Hydrology, 2024)

Sediment microbial fuel cell monitoring repeated Cr(VI) shocks in different wetlands for a year: Performance and mechanism - Chenlu Li; Xiaofang Li; Tao Li; Yirui Su; Wenhui Zhong; Cheng Han; Yunbin Jiang; Huan Deng (Journal of Cleaner Production, 2024)

The cumulative impact of temperature and nitrogen availability on the potential nitrogen fixation and extracellular polymeric substances secretion by Dolichospermum - Dailan Deng; Han Meng; You Ma; Yongqi Guo; Zixuan Wang; Huan He; Wenming Xie; Jin-e Liu; Limin Zhang (Harmful Algae, 2024)

Transoceanic ships as a source of alien dinoflagellate invasions of inland freshwater ecosystems - Lixia Shang; Zhangxi Hu; Yunyan Deng; Jing Li; Yuyang Liu; Xiaoying Song; Xinyu Zhai; Zifeng Zhan; Wen Tian; Jinxiang Xu; Yangchun Han; Hao Shen; et al. (Harmful Algae, 2024)

Development and validation of a liquid chromatography tandem mass spectrometry method for the determination of 10 mycotoxins in beer of the Chinese market and exposure estimate - Tianyang Wu; Kun Kang; Ying Xia; Huan Deng; Bing Han; Xiaoyu Han; Yiding Xie; Chenyu Li; Jicheng Zhan; Weidong Huang; Yilin You (Food Research International, 2024)

The novel lactoferrin and DHA-codelivered liposomes with different membrane structures: Fabrication, in vitro infant digestion, and suckling pig intestinal organoid absorption - Xiankang Xu; Aiqian Ye; Tingting Zhang; Yujie Pan; Hanyun Jiang; Leiyu Deng; Yumei Qin; Jessie Li; Jianzhong Han; Weilin Liu (Food Chemistry, 2024)

Discussion of “Inactivation of foodborne pathogenic and spoilage bacteria by single and dual wavelength UV-LEDs: Synergistic effect and pulsed operation” [Food Control 125 (2021) 107999] - Baoqing Deng; Xiucheng Han; Xiaonan Zou; Jiajia Luo (Food Control, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Floral resource partitioning of coexisting bumble bees: Distinguishing species‐, colony‐, and individual‐level effects - Zhong‐Ming Ye; Yong‐Deng He; Pedro J. Bergamo; Michael C. Orr; Wen Huang; Xiao‐Fang Jin; Han‐Ning Lun; Qing‐Feng Wang; Chun‐Feng Yang (Ecology, 2024)
Resource partitioning is considered a key factor in alleviating competitive interactions, enabling coexistence among consumer species. However, most studies have focused on resource partitioning between species, ignoring the potentially critical role of intraspecific variation in resource use. We investigated floral resource partitioning across species, colonies, and individuals in a species‐rich bumblebee community in the diversification center of bumblebees. We used a total of 10,598 bumblebees belonging to 13 species across 5 years in the Hengduan Mountains of southwest China. First, we evaluated the influence of a comprehensive set of floral traits, including both those related to attractiveness (flower color and shape) and rewards (pollen, sugar ratio, nectar volume, sugar concentration, and amino acid content) on resource partitioning at the species level in bumblebee–plant networks. Then, we explored intraspecific resource partitioning on the colony and individual levels. Our results suggest that bumblebee species differ substantially in their use of the available floral resources, and that this mainly depends on flower attractiveness (floral color and shape). Interestingly, we also detected floral resource partitioning at the colony level within all commonest bumblebee species evaluated. In general, floral resource partitioning between bumblebee individuals decreased with species‐ and individual‐level variation in body size (intertegular span). These results suggest that bumblebee species may coexist via the flexibility in their preferences for specific floral traits, which filters up to support the co‐occurrence of high numbers of species and individuals in this global hotspot of species richness.

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

Assessment of natural resource endowment and urban-rural integration for sustainable development in Xinjiang, China - Keqiao Su; Dawei He; Ruixue Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2024)

The impact of cross-regional social and ecological interactions on ecosystem service synergies - Ze Han; Xiangzheng Deng (Journal of Environmental Management, 2024)

A novel p-type CoSe2 co-catalyst cooperated with hematite for boosting photoelectrochemical water splitting - Shanshan Jiang; Dabo Liu; Dongke Li; Mengyuan Xiao; Yunchou Deng; Yu Han; Ran Tao; Xiaoxing Fan; Kuiyong Liu (Fuel, 2024)

Unveiling the activation mechanism: The role of nitrogen-doped biochar in enhancing Fe(VI) catalysis - Sheng Deng; Xu Han; Ningqing Lv; Xiaochun Yang; Qiyuan Liu; Yonghai Jiang; Yu Yang; Beidou Xi (Chemical Engineering Journal, 2024)

Dual effect of organic/inorganic artificial protective layer to construct high-performance zinc metal anode - Yingxiao Du; Ruotong Li; Tingting Wang; Ziyi Feng; Han Dong; Fangfang Fan; Dezhao Deng; Jing Zhu; Yongguang Liu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2024)

The accumulation capacity of microbial residues in the rhizosphere increased along an elevation gradient - Shaojun Deng; Qitong Wang; Dungang Wang; Han Yang; Peipei Zhang; Na Li; Xinjun Zhang; Ruihong Wang; Huajun Yin (CATENA, 2024)

Effects of crop growth and surface microtopography on runoff and soil losses in the red soil region of southern China - Kenan Deng; Yan Zhu; Zhao Liu; Guanfang Sun; Xudong Han; Haijin Zheng (CATENA, 2024)

Spatial patterns and controlling factors of radon concentration in Quaternary alluvial-lacustrine aquifer systems - Jiawen Xu; Yao Du; Xiaoliang Sun; Yamin Deng; Shunjie Zhu; Peng Han; Yiqun Gan (Applied Geochemistry, 2024)

Rapid identification of mushroom toxins by direct electrospray probe mass spectrometry for emergency care - Hung Su; Zong-Han Jiang; Yi-Wen Hsu; Yu-Chi Wang; Yun-Yi Chen; Deng-Chyang Wu; Jentaie Shiea; Chi-Wei Lee (Analytica Chimica Acta, 2024)

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Identification and analysis of the light-responsive characteristics of the bHLH transcription factor gene family in Chrysanthemum morifolium - Mengke Qin; Tian Tian Wang; Dandan Deng; Qingchen Zhang; Xiao Qin Zhu; Fangfang Jia; Dongli Pei; Shuang Han (South African Journal of Botany, 2024)

Strong metal oxide-zeolite interactions during selective catalytic reduction of nitrogen oxides - Jiebing He; Jiang Deng; Tianwei Lan; Xiangyu Liu; Yongjie Shen; Lupeng Han; Junan Wang; Dengsong Zhang (Journal of Hazardous Materials, 2024)

Nature, source, and evolution of the ore-forming fluids in the Dunbasitao gold deposit, East Junggar, China: Constraints from geology, fluid inclusions, and C-H-O isotopes - Wenxiang Liu; Xiaohua Deng; Franco Pirajno; Shen Han; Xi Chen; Xun Li; Abulimiti Aibai; Yanshuang Wu; Yong Wang; Yanjing Chen (Journal of Geochemical Exploration, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

A systematic investigation of direct and indirect-cold atmospheric plasma treatment on Bacillus cereus and the application in black pepper - Yuhan Wang; Yana Liu; Yijie Zhao; Yingying Sun; Han Wang; Dongyi Wang; Jiaolong Deng; Xiaoju Cui; Zhongqiu Ma; Ruitong Dai; Xingmin Li; Fei Jia (Innovative Food Science & Emerging Technologies, 2024)

Bank erosion under the impacts of hydraulic erosion, river stage change and revetment protection in the Middle Yangtze River - Yueyao Zhou; Junqiang Xia; Shanshan Deng; Zhong Han (Geomorphology, 2024)

Deep integration of pyrolysis kinetics and pyrolysis mechanism of polyimide aerogels - Xiangming Hu; Hongbin Wei; Yurui Deng; Zhiyuan Yang; Xiaoxuan Wei; Guoyu Han (Fuel, 2024)

Defect-rich hollow double-shell bimetallic phosphides for electrocatalytic hydrogen evolution over a wide pH range - Chunpu Li; Han Zhang; Yuying Zhao; Aiman Li; Zexing Wu; Zhenyu Xiao; Zhenjiang Li; Fusheng Liu; Ying Deng; Lei Wang (Fuel, 2024)

Biodiversity and core microbiota of key-stone ecological clusters regulate compost maturity during cow-dung-driven composting - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Yong Yang; Xingxiang Deng; Guixian Xie; Gongwen Luo (Environmental Research, 2024)

Soil properties and fungal community jointly explain N2O emissions following N and P enrichment in an alpine meadow - Zhenrong Lin; Lina Shi; Xiaoting Wei; Bing Han; Cuoji Peng; Zeying Yao; Yicheng He; Qing Xiao; Xinmin Lu; Yanfang Deng; Huakun Zhou; Kesi Liu; et al. (Environmental Pollution, 2024)

Numerical-geostatistical-based approach to investigate the earth pressure evolution within the large grid wall foundation under adjacent surcharge loading - Marsheal Fisonga; Yongtao Hu; Shijie Han; Yongfeng Deng; Rennie B. Kaunda (Computers and Geotechnics, 2024)

Experimental study of natural convection and cooling capacity of closed crushed-rock layers affected by summer rainfall in cold regions - Yang Lv; Fenglei Han; Hang Cao; Yongqi Geng; Kaichi Qiu; Lu Cheng; Wei Yang; Kaiyu Deng (Cold Regions Science and Technology, 2024)

A novel evaluation indicator and optimal heating strategy for using an intermittent-operation catalytic combustion heater in open cold environments - Mingyuan Qin; Bee Teng Chew; Yat Huang Yau; Xiaofei Han; Zhen Yang; Tong Cui; Fei Deng; Song Pan (Building and Environment, 2024)

An effective pharmacological hydrogel induces optic nerve repair and improves visual function - Lipeng Wang; Shan Zhang; Yawen Han; Shuo Tang; Jiarui Li; Lina Bu; Dongyu Zhao; Hongkui Deng (Science China Life Sciences, 2024)

Effects of ridge tillage and peanut growth on the surface–subsurface runoff generation and soil loss in the red soil sloping farmland of southern China - Kenan Deng; Zhao Liu; Xudong Han; Yan Zhu; Guanfang Sun; Minghao Mo (Journal of Soils and Sediments, 2024)

Lignocellulosic fraction-induced niche differentiation within dissimilatory iron reducing bacterial groups in a paddy soil - Yunbin Jiang; Wenting Hu; Kailou Liu; Shangshu Huang; Fengwu Zhou; Cheng Han; Huan Deng; Wenhui Zhong (Soil Ecology Letters, 2024)

Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of Coilia nasus in the Yangtze River - Shuwei Wei; Zhong Hua; Yanping Yang; Fengjiao Ma; Wei Han; Wei Zhang; Congping Ying; Yanmin Deng; Kai Liu (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.

Synthesis of sewage sludge biochar in molten salt environment for advanced wastewater treatment: Performance enhancement, carbon footprint and environmental impact reduction - Zeyu Fan; Xian Zhou; Qi Lu; Zhuo Fan Gao; Shanshan Deng; Ziling Peng; Wei Han; Xia Chen (Water Research, 2024)

Synergistic catalysis induced by a multicomponent system constructed with combined DBD plasma, g-C3N4/FOD and persulfate for trichloroethylene removal - Wei Gao; Xiaoying Xu; Xueqi Han; Ling Zhang; Haitao Ding; Chengxun Deng (Journal of Water Process Engineering, 2024)

Synchronous fluorescence detection of nitrite in meat products based on dual-emitting dye@MOF and its portable hydrogel test kit - Siyang Deng; Junmei Liu; Dong Han; Xinting Yang; Huan Liu; Chunhui Zhang; Christophe Blecker (Journal of Hazardous Materials, 2024)

Estimating fossil CO2 emissions from COVID-19 post-pandemic recovery in G20: A machine learning approach - Shiyu Deng; Xi Deng; Han Chen; Zhangcai Qin (Journal of Cleaner Production, 2024)

Metagenomic insights into microorganisms and antibiotic resistance genes of waste antibiotic fermentation residues along production, storage and treatment processes - Ziming Han; Xiao Luan; Haodi Feng; Yanqin Deng; Min Yang; Yu Zhang (Journal of Environmental Sciences, 2024)

Microbial removal of uranyl from aqueous solution by Leifsonia sp. in the presence of different forms of iron oxides - Chao Pang; Yuan Li; Han Wu; Zhiwen Deng; Shanlin Yuan; Wenfa Tan (Journal of Environmental Radioactivity, 2024)

Unveiling the formation and magma transport dynamics of the Ulanqab maar volcanic cluster in the western North China Craton: Insights from 40Ar-39Ar geochronology, mineral chemistry, and Sr-Nd-Mg isotopes - Zong-yuan Tang; Chen-chang Chen; Si-ying Gui; Jie Li; De-you Sun; Chang-zhou Deng; Han Zheng; Guo-chun Zhao (Gondwana Research, 2024)

Synthesis and performance evaluation of multi-crosslinked preformed particle gels with ultra-high strength and high-temperature and high-salinity resistance for conformance control - Jianan Deng; Haoyu Lian; Yuan Zhuang; Honghao Zhao; Zhanyi Wang; Yongjun Tian; Chao Lin; Haozhong Yuan; Miao Han; Guiwu Lu; Xiao Zhang (Fuel, 2024)

Recent advancements in the taste transduction mechanism, identification, and characterization of taste components - Pinhu Wang; Xiang Ye; Jun Liu; Yao Xiao; Min Tan; Yue Deng; Mulan Yuan; Xingmei Luo; Dingkun Zhang; Xingliang Xie; Xue Han (Food Chemistry, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

A novel sulfur supply strategy for maximizing lipid production in Tribonema minus (Xanthophyceae) - Baoyan Gao; Jian Hong; Qian Deng; Baoye Han; Jielin Kong; Chengwu Zhang (Bioresource Technology, 2024)

Exploring the potential of cutting battery use in electric vehicles - Yunfeng Deng; Han Hao; Chengru Jia (Clean Technologies and Environmental Policy, 2024)

Saturation Estimation with Complex Electrical Conductivity for Hydrate-Bearing Clayey Sediments: An Experimental Study - Lanchang Xing; Shuli Zhang; Huanhuan Zhang; Chenyutong Wu; Bin Wang; Liyun Lao; Wei Wei; Weifeng Han; Zhoutuo Wei; Xinmin Ge; Shaogui Deng (Journal of Ocean University of China, 2024)

Particulate polycyclic aromatic hydrocarbons in rural households burning solid fuels in Xuanwei County, Southwest China: occurrence, size distribution, and health risks - Xinyu Han; Dingshuang Li; Wei Du; Jianwu Shi; Shuai Li; Yuqi Xie; Shihan Deng; Zhihao Wang; Senlin Tian; Ping Ning (Environmental Science and Pollution Research, 2024)

Residence time and the concentration of microorganism in the ozone contactor: a CFD simulation on chamber deflectors - Xiucheng Han; Xiaonan Zou; Jiajia Luo; Jiming Wu; Baoqing Deng (Environmental Science and Pollution Research, 2024)

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Active microbial taxa preferentially assimilate inorganic nitrogen in acidic upland soils using a 15N-DNA-SIP approach - Ran Liu; Cheng Han; Yu Kang; Yunbin Jiang; Huan Deng; Kailou Liu; Jinbo Zhang; Wenhui Zhong (Soil Biology and Biochemistry, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Mixing uniformity effect on leaching behaviour of cement-based solidified contaminated clay - Tingting Deng; Marsheal Fisonga; Han Ke; Ling Li; Jianwei Wang; Yongfeng Deng (Science of The Total Environment, 2024)

Degradation of aqueous phenol by combined ultraviolet and electrochemical oxidation treatment - Hongxiang Xu; Xin Sun; Han Yang; Jiahua Cui; Jingzheng Wang; Yuntao Kang; Jiushuai Deng; Gen Huang (Journal of Cleaner Production, 2024)

Field-based evidence for the enrichment of intrinsic antibiotic resistome stimulated by plant-derived fertilizer in agricultural soil - Shihai Liu; Ziming Han; Dong Zhu; Xiao Luan; Liujie Deng; Liping Dong; Min Yang; Yu Zhang (Journal of Environmental Sciences, 2024)

Clean energy consumption in newly poverty-relieved villages: Limited adaptability to external shocks - Bo Wang; Shuling Xu; Nana Deng; Han Shi (Environmental Impact Assessment Review, 2024)

Corrosion-induced growth control of lead halide perovskite nanoparticles - Chun Sun; Kai Lian; Xiaoyu Zhang; Zhengtong Wang; Yiwei Zhao; Zhihui Deng; Fuhao Zhang; Jiachen Han; Hu Zhang; Wengang Bi (Chemical Engineering Journal, 2024)

Novel layer-to-layer charge transfer in an anion-pillared metal-organic framework for efficient CO2 photoreduction to CH4 - Xinxin Han; Hongtao Wu; Shixia Chen; Shuguang Deng; Jun Wang (Chemical Engineering Journal, 2024)

Organic hybrid tetranuclear clusteroluminogens: Blue-light-excitable LED with ultrahigh luminous efficacy - Yang-Peng Lin; Xuexia Lu; Zhizhuan Zhang; Xinghui Qi; Jiance Jin; Jielong Xu; Yancong Wu; Yanan Wu; Zhonghua Deng; Xiao-Ying Huang; Cuiping Han; Sanlue Hu; et al. (Chemical Engineering Journal, 2024)

Carbon fiber-based multichannel solid-contact potentiometric ion sensors for real-time sweat electrolyte monitoring - Meixue Lai; Lijie Zhong; Siyi Liu; Yitian Tang; Tingting Han; Huali Deng; Yu Bao; Yingming Ma; Wei Wang; Li Niu; Shiyu Gan (Analytica Chimica Acta, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Past and projected future patterns of fractional vegetation coverage in China - Zijie Kong; Hongbo Ling; Mingjiang Deng; Feifei Han; Junjie Yan; Xiaoya Deng; Zikang Wang; Yuanzhi Ma; Wenqi Wang (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Synergistic effects of zero-valent iron-carbon galvanic cells on the microalgal-bacterial symbiosis system for efficient anaerobic digestion effluent treatment - Weiwei Ma; Zhen Cao; Xueqing Shi; Shi-Hai Deng; Han Dai; Binghan Xie (Journal of Water Process Engineering, 2023)

Ultrasonic assisted activation of persulfate for the treatment of spent porous biochar: Degradation of adsorbed PFOA and adsorbent regeneration - Jiaqin Deng; Ying Fang; Changlan Hou; Yanru Zhang; Meifang Li; Jianing Han; WanXuan Du; Chunfang Tang; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Metabolites and metagenomic analysis reveals the quality of Pu-erh “tea head” - Shiqiang He; Xinyi Deng; Yuxin Han; Zhengli Gong; Jian Wang; Xiaoqi Tao; Huarong Tong; Yingjuan Chen (Food Chemistry, 2023)

A novel 3D-fluorescence sensing strategy based on HN-chitosan polymer probe for rapid identification and quantification of potential adulteration in saffron - Wanjun Long; Gaoqiong Deng; Yanmei Zhu; Qingyang Han; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Achieving broadband electromagnetic absorption at a wide temperature range up to 1273 K by metamaterial design on polymer-derived SiC-BN@CNT ceramic composites - Bin Ren; Yumeng Deng; Yujun Jia; Liyuan Han; Xin Wang; Hejun Li (Chemical Engineering Journal, 2023)

Bacterial cellulose-based film with self-floating hierarchical porous structure for efficient solar-driven interfacial evaporation - Mengtian Jin; Xiangyang Qu; Jing Li; Lili Deng; Zhiliang Han; Shiyan Chen; Huaping Wang (Carbohydrate Polymers, 2023)

Biotechnology Remediation and Environmental Behavior of Microplastics in Soils: A Review - Weiying Feng; Yuxin Deng; Yingnan Cao; Jing Liu; Yunping Han; Jianguo Liu; Qingfeng Miao; Fang Yang; Ying Zhu; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Curcumin alleviates traumatic brain injury induced by gas explosion through modulating gut microbiota and suppressing the LPS/TLR4/MyD88/NF-κB pathway - Xinwen Dong; Lvfei Deng; Yaguang Su; Xiaofeng Han; Sanqiao Yao; Weidong Wu; Jia Cao; Linqiang Tian; Yichun Bai; Guizhi Wang; Wenjie Ren (Environmental Science and Pollution Research, 2023)

Research on Method of Collision Avoidance Planning for UUV Based on Deep Reinforcement Learning - Wei Gao; Mengxue Han; Zhao Wang; Lihui Deng; Hongjian Wang; Jingfei Ren (Journal of Marine Science and Engineering, 2023)
A UUV can perform tasks such as underwater surveillance, reconnaissance, surveillance, and tracking by being equipped with sensors and different task modules. Due to the complex underwater environment, the UUV must have good collision avoidance planning algorithms to avoid various underwater obstacles when performing tasks. The existing path planning algorithms take a long time to plan and have poor adaptability to the environment. Some collision-avoidance planning algorithms do not take into account the kinematic limitations of the UUV, thus placing high demands on the performance and control algorithms of UUV. This article proposes a PPO−DWA collision avoidance planning algorithm for the UUV under static unknown obstacles, which is based on the proximal policy optimization (PPO) algorithm and the dynamic window approach (DWA). This algorithm acquires the obstacle information from forward-looking sonar as input and outputs the corresponding continuous actions. The PPO−DWA collision avoidance planning algorithm consists of the PPO algorithm and the modified DWA. The PPO collision avoidance planning algorithm is only responsible for outputting the continuous angular velocity, aiming to reduce the difficulty of training neural networks. The modified DWA acquires obstacle information and the optimal angular velocity from the PPO algorithm as input, and outputs of the linear velocity. The collision avoidance actions output by this algorithm meet the kinematic constraints of UUV, and the algorithm execution time is relatively short. The experimental data demonstrates that the PPO−DWA algorithm can effectively plan smooth collision-free paths in complex obstacle environments, and the execution time of the algorithm is acceptable.

Environmental DNA Detects Remaining Populations of Endangered Stream Salmon (Sichuan Taimen: Hucho bleekeri Kimura Salmonidae) in the Qinling Mountains - Hu Zhao; Jianlu Zhang; Qijun Wang; Hongying Ma; Han Zhang; Fei Kong; Jie Deng; Cheng Fang; Hongxing Zhang; Wei Jiang (Fishes, 2023)
Sichuan taimen (Hucho bleekeri Salmonidae) populations are declining, and the status of remnant populations in the Qinling Mountains is poorly known. In this study, eDNA and creel netting were used to estimate the distributions of Sichuan taimen in two upper tributaries of the Hanjiang River. A qPCR assay was applied to detect the eDNA of H. bleekeri, and the presence of Sichuan taimen in the Taibai River, but not in the Xushui River, was confirmed. Sampling during summer achieved a relatively higher detection rate. The utility of eDNA techniques for detecting low-density Sichuan taimen was demonstrated in intricate stream ecosystems. The eDNA method can increase the efficiency of the management of endangered freshwater species, such as Sichuan taimen, by providing reliable distribution data.

Spatiotemporal variations and its driving factors of NDVI in Northwest China during 2000–2021 - Jiaxin Zhang; Tao Yang; Mingjiang Deng; Huiping Huang; Yuping Han; Huanhuan Xu (Environmental Science and Pollution Research, 2023)

Efficient removal of per- and polyfluoroalkyl substances from biochar composites: Cyclic adsorption and spent regenerant degradation - Jiaqin Deng; Jianing Han; Changlan Hou; Yanru Zhang; Ying Fang; WanXuan Du; Meifang Li; Yuan Yuan; Chunfang Tang; Xinjiang Hu (Chemosphere, 2023)

Gastrointestinal microbiome, resistance genes, and risk assessment of heavy metals in wild giant pandas - Lei Jin; Hongning Wu; Guo Li; Shengzhi Yang; Rongping Wei; Yan Huang; Petri Penttinen; Wenwen Deng; Jianbin Chen; Xinfeng Han; Caiwu Li; Lan Hu; et al. (Science of The Total Environment, 2023)

A study on the coupling mechanism of hydrate dissociation-seepage-heat transfer induced by suction anchor installation in marine sediments - Shuxin Han; Xuejing Deng; Wangchen Li; Long Yu; Longfei Guan (Ocean Engineering, 2023)

Review of influence of steric effect on aggregation behavior of fine particles - Hongxiang Xu; Han Tian; Jiushuai Deng; Qiming Zhuo; Jiahua Cui; Jingzheng Wang; Yanan Yin; Peng Yu (Minerals Engineering, 2023)

Preliminary magnetotelluric investigation of crustal magma plumbing system beneath the Wulanhada volcanic field, northern China: Implications for the Magma reservoir and pathway - Zeyi Dong; Qibin Xiao; Yan Deng; Bing Han; Ji Tang; Lifeng Wang; Jijun Wang (Journal of Volcanology and Geothermal Research, 2023)

The influence of anthropogenic climate change on meteorological drought in the Lancang-Mekong River basin - Xingye Han; Qiongfang Li; Xiaoqiang Yang; Shuhong Xu; Zhenhua Zou; Mingjiang Deng; Wen Wang (Journal of Hydrology, 2023)

Weakened economic impacts with future intensifying drought in Chinese mainland - Feifei Han; Hongbo Ling; Xiaoya Deng; Junjie Yan; Yanming Gong; Guangpeng Zhang; Yuanzhi Ma (Journal of Cleaner Production, 2023)

Vitamin B12 and iron-rich sludge-derived biochar enhanced PFOA biodegradation: Importance of direct inter-species electron transfer and functional microbes - Kaikai Zhang; Jiayu Deng; Wei-Han Lin; Shaogang Hu (Journal of Environmental Management, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Rebuilding high-quality near-surface ozone data based on the combination of WRF-Chem model with a machine learning method to better estimate its impact on crop yields in the Beijing-Tianjin-Hebei region from 2014 to 2019 - Tian Han; Xiaomin Hu; Jing Zhang; Wenhao Xue; Yunfei Che; Xiaoqing Deng; Lihua Zhou (Environmental Pollution, 2023)

Evaluation of urban public transport sustainability in China based on the Driving Force-Pressure-State-Impact-Response (DPSIR) framework——A case study of 36 major cities - Xiaoran Hou; Tao Lv; Jie Xu; Xu Deng; Feng Liu; Jasmine Siu Lee Lam; Zhenzhen Zhang; Xuesen Han (Environmental Impact Assessment Review, 2023)

Analysis of spatial and temporal carbon emission efficiency in Yangtze River Delta city cluster — Based on nighttime lighting data and machine learning - Qingqing Sun; Hong Chen; Yujie Wang; Han Huang; Shaoxian Deng; Chenxin Bao (Environmental Impact Assessment Review, 2023)

Nickel phosphide nanoarrays decorated on amorphous NiPOx/Fe(OH)3: A stable core–shell electrocatalyst for efficient oxygen evolution at large current density - Xinding Lv; Yan Li; Fei Deng; Haotong Li; Shutong Wan; Xue Han; Wanqi Zhang; Xia Tao (Chemical Engineering Journal, 2023)

Effect of extracellular polymeric substances on Dolichospermum aggregation during temperature rise - Dailan Deng; Han Meng; You Ma; Yongqi Guo; Zixuan Wang; Huan He; Khan Waqas; Jin’e Liu; Limin Zhang (Journal of Oceanology and Limnology, 2023)

Mangrove forest mapping from object-oriented multi-feature ensemble classification using Sentinel-2 images - Han Zhang; Qing Xia; Shuo Dai; Qiong Zheng; Yunfei Zhang; Xingsheng Deng (Frontiers in Marine Science, 2023)
Accurate mapping of mangrove forests is crucial for understanding their ecosystem function and developing effective management policies. However, the absence of an operational multi-feature fusion approach and an ensemble classification system restricts the achievement of this goal. This study aims to develop an object-oriented multi-feature ensemble classification scheme (OMEC). First, an enhanced mangrove spectral index (EMSI) is established by analyzing the spectral reflectance differences between mangrove forests and other land cover types. Sentinel-2 images are segmented into objects using the multi-resolution segmentation method. Then, spectral, textural, and geometric features are extracted, and these features (including EMSI) are inputted into the nearest neighbor classifier to implement mangrove classification. The experiment was conducted in three typical mangrove areas in China using Sentinle-2 images. The results demonstrate that EMSI exhibits good spectral separability for mangroves and performs well in the ensemble classification scheme. The overall accuracy of mangrove classification exceeds 90%, with a Kappa coefficient greater than 0.88. The object-oriented multi-feature ensemble classification scheme significantly improves accuracy and exhibits excellent performance. The method enhances the accuracy of mangrove classification, enriches the approach to mangrove remote sensing interpretation, and offers data support and scientific references for the restoration, management, and protection of coastal wetlands.

A rapid segmentation method for weed based on CDM and ExG index - Xiaowu Han; Han Wang; Ting Yuan; Kunlin Zou; Qianfeng Liao; Kai Deng; Zhiqin Zhang; Chunlong Zhang; Wei Li (Crop Protection, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

A fully π-conjugated covalent organic framework with dual binding sites for ultrasensitive detection and removal of divalent heavy metal ions - Bin Zhu; Longyi Zhu; Shengyuan Deng; Ying Wan; Feng Qin; Haikang Han; Jun Luo (Journal of Hazardous Materials, 2023)

Performance evaluation on CO2 fixation with chlorine gas production based on direct electrolysis of seawater - Ling Han; Shuai Deng; Ruikai Zhao; Xun Wang; Zhihao Guo; Yixuan Li; Peng Sun (Journal of Environmental Chemical Engineering, 2023)

Enhanced degradation of tetracycline hydrochloride with in situ prepared ferrate supernatant based on calcium hypochlorite: Compare with purified and commercial ferrate - Xiaochun Yang; Yu Yang; Xu Han; Yonghai Jiang; Beidou Xi; Han Xiao; Xiangjian Xu; Yuhan Hu; Sheng Deng; Jiao Zhang (Journal of Environmental Chemical Engineering, 2023)

Water distribution based on SAR and optical data to improve hazard mapping - Yang Han; Fan Deng; Jie Gong; Zhiyuan Li; Ziyang Liu; Jing Zhang; Wenjun Liu (Environmental Research, 2023)

Occupant behavior modules development for coupled simulation in DeST 3.0 - Xiaoyu Jia; Yiqun Pan; Mingya Zhu; Han Zhu; Zhengrong Li; Jingsi Zhang; Xiang Zhou; Song Pan; Chuang Wang; Da Yan; Zejun Wu; Huiyan Deng; et al. (Energy and Buildings, 2023)

Transdermal delivery of Fluoropolymer-Modified microneedle vaccines against rabies elicits potent humoral immunity - Jiamin Deng; Zongmei Wang; Zhipeng Zhou; Wentao Yu; Xun Li; Zhiyong Song; Heyou Han; Ling Zhao (Chemical Engineering Journal, 2023)

Surface nano-engineering of cellulosic textiles for superior biocidal performance and effective bacterial detection - Chao Deng; Zhaochuan Yu; Fangyuan Liang; Yuqian Liu; Farzad Seidi; Qiang Yong; Chao Liu; Yinjiang Zhang; Jingquan Han; Huining Xiao (Chemical Engineering Journal, 2023)

A new algorithm for real-time detection of window opening area in residential buildings - Yiqiao Liu; Wen Tong Chong; Yat Huang Yau; Di Han; Mingyuan Qin; Fei Deng; Xiyao Wang; Song Pan (Building and Environment, 2023)

Single and Combined Effects of Short-Term Selenium Deficiency and T-2 Toxin-Induced Kidney Pathological Injury Through the MMPs/TIMPs System - Ziwei Guo; Mumba mulutula Chilufya; Huan Deng; Lichun Qiao; Jiaxin Liu; Xiang Xiao; Yan Zhao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jing Han (Biological Trace Element Research, 2023)

Impacts of cross-regional population migration and agglomeration on carbon emissions in China - Ze Han; Xiangzheng Deng (Applied Geography, 2023)

Natural phosphorus-ferromanganese ore-based composites for the simultaneous remediation of arsenic- and lead-co-contaminated groundwater: synergistic effectiveness, kinetics, and mechanisms - Hongli Lu; Xiangjian Xu; Yu Yang; Han Xiao; Fu Xia; Xu Han; Sheng Deng; Shuxuan Wu; Xingang Wang; Yonghai Jiang; Qinghua Yan (Environmental Science and Pollution Research, 2023)

Permanganate activation by glucose-derived carbonaceous materials for highly efficient degradation of phenol and p-nitrophenol: Formation of hydroxyl radicals and multiple roles of carbonaceous materials - Kaikai Zhang; Muhan Qin; Chih-Ming Kao; Jiayu Deng; Jing Guo; Qiong Guo; Jing Hu; Wei-Han Lin (Chemosphere, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

How does Microcystis aeruginosa respond to elevated temperature? - Yongqi Guo; Han Meng; Sichuan Zhao; Zixuan Wang; Lin Zhu; Dailan Deng; Jine Liu; Huan He; Wenming Xie; Guoxiang Wang; Limin Zhang (Science of The Total Environment, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

Physical model test on the mechanical behavior and progressive failure of tunnel-type anchorages - Yafeng Han; Xinrong Liu; Libing Du; Zhiyun Deng; Xiaohan Zhou; Yu Xiao; Gang Zhang; Guoshen Lai (International Journal of Rock Mechanics and Mining Sciences, 2023)

Cooperated catalytic mechanism of atomically dispersed binary Cu-N4 and Zn-N4 in N-doped carbon materials for promoting electrocatalytic CO2 reduction to CH4 - Cuihua An; Shuai Wu; Rui Huang; Xiaodong Chen; Xiaopeng Han; Hassanien Gomaa; Qibo Deng; Libin Zhao; Ning Hu (Chemical Engineering Journal, 2023)

Nanocomposite scintillation perovskite-delignified wood photonic guides for X-ray imaging - Yifan Zhou; Zhiliang Deng; Bing Wang; Pei Li; Lingxi Li; Wenmin Han; Jie Huang; Wenbao Jia; Xiaoping Ouyang; Qiang Xu; Kostya (Ken) Ostrikov (Chemical Engineering Journal, 2023)

Nano-elemental selenium particle developed via supramolecular self-assembly of chondroitin sulfate A and Na2SeO3 to repair cartilage lesions - Jing Han; Huan Deng; Yang Li; Lichun Qiao; Hongrui Jia; Lan Zhang; Linghang Wang; Chengjuan Qu (Carbohydrate Polymers, 2023)

Protective effect of solanesol in glucose-induced hepatocyte injury: Mechanistic insights on oxidative stress and mitochondrial preservation - Yiqiu Liu; Musen Lin; Xingrui Mu; Lin Qin; Junyu Deng; Ye Liu; Xingqian Wu; Wenjie He; Huiwen Pang; Felicity Han; Chengxin Sun; Xuqiang Nie (Chemico-Biological Interactions, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Profile and relaxation of sequence-specificity of DNA sulfur binding domains facilitate new nucleic acid detection platform - Yuting Shuai; Anan Xu; Jiayi Li; Zhaoxi Han; Dini Ma; Hairong Duan; Xinye Wang; Lan Jiang; Jingyu Zhang; Gao-Yi Tan; Xueting Liu; Yi-Lei Zhao; et al. (Science Bulletin, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Design of red-emitting 1D zinc coordination polymer for targeted drug delivery to nucleus - Shuo Xiang; Jia Liu; Guangze Han; Wei Zhang; Yanyang Long; Yuxian Deng; Binju Wang; Qunhong Weng (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Hydrolysis and condensation kinetic studies of mercaptopropyl trimethoxysilane using in-situ Raman spectroscopy - Chunli Han; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

Ultrasound-induced cell disintegration and its ultrastructure characterization for the valorisation of Chlorella pyrenoidosa protein - Yong Deng; Xiaoling Yang; Tianyi Yan; Weidong Xu; Jiaheng Li; Ruihao Niu; Runan Zhao; Han Wang; Hao Wang; Tingting Chen; Mingming Guo; Wenjun Wang; et al. (Bioresource Technology, 2023)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Quantification of groundwater-borne greenhouse gases (CH4, CO2, N2O) fluxes to an oxbow lake in a subtropical alluvial-lacustrine plain - Yuan Jiang; Yao Du; Xiaoliang Sun; Yamin Deng; Jiawen Xu; Hao Tian; Peng Han; Yiqun Gan; Teng Ma; Yanxin Wang (Applied Geochemistry, 2023)

Degradation of trichloroethylene by double dielectric barrier discharge (DDBD) plasma technology: Performance, product analysis and acute biotoxicity assessment - Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Er-Hong Duan; Meng-Fei Han; Hsing-Cheng Hsi; Ji-Guang Deng (Chemosphere, 2023)

Revealing the response of microbial communities to polyethylene micro(nano)plastics exposure in cold seep sediment - Chunlei Chen; Yinan Deng; Hanghai Zhou; Lijia Jiang; Zhaochao Deng; Jiawang Chen; Xiqiu Han; Dongdong Zhang; Chunfang Zhang (Science of The Total Environment, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

Metabolic engineering and fermentation optimization strategies for producing organic acids of the tricarboxylic acid cycle by microbial cell factories - Shenghu Zhou; Nana Ding; Runhua Han; Yu Deng (Bioresource Technology, 2023)

Short-term effects of asymmetric day and night warming on soil N2O, CO2 and CH4 emissions: A field experiment with an invasive and native plant - Xue Han; Na-Na Yao; Xiao-Jing Wang; Hao-Hui Deng; Hui-Xuan Liao; Sheng-Qi Fan; Bao-Ming Chen (Applied Soil Ecology, 2023)

Editorial: Aquatic microorganism and their response to environment virulence and antimicrobial resistance - Yiqin Deng; Songzhe Fu; Learn-Han Lee; Juan Feng; Jie Huang (Frontiers in Marine Science, 2023)

Hierarchical structure-based joint operations algorithm for global optimization - Gaoji Sun; Rongqing Han; Libao Deng; Chunlei Li; Guoqing Yang (Swarm and Evolutionary Computation, 2023)

The mechanisms of optimal nitrogen conditions to accelerate flowering of Chrysanthemum vestitum under short day based on transcriptome analysis - Qiuling Zhang; Junzhuo Li; Chengyan Deng; Jiaqi Chen; Wenjia Han; Xiuzhen Yang; Zhongman Wang; Silan Dai (Journal of Plant Physiology, 2023)

Efficient utilization of biogenic manganese oxides in bioaugmentation columns for remediation of thallium(I) contaminated groundwater - Liangjing Zhang; Yu Yang; Xiangjian Xu; Sheng Deng; Han Xiao; Xu Han; Fu Xia; Yonghai Jiang (Journal of Hazardous Materials, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Driving factors of soil organic carbon sequestration under straw returning across China's uplands - Chongchong Zhu; Wenhui Zhong; Cheng Han; Huan Deng; Yunbin Jiang (Journal of Environmental Management, 2023)

Fabrication of Cu0-composited CuFe2O4 magnetic nanoparticles on diatomite support for efficient degradation of tetracycline hydrochloride by a Fenton-like system - Shuai Deng; Zhi Guo; Yi-Han Chen; Kang-Ping Cui; Zhao-Gang Ding; Bei Wang; Rohan Weerasooriya; Xing Chen (Journal of Environmental Chemical Engineering, 2023)

Effect of oligosaccharides as lyoprotectants on the stability of curcumin-loaded nanoliposomes during lyophilization - Hanyun Jiang; Yanping Wang; Xiankang Xu; Leiyu Deng; Lifang Feng; Jianzhong Han; Weilin Liu (Food Chemistry, 2023)

Excessive ER-phagy contributes to ochratoxin A-induced apoptosis - Huiqiong Deng; Wenying Chen; Boyang Zhang; Yiwen Zhang; Lingyun Han; Qipeng Zhang; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Effect of extreme temperatures on asthma hospital visits: Modification by event characteristics and healthy behaviors - Shizhou Deng; Azhu Han; Shuyan Jin; Shuang Wang; Jing Zheng; Bin B. Jalaludin; Shakoor Hajat; Wannian Liang; Cunrui Huang (Environmental Research, 2023)

AI-aided multiscale modeling of physiologically-significant blood clots - Yicong Zhu; Changnian Han; Peng Zhang; Guojing Cong; James R. Kozloski; Chih-Chieh Yang; Leili Zhang; Yuefan Deng (Computer Physics Communications, 2023)

Selenium nanoparticles: Properties, preparation methods, and therapeutic applications - Xiang Xiao; Huan Deng; Xue Lin; Ahmed Sameir Mohamed Ali; Angelo Viscardi; Ziwei Guo; Lichun Qiao; Yujie He; Jing Han (Chemico-Biological Interactions, 2023)

An experimental study on the resuspension characteristics of evaporation residues of human exhaled droplets on medical clothing - Han Yu; Chunying Li; Haida Tang; Pengjie Cui; Wenzheng Deng; QianQian Zhang (Building and Environment, 2023)

The Effects of Interface Roughness on the Pull-Out Performance and Failure Characteristics of Tunnel-Type Anchorages in Soft Rock - Yafeng Han; Xinrong Liu; Mingwei Liu; Bin Xu; Zhiyun Deng; Xiaohan Zhou; Gang Zhang; Guoshen Lai (Rock Mechanics and Rock Engineering, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Arbuscular Mycorrhizal Fungi Alter the Interaction Effects Between Bacillus and Rhizobium on Root Morphological Traits of Medicago ruthenica L. - Lu Yu; Hui Zhang; Wantong Zhang; Bing Han; Huakun Zhou; Xinming Lu; Yanfang Deng; Kesi Liu; Xinqing Shao (Journal of Soil Science and Plant Nutrition, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Numerical evaluation of the suitability of the equivalent porous medium model for characterizing the two-dimensional flow field in a fractured geologic medium - Lei Ma; Di Han; Jiazhong Qian; Di Gao; Haichun Ma; Yaping Deng; Xiaoliang Hou (Hydrogeology Journal, 2023)

China’s sponge cities alleviate urban flooding and water shortage: a review - Jie Han; Chaoqi Wang; Shihai Deng; Eric Lichtfouse (Environmental Chemistry Letters, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

Mineralocorticoid Receptor Mediates Cortisol Regulation of Ionocyte Development in Tilapia (Oreochromis mossambicus) - Chien-Yu Wu; Tsung-Han Lee; Deng-Yu Tseng (Fishes, 2023)
Cortisol is the predominant corticosteroid in ray-finned fish since it does not possess the aldosterone synthase necessary to produce specific mineralocorticoids. Cortisol is traditionally believed to function as a fish mineralocorticoid. However, the effects of cortisol are mediated through corticosteroid receptors in other vertebrates, and there is an ongoing debate about whether cortisol acts through the glucocorticoid receptor (GR) or the mineralocorticoid receptor (MR) in teleosts. To investigate this issue, we conducted a study using euryhaline Mozambique tilapia (Oreochromis mossambicus) as the experimental species. The experiment was designed to investigate the effect of cortisol on ionocyte development at both the cellular and gene expression levels in tilapia. We administered exogenous cortisol and receptor antagonists, used immunohistochemistry to quantify ionocyte numbers, and performed real-time PCR to assess the expression of the differentiation factor tumor protein 63 (P63) mRNA, an epidermal stem cell marker. We observed that cortisol increased the number of Na+-K+-ATPase (NKA)-immunoactive ionocytes (increased by 1.6-fold) and promoted the gene expression of P63 mRNA (increased by 1.4-fold). Furthermore, we found that the addition of the mineralocorticoid receptor antagonist Spironolactone inhibited the increase in the number of ionocytes (decreased to the level of the control group) and suppressed the gene expression of P63 (similarly decreased to the level of the control group). We also provided evidence for gr, mr, and p63 localization in epidermal cells. At the transcript level, mr mRNA is ubiquitously expressed in gill sections and present in epidermal stem cells (cells labeled with p63), supporting the antagonism and functional assay results in larvae. Our results confirmed that cortisol stimulates ionocyte differentiation in tilapia through the MR, rather than the GR. Therefore, we provide a new direction for investigating the dual action of osmotic regulation and skin/gill epithelial development in tilapia, which could help resolve previously inconsistent and conflicting findings.

Glucocorticoid Receptor Mediates Cortisol Regulation of Glycogen Metabolism in Gills of the Euryhaline Tilapia (Oreochromis mossambicus) - Chien-Yu Wu; Tsung-Han Lee; Deng-Yu Tseng (Fishes, 2023)
In this study, we investigated the effects of cortisol on the regulation of the glycogen metabolism biomarkers glycogen synthase (GS) and glycogen phosphorylase (GP) in the glycogen-rich cells of the gills of tilapia (Oreochromis mossambicus). In the gills of tilapia, GP, GS, and glycogen were immunocytochemically colocalized in a specific group of glycogen-rich cells adjacent to the gills’ main ionocytes and mitochondria-rich cells. Cortisol plays a vital role in the regulation of physiological functions in animals, including energy metabolism, respiration, immune response, and ion regulation. However, no studies have elucidated the mechanisms regulating cortisol and glycogen-rich cells in the gills. Therefore, we treated tilapia larvae with exogenous cortisol and a glucocorticoid receptor (GR) antagonist to investigate the regulatory mechanisms between cortisol and glycogen-rich cells in the gills. Our results showed that cortisol promoted the expression of gill glycogen phosphorylase isoform (GPGG) mRNA via GR, whereas the GS gene expression remained unaffected. We also found that GR mRNA was colocalized with some glycogen-rich cells in the gills, further confirming our hypothesis that cortisol directly acts on glycogen-rich cells in the gills of tilapia and regulates glycogen metabolism by promoting GPGG mRNA expression.

Simulation of pollutant diffusion in vegetation open channel based on LBM-CA method - Shiyu Wang; Jialin Zhuo; Fengcong Jia; Liuhong Deng; Hongru Wang; Yu Han (Environmental Science and Pollution Research, 2023)

Proximity RNA labeling reveals functions of lncRNA in DNA damage response - Weili Li; Zhongxia Li; Zhiwen Deng; Jie Zhai; Shuzhen Han; Xiangyu Liu (Genome Instability & Disease, 2023)

Effects of instantaneous changes in temperature, light, and salinity on the dynamics of dissolved organic carbon release by Sargassum thunbergii - Zhi-Fang Zhao; Zhong-Jian Huang; Zuo-Deng Sun; Zheng-Yi Liu; Song Qin; Tong Han; Xin-Yu Qi; Xi-Yan Sun; Zhi-Hai Zhong (Marine Pollution Bulletin, 2023)

Microbial community evolution and functional trade-offs of biofilm in odor treatment biofilters - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Guan-Yu Jiang; Meng-Fei Han; Ji-Guang Deng; Hsing-Cheng Hsi (Water Research, 2023)

Finite-time event-triggered sliding mode predictive control of unmanned underwater vehicles without velocity measurements - Xinbin Li; Hongtao Pan; Yingjie Deng; Song Han; Haifeng Yu (Ocean Engineering, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

The construction of defect-rich CoP@CoP@(Co/Ni)2P triple-shell hollow nanospheres with boosted electrocatalytic hydrogen evolution performances over a wide pH range - Han Zhang; Yaqi Wu; Xiaodong Wang; Chunpu Li; Zhenyu Xiao; Yanru Liu; Ying Deng; Zhenjiang Li; Lei Wang (Chemical Engineering Journal, 2023)

Bacterial cellulose-based hydrogel with antibacterial activity and vascularization for wound healing - Lili Deng; Yinjun Huang; Shiyan Chen; Zhiliang Han; Zhengzhe Han; Mengtian Jin; Xiangyang Qu; Baoxiu Wang; Huaping Wang; Song Gu (Carbohydrate Polymers, 2023)

Comparative review on microbial electrochemical technologies for resource recovery from wastewater towards circular economy and carbon neutrality - Shihai Deng; Chaoqi Wang; Huu Hao Ngo; Wenshan Guo; Na You; Hao Tang; Hongbin Yu; Long Tang; Jie Han (Bioresource Technology, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Altered transcriptomic and metabolomic profiles of testicular interstitial ﬂuid during aging in mice - Dayu Han; Jiahui Yao; Wanmei Chen; Jintao Zhuang; Jun Bian; Bin Ouyang; Xiangzhou Sun; Chunhua Deng; Yun Xie; Qiyun Yang (Theriogenology, 2023)

Heavy metal content and health risk assessment of atmospheric particles in China: A meta-analysis - Pengyue Yu; Yongliang Han; Maodi Wang; Zhen Zhu; Zhenglong Tong; XingYuan Shao; Jianwei Peng; Yasir Hamid; Xiaoe Yang; Yaocheng Deng; Ying Huang (Science of The Total Environment, 2023)

It is time to acknowledge coronavirus transmission via frozen and chilled foods: Undeniable evidence from China and lessons for the world - Han Dai; Hao Tang; Wen Sun; Shihai Deng; Jie Han (Science of The Total Environment, 2023)

Tannic acid-assisted prussian blue anchoring on membranes for rapid and recyclable removal of cesium - Jiayu Qin; Linxue Yan; Senjian Han; Xiaonan Yang; Yafei Guo; Long Li; Tianlong Deng (Journal of Water Process Engineering, 2023)

Desorption of cadmium from Fe Cd and recycle of Fe0: Experimental and mechanism study - Junhao Fu; Guanshuo Han; Haisheng Han; Ruohua Liu; Chaozheng Deng; Jianhua Kang; Tong Yue (Journal of Environmental Chemical Engineering, 2023)

A leaching, solvent extraction, stripping, precipitation and calcination process for the recovery of MoO3 and NiO from spent hydrofining catalysts - Yaxing Han; Ji Chen; Yuefeng Deng; Tianchi Liu; Hailian Li (Hydrometallurgy, 2023)

H2 impact on combustion kinetics, soot formation, and NOx emission of hydrocarbon fuel flames - M. Zuhaib Akram; Fanhua Ma; Muhammad Aziz; Yangbo Deng; Han Wu (Fuel, 2023)

Specific protection mechanism of oligosaccharides on liposomes during freeze-drying - Leiyu Deng; Yanping Wang; Hanyun Jiang; Xiankang Xu; Jianzhong Han; Weilin Liu (Food Research International, 2023)

Release of microplastics from breastmilk storage bags and assessment of intake by infants: A preliminary study - Liping Liu; Xue Zhang; Puqi Jia; Shanshan He; Han Dai; Shihai Deng; Jie Han (Environmental Pollution, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

Influence of built environment on outdoor thermal comfort: A comparative study of new and old urban blocks in Guangzhou - Xingdong Deng; Weixiao Nie; Xiaohui Li; Jie Wu; Zhe Yin; Jiejie Han; Haonan Pan; Cho Kwong Charlie Lam (Building and Environment, 2023)

Estimation of high spatial resolution all-weather near-surface air temperature using FY-4A AGRI observations - Hailei Liu; Yaoyao Chen; Qinzhe Han; Xiaobo Deng; Jiazhi Fan; Minzheng Duan; Qihong Huang (Atmospheric Research, 2023)

Molecular Analysis and Sex-specific Response of the Hepcidin Gene in Yellow Perch (Perca Flavescens) Following Lipopolysaccharide Challenge - Xing Lu; Yueh-Chiang Han; Brian S. Shepherd; Ying Xiang; Dong-Fang Deng; Bryan T. Vinyard (Probiotics and Antimicrobial Proteins, 2023)

Methcathinone Increases Visually-evoked Neuronal Activity and Enhances Sensory Processing Efficiency in Mice - Jun Zhou; Wen Deng; Chen Chen; Junya Kang; Xiaodan Yang; Zhaojuan Dou; Jiancheng Wu; Quancong Li; Man Jiang; Man Liang; Yunyun Han (Neuroscience Bulletin, 2023)

Chidamide works synergistically with Dasatinib by inducing cell-cycle arrest and apoptosis in acute myeloid leukemia cells - Mingyang Deng; Han Xiao; Hongling Peng; Huan Yuan; Xiang Xiao; Sufang Liu (Molecular and Cellular Biochemistry, 2023)

One-pot RPA-Cas12a assay for instant and visual detection of Burkholderia pseudomallei - Ling Deng; Xiaoyi He; Ke Liu; Yuanli Li; Han Xia; Hang Qian; Xiaoxue Lu; Xuhu Mao; Yang Xiang (Analytica Chimica Acta, 2023)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals - Zeyu Fan; Xian Zhou; Ziling Peng; Sha Wan; Zhuo Fan Gao; Shanshan Deng; Luling Tong; Wei Han; Xia Chen (Chemosphere, 2023)

Formaldehyde causes an increase in blood pressure by activating ACE/AT1R axis - Shuwei Wang; Qi Han; Zhaolan Wei; Yunyi Wang; Lingfu Deng; Mingqing Chen (Toxicology, 2023)

Exposure to cadmium induced gut antibiotic resistance genes (ARGs) and microbiota alternations of Babylonia areolata - Wang Zhao; Qian Han; Rui Yang; Weigeng Wen; Zhenghua Deng; Huan Li; Zhongming Zheng; Zhenhua Ma; Gang Yu (Science of The Total Environment, 2023)

A novel thermosensitive persulfate controlled-release hydrogel based on agarose/silica composite for sustained nitrobenzene degradation from groundwater - Shuxuan Wu; Sheng Deng; Fu Xia; Xu Han; Tianyu Ju; Han Xiao; Xiangjian Xu; Yu Yang; Yonghai Jiang; Beidou Xi (Journal of Hazardous Materials, 2023)

Comparative life cycle greenhouse gas emissions assessment of battery energy storage technologies for grid applications - Xiaoqu Han; Yanxin Li; Lu Nie; Xiaofan Huang; Yelin Deng; Junjie Yan; Dimitrios-Sotirios Kourkoumpas; Sotirios Karellas (Journal of Cleaner Production, 2023)

Experimental study on the redistribution law of heavy metals in sludge disintegration - Juanjuan Zhao; Feng Deng; Han Zhang; Wenwen Gu; Huidan Chen; Siqi Huang (Journal of Environmental Management, 2023)

Identification of mare milk adulteration with cow milk by liquid chromatography-high resolution mass spectrometry based on proteomics and metabolomics approaches - Zhongyuan Ji; Junyu Zhang; Chunxia Deng; Zhisheng Hu; Qijing Du; Tongjun Guo; Jun Wang; Rongbo Fan; Rongwei Han; Yongxin Yang (Food Chemistry, 2023)

Survey of the biogenic amines in craft beer from the Chinese market and the analysis of the formation regularity during beer fermentation - Chenyu Li; Xiaoyu Han; Bing Han; Huan Deng; Tianyang Wu; Xiaoxuan Zhao; Weidong Huang; Jicheng Zhan; Yilin You (Food Chemistry, 2023)

Structural degradation and uptake of resveratrol-encapsulated liposomes using an in vitro digestion combined with Caco-2 cell absorption model - Xiankang Xu; Mengmeng Tian; Leiyu Deng; Hanyun Jiang; Jianzhong Han; Chenxi Zhen; Lewei Huang; Weilin Liu (Food Chemistry, 2023)

Fluorescence sensing platform for Cronobacter sakazakii based on the cationic metal-organic frameworks modified upconversion nanoparticles - Mingyuan Yin; Zedan Wang; Peijuan Xie; Lirong Han; Linsen Li; Haiyan Wang; Xiaoqiang Qiao; Qiliang Deng (Food Control, 2023)

Achieving superior nitrogen removal in an air-lifting internal circulating reactor for municipal wastewater treatment: Performance, kinetic analysis, and microbial pathways - Yi Han; Xiejuan Lu; Yang Liu; Yangfan Deng; Feixiang Zan; Juan Mao; Tianwei Hao; Cheng Cao; Xiaohui Wu (Bioresource Technology, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Deep learning for visual recognition and detection of aquatic animals: A review - Juan Li; Wenkai Xu; Limiao Deng; Ying Xiao; Zhongzhi Han; Haiyong Zheng (Reviews in Aquaculture, 2023)
The ocean is an important ecosystem, and aquatic animals play an important role in the biological world, especially in aquaculture. How to accurately and intelligently recognise and detect aquatic animals is one of the urgent problems in the field of underwater biological detection. The wide applications of artificial intelligence (AI), especially deep learning (DL), provide new opportunities and challenges for the efficient and intelligent exploration of aquatic animals. DL has been widely used in the visual recognition and detection of terrestrial animals, but it is in the early stages of use for aquatic animals due to the complexity of underwater environment and the difficulty of data acquisition. Here, this article reviews the current application status of DL for aquatic animals, potential challenges and future directions. The key advances of DL algorithms applied to the visual recognition and detection of aquatic animals are generalised, including datasets, algorithms and performance. The applications of DL are summarised in aquatic animals, including image detection, video detection, species classification, biomass estimation, behaviour analysis and food safety. Furthermore, the challenges are summed up and classified in the object recognition and detection domain for aquatic animals. Finally, further research direction is discussed and the conclusions are drawn. The key advances of DL in the recognition and detection of aquatic animals will help to further excavate and extend the application of DL in the field of marine biological exploration.

Changes in China’s food security driven by nutrition security and resource constraints - Ze Han; Xinqi Zheng; Lingling Hou; Nan Xiao; Xiangzheng Deng (Environment, Development and Sustainability, 2023)

Identification of Novel Mutations in the Tyrosinase Gene (TYR) Associated with Pigmentation in Chinese Giant Salamanders (Andrias davidianus) - Jie Deng; Mengdi Han; Hongying Ma; Han Zhang; Hongxing Zhang; Hu Zhao; Jia Li; Wei Jiang (Fishes, 2023)
The Chinese giant salamander (Andrias davidianus), an endangered amphibian species endemic to China, has been previously evaluated with regards to its phyletic evolution, zooecology, and ethology, but molecular mechanisms underlying its skin pigmentation remain unknown. Herein, a skin transcriptome database of different colored salamanders was established using RNA-seq, and a total of 47,911 unigenes were functionally annotated. Among these unigenes, a total of 1252 differentially expressed genes (DEGs) were annotated in the seven public databases, and six DEGs were validated by qPCR between five different skin colors and eight tissues. The results showed that TYR, TYRP1, and ASIP were significantly differentially expressed between different body colors, while TYR, TYRP1, and DCT were highly expressed in skin tissue. The full-length complementary DNA of TYR was cloned and analyzed between normal and yellow phenotypes. Three nucleotide sequence deletion sites were identified in the coding region of TYR, leading to premature termination of transcription and translation in yellow individuals. Our study provides useful data for the further study of the molecular mechanisms of melanin formation, and a valuable reference for the breeding of specific skin colors in other salamanders.

Use of nanoparticle-coated bacteria for the bioremediation of organic pollution: A mini review - Jin-Ru Feng; Qing-Xin Deng; Shang-Kun Han; Hong-Gang Ni (Chemosphere, 2023)

Dissociation and removal of alkali and alkaline earth metals from sewage sludge flocs during separate and assisted thermal hydrolysis - Minghao Jin; Huan Liu; Hongping Deng; Han Xiao; Shuai Liu; Hong Yao (Water Research, 2023)

Experiment and evaluation model of liner design for renewal of deteriorated reinforced concrete pipes utilizing cured-in-place-pipe technology - Zhao Yahong; Huang Sheng; Ma Baosong; Zeng Cong; Yan Xuefeng; Ti Zhongsen; Liu Han; Deng Caiying (Tunnelling and Underground Space Technology, 2023)

Two haplotype-resolved, gap-free genome assemblies for Actinidia latifolia and Actinidia chinensis shed light on the regulatory mechanisms of vitamin C and sucrose metabolism in kiwifruit - Xue Han; Yilin Zhang; Qiong Zhang; Ni Ma; Xiaoying Liu; Wenjing Tao; Zhiying Lou; Caihong Zhong; Xing Wang Deng; Dawei Li; Hang He (Molecular Plant, 2023)

Water hazard detection: A 20-year review - Xiaodong Guo; Jizhou Han; Jingyu Li; Zhoubo Wang; Zhenhai Zhang; Xiao Kang; Wei Zhu; Hongbin Deng (Journal of Terramechanics, 2023)

Multiscale fractures integrated equivalent porous media method for simulating flow and solute transport in fracture-matrix system - Lei Ma; Di Gao; Jiazhong Qian; Di Han; Kun Xing; Haichun Ma; Yaping Deng (Journal of Hydrology, 2023)

Altered microbial P cycling genes drive P availability in soil after afforestation - Ruochen Zhi; Jian Deng; Yuling Xu; Miaoping Xu; Shuohong Zhang; Xinhui Han; Gaihe Yang; Chengjie Ren (Journal of Environmental Management, 2023)

Impact of elderly gastrointestinal alterations on gastric emptying and enzymatic hydrolysis of skim milk: An in vitro study using a dynamic stomach system - Ping Zhang; Shahid Iqbal; Renpan Deng; Xu Duan; Huaxin Han; Xiao Dong Chen; Peng Wu (Food Chemistry, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Deciphering biochar compost co-application impact on microbial communities mediating carbon and nitrogen transformation across different stages of corn development - Ayodeji Bello; Wanying Liu; Nuo Chang; Kehinde Olajide Erinle; Liting Deng; Ugochi Uzoamaka Egbeagu; Busayo Joshua Babalola; Han Yue; Yu Sun; Zimin Wei; Xiuhong Xu (Environmental Research, 2023)

Facilely full-end-capping engineering promotes high-performance organic solar cells with simultaneously improved efficiency and stability - Youhui Zhang; Jiawei Deng; Qilong Mao; Sang Young Jeong; Xuexiang Huang; Lifu Zhang; Byongkyu Lee; Bin Huang; Han Young Woo; Changduk Yang; Junying Xu; Feiyan Wu; et al. (Chemical Engineering Journal, 2023)

A novel method based on hydrodynamic cavitation to effectively remove NO2 - Liguo Song; Jingang Yang; Hao Sui; Yuhang Wei; Chengqi Deng; Lingrun Meng; Feng Guo; Zhitao Han; Xinxiang Pan; Dionysios D. Dionysiou (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

Uplift history of the Northern Tianshan constrained from the inversion of river profiles - Runing Hou; Mei Liu; Ningsheng Chen; MingFeng Deng; Shufeng Tian; Yujia Li; Huayong Ni; Zheng Han (International Journal of Earth Sciences, 2023)

Symbiont-screener: A reference-free tool to separate host sequences from symbionts for error-prone long reads - Mengyang Xu; Lidong Guo; Yanwei Qi; Chengcheng Shi; Xiaochuan Liu; Jianwei Chen; Jinglin Han; Li Deng; Xin Liu; Guangyi Fan (Frontiers in Marine Science, 2023)
Metagenomic sequencing facilitates large-scale constitutional analysis and functional characterization of complex microbial communities without cultivation. Recent advances in long-read sequencing techniques utilize long-range information to simplify repeat-aware metagenomic assembly puzzles and complex genome binning tasks. However, it remains methodologically challenging to remove host-derived DNA sequences from the microbial community at the read resolution due to high sequencing error rates and the absence of reference genomes. We here present Symbiont-Screener ( https://github.com/BGI-Qingdao/Symbiont-Screener ), a reference-free approach to identifying high-confidence host’s long reads from symbionts and contaminants and overcoming the low sequencing accuracy according to a trio-based screening model. The remaining host’s sequences are then automatically grouped by unsupervised clustering. When applied to both simulated and real long-read datasets, it maintains higher precision and recall rates of identifying the host’s raw reads compared to other tools and hence promises the high-quality reconstruction of the host genome and associated metagenomes. Furthermore, we leveraged both PacBio HiFi and nanopore long reads to separate the host’s sequences on a real host-microbe system, an algal-bacterial sample, and retrieved an obvious improvement of host assembly in terms of assembly contiguity, completeness, and purity. More importantly, the residual symbiotic microbiomes illustrate improved genomic profiling and assemblies after the screening, which elucidates a solid basis of data for downstream bioinformatic analyses, thus providing a novel perspective on symbiotic research.

Spatiotemporal variation of irrigation water requirements for grain crops under climate change in Northwest China - Jiaxin Zhang; Mingjiang Deng; Yuping Han; Huiping Huang; Tao Yang (Environmental Science and Pollution Research, 2023)

Lake dynamics in Tibetan Plateau during 1990–2020 and exploratory factor analyses using Google Earth Engine - Zhiyuan Li; Fan Deng; Jie Gong; Longwei Xiang; Yang Han; Peixin Zheng; Enling Zhao (Environmental Science and Pollution Research, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

An intelligent measurement scheme for basic characters of fish in smart aquaculture - Chuang Yu; Zhuhua Hu; Bing Han; Yutong Dai; Yaochi Zhao; Yingjun Deng (Computers and Electronics in Agriculture, 2023)

Effects of hyperosmotic stress on the intestinal microbiota, transcriptome, and immune function of mandarin fish (Siniperca chuatsi) - Haofeng Ouyang; Niuniu Deng; Jiachang Xu; Jingjun Huang; Chong Han; Dingrui Liu; Shiyan Liu; Baohua Yan; Linqiang Han; Shuisheng Li; Guifeng Li; Jin Zhang; et al. (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Suggestion on further strengthening ultra-low emission standards for PM emission from coal-fired power plants in China - Jianguo Deng; Shumin Wang; Jiawei Zhang; Yi Zhang; Jingkun Jiang; Yongzheng Gu; Tao Han; Lei Feng; Jian Gao; Lei Duan (Journal of Environmental Sciences, 2023)

Asthma triggered by extreme temperatures: From epidemiological evidence to biological plausibility - Azhu Han; Shizhou Deng; Jiarui Yu; Yali Zhang; Bin Jalaludin; Cunrui Huang (Environmental Research, 2023)

Cruise observation of the marine atmosphere and ship emissions in South China Sea: Aerosol composition, sources, and the aging process - Qibin Sun; Baoling Liang; Mingfu Cai; Yongyun Zhang; Hengjia Ou; Xue Ni; Xi Sun; Bo Han; Xuejiao Deng; Shengzhen Zhou; Jun Zhao (Environmental Pollution, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Ultrathin metal organic framework nanosheets with rich defects for enhanced fluoride removal - Junyu Su; Maosen Yuan; Lu Han; Hongxia Deng; Jiahao Chang; Yuting Zhuang; Jinyi Wang; Yue Zhang (Chemical Engineering Journal, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

Optimization of clofibrate with natural product sesamol for reducing liver injury induced by acetaminophen - Chuchu Han; Linyang Zhang; Yuxin Hua; Haitao Liu; Jiping Liu; Yongheng Shi; Xiaoping Wang; Wei Wang; Yi Jiang; Huawei Zhang; Chong Deng; Yundong Xie; et al. (Medicinal Chemistry Research, 2023)

Predicting Sex-Related Transcripts in the Chinese Giant Salamander (Andrias davidianus): A Transcriptomics Study, Selection Gender for Preservation, Breeding and Reintroduction - Hu Zhao; Jiqin Huang; Cheng Fang; Hongying Ma; Han Zhang; Jie Deng; Wei Jiang; Fei Kong; Hongxing Zhang; Hong Liu; Qijun Wang (Fishes, 2022)
The Chinese giant salamander (Andrias davidianus) is the biggest extant and endangered amphibian, which has an incongruous sex ratio during the artificial breeding process and is sex indistinguishable in appearance. The sex development mechanism of this rare species thus needs to be explored. We therefore conducted this study to explore the molecular mechanisms of sex hallmarks or gonad maintenance genes for CGS. In this study, we sequenced and analyzed the sexually mature male and female gonads of Chinese giant salamanders (CGSs) using RNA-seq technology and found a total of 15,063 differentially expressed genes (DEGs) in the testicular and ovarian tissues, of which 7973 (52.93%) were expressed in testicular and 7090 (47.07%) in ovarian tissues. Thirteen gonad DEGs were selected based on gene expression abundance and quantified in the muscle and skin tissues of both male and female CGSs. The results showed that these 13 DEGS, out of the 20 analyzed DEGs, were expressed in both the muscle and skin tissues and only two of them (Bmp15 and ZP3) were consistent in the muscle and skin compared to the gonads of CGSs of the two sexes. Overall, our study should provide an important reference for the sex-characteristics-related genes in this type of species, shedding new light on future research on this topic.

Sex-related differences in safety profiles, pharmacokinetics and tissue distribution of sinomenine hydrochloride in rats - Hong Huang; Er-Bing Zhang; Ou-Yang Yi; Han Wu; Guiming Deng; Yu-Ming Huang; Wen-Liang Liu; Jian-Ye Yan; Xiong Cai (Archives of Toxicology, 2022)

Geology, fluid inclusion and H–O–C isotope geochemistry of the Doranasai gold deposit, Chinese Altai: implications for ore genesis - Xun Li; Xiaohua Deng; Wenxiang Liu; Abulimiti Aibai; Xi Chen; Shen Han; Yanshuang Wu; Yanjing Chen (International Journal of Earth Sciences, 2022)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

Lignans from Bupleurum marginatum and their antioxidant activity - Jian Zhou; Xin He; Rongjin Sun; Zhenlong Yu; Chao Wang; Sa Deng; Baojing Zhang; Shanshan Huang; Chunhui Han; Dawei Li (Natural Product Research, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

Association of SNPs in zinc transporter genes on seminal plasma zinc levels in humans - Peipei Deng; Xiaoke Han; Jing Ma; Xin Huang; Bo Sun; Yasong Geng; Bo Zheng; Shusong Wang (BioMetals, 2022)

Distribution characteristics of microplastics in the soil of mangrove restoration wetland and the effects of microplastics on soil characteristics - Bo Hu; Peiyong Guo; Siyu Han; Yifan Jin; Yiting Nan; Jun Deng; Junming He; Yaqing Wu; Sijia Chen (Ecotoxicology, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Influence of Block form on the Shear Behaviour of Soft Soil–Rock Mixtures by 3D Block Modelling Approaches - Han Zhang; Daniela Boldini; Lehua Wang; Huafeng Deng; Chang Liu (Rock Mechanics and Rock Engineering, 2022)
The influence of block forms on the shear behaviour of soil–rock mixtures with soft blocks (soft S–RMs) can be efficiently investigated by the discrete element method (DEM) on the basis of accurate 3D models accounting for the block breakage. This paper proposes a novel modelling approach, based on the spherical harmonics series, for the generation of 3D block geometries with different forms but same convexity and angularity. An already existing non-overlapping modelling approach was improved, characterized by a reduced computational cost, for the set-up of 3D block DEM models accounting for the block breakage. A number of soft S–RM DEM samples, subjected to numerical direct shear tests, were generated to analyze the influence of block forms and volumetric block proportion VBP on the mesoscopic and macroscopic behaviours. The results showed that the breakage degree is maximum for the spheroidal blocks, followed by the oblate, prolate and blade ones, due to the combined influence of the block frictional sliding and rotation. The shear strength of soft S–RMs is mainly controlled by the block interlocking and breakage, being maximum in the case of spheroidal block samples when the applied normal stress is low and in the case of prolate and blade ones for a high normal stress. It was found that a nonlinear Mohr–Coulomb criterion can provide a good description of the shear strength envelope of soft S–RMs. Soft S–RMs are characterized by a higher friction angle if composed by spheroidal and prolate blocks when the VBP is 40%, due to their elevated block interlocking, and in the case of prolate and blade blocks when the VBP is 60% at the higher normal stress, due to their lower block breakage degree.

Building a predictive model to identify clinical indicators for COVID-19 using machine learning method - Xinlei Deng; Han Li; Xin Liao; Zhiqiang Qin; Fan Xu; Samantha Friedman; Gang Ma; Kun Ye; Shao Lin (Medical & Biological Engineering & Computing, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Impacts of Human Activities and Climate Change on Water Storage Changes in Shandong Province, China - Longyun Deng; Zhen Han; Weixing Pu; Rong Bao; Zheye Wang; Quanyuan Wu; Jianmin Qiao (Environmental Science and Pollution Research, 2022)

Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review - Meng-Fei Han; Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Zhuo-Wei Cheng; Ke Feng; Miao-Miao Qu; Jian-Meng Chen; Ji-Guang Deng; Hsing-Cheng Hsi (Critical Reviews in Environmental Science and Technology, 2022)

Harmful Effects of Inorganic Mercury Exposure on Kidney Cells: Mitochondrial Dynamics Disorder and Excessive Oxidative Stress - Biqi Han; Zhanjun Lv; Xuemin Han; Siyu Li; Bing Han; Qingyue Yang; Xiaoqiao Wang; Pengfei Wu; Jiayi Li; Ning Deng; Zhigang Zhang (Biological Trace Element Research, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Ameliorating Effect of Umbilical Cord Mesenchymal Stem Cells in a Human Induced Pluripotent Stem Cell Model of Dravet Syndrome - Huifang Zhao; Shuai Li; Lang He; Feng Tang; Xiaobo Han; Weiyue Deng; Zuoxian Lin; Rongqi Huang; Zhiyuan Li (Molecular Neurobiology, 2022)

MicroRNA-451a attenuates angiotensin II–induced cardiac fibrosis and inflammation by directly targeting T-box1 - Hao-Yuan Deng; Ze-Yin He; Zhi-Chao Dong; Yun-Long Zhang; Xiao Han; Hui-Hua Li (Journal of Physiology and Biochemistry, 2022)

Progressive multifocal leukoencephalopathy and peripheral neuropathy in a patient with Good’s syndrome - Qinqin Deng; Zhaofen Yan; Yujiao Yang; Jing Wang; Yixian Han; Xing Feng; Minghui Wang; Liping Zhang; Mengyang Wang (Journal of NeuroVirology, 2022)

Back analysis of shear strength parameters for progressive landslides: case study of the Caifengyan landslide, China - Shi Zuo; Lianheng Zhao; Dongping Deng; Zheng Han; Biao Zhao; Zhigang Zhao (Bulletin of Engineering Geology and the Environment, 2022)

Behavior of offshore dike using non-uniform geotextile mats on clay-overlaying-sand soil deposits - Mi Zhou; Huiqi Deng; Zejun Han; Xiaoliang Wang; Xihong Zhang; Huihui Zhao (Marine Georesources & Geotechnology, 2021)

A Combined Remediation Strategy of Arsenic and Cadmium in the Paddy Soil of Polymetallic Mining Areas - Longyong Lin; Runliang Zhu; Zhaohui Li; Cunliang Han; Weiyu Li; Yirong Deng (Bulletin of Environmental Contamination and Toxicology, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Spartina alterniflora saltmarsh soil organic carbon properties and sources in coastal wetlands - Jin-e Liu; Dailan Deng; Caiyu Zou; Ruiming Han; Yue Xin; Zihao Shu; Li-min Zhang (Journal of Soils and Sediments, 2021)

Stenotrophomonas strain CPCC 101271, an intestinal lifespan-prolonging bacterium for Caenorhabditis elegans that assists in host resistance to “Bacillus nematocida” colonization - Rui Han; Yu Wang; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)
The soil-dwelling, opportunistic pathogenic bacterium "Bacillus nematocida" B16 exhibits strong killing activities against a variety of pathogenic nematodes via a “Trojan horse” mechanism that can kill worm species like Caenorhabditis elegans . The bacterial strain CPCC 101271 was previously isolated from the intestines of C. elegans that were recovered from natural habitats and can serve as a probiotic for C. elegans , while also assisting in resistance to infection by the pathogenic strain B16. In this study, the lifespan of C. elegans fed with strain CPCC 101271 cells was extended by approximately 40% compared with that of worms fed with Escherichia coli OP50 cells. In addition, the colonization of C. elegans by the pathogenic bacterium "B. nematocida" B16 was inhibited when pre-fed with strain CPCC 101271. Metagenomic sequence analysis of intestinal microbiota of C. elegans fed with strain CPCC 101271 and infected with B16 revealed that pre-feeding worms with CPCC 101271 improved the diversity of the intestinal bacteria. Moreover, community structure significantly varied in coordination with Stenotrophomonas spp. and Bacillus spp. abundances when competition between strains CPCC 101271 and B16 was evaluated. In conclusion, the nematode microbiota strain CPCC 101271 assisted in its host resistance to colonization by the pathogen "Bacillus nematocida" and can also promote life span-prolongation in C. elegans. These results underscore that understanding the interactions between C. elegans microbiota and pathogens can provide new insights into achieving effective biological control of agricultural pests.

The protective effect of hydrogen-rich water on rats with type 2 diabetes mellitus - Mengna Zheng; Han Yu; Yong Xue; Tong Yang; Qiufen Tu; Kaiqing Xiong; Daihua Deng; Lei Lu; Nan Huang (Molecular and Cellular Biochemistry, 2021)

Sum of High-Risk Gene Mutation (SHGM): A Novel Attempt to Assist Differential Diagnosis for Adrenocortical Carcinoma with Benign Adenoma, Based on Detection of Mutations of Nine Target Genes - Guo-Yang Zheng; Xue-Bin Zhang; Han-Zhong Li; Yu-Shi Zhang; Jian-Hua Deng; Xing-Cheng Wu (Biochemical Genetics, 2021)
There has been no research on applying gene detection to differential diagnosis of adrenocortical carcinoma (ACC). We attempted to explore a novel auxiliary method for differential diagnosis between ACC with benign adrenocortical adenoma (ACA), based on mutations of target genes in tissues. Nine genes were chosen as target genes, including TP53, CTNNB1, ARMC5, PRKAR1A, ZNRF3, RB1, APC, MEN1, and RPL22 . Exons sequencing of target genes were performed in 98 cases of tissue samples by FastTarget technology, including 41 ACC tissues, 32 ACA tissues, and 25 normal adrenal gland tissues. Significant mutations were detected and identified, and the clinical information was collected, for further comparative analysis and application to assist differential diagnosis of ACC. We identified 132 significant gene mutations and 227 significant mutation sites in 37 ACC tissues, much more than ACA and normal adrenal gland tissues. Mutation rates of 6 genes in ACC tissues were obviously higher than ACA tissues, including ZNRF3, ARMC5, TP53, APC, RB1, and PRKAR1A , regarded as high-risk genes. The sum of mutated high-risk genes detected in each sample was denominated sum of high-risk gene mutation (SHGM), and the rates of SHGM > 0 and SHGM > 1 in ACC tissues were 73.0% and 62.2%, respectively, both obviously higher than those in ACA tissues, with significant statistic differences. Especially for 8 cases of ACC with diameter 0 and SHGM > 1 were found in 6 samples (75%) and 4 samples (50%), respectively. However, no relevance was found between SHGM and clinical characteristics of ACC. We identified 6 high-risk genes in ACC tissues, with significantly higher mutation rates than ACA or normal adrenal gland tissues. The sum of mutated high-risk genes detected in ACC tissues was denominated SHGM, which was potential to assist the differential diagnosis of ACC with ACA, especially for the small-size ACC.

Effects of diethyl aminoethyl hexanoate on the physiology and selenium absorption of grape seedlings - Lei Liu; Jiaxi Han; Lili Deng; Huixuan Zhou; Yuhui Bie; Qianhe Jing; Lijin Lin; Jin Wang; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Over-expression of Fgf8 in cardiac neural crest cells leads to persistent truncus arteriosus - Aijuan Tian; Shangqi Wang; Haoru Wang; Nan Li; Han Liu; Hailing Zhou; Xiaoyan Chen; Xuena Liu; Jiamin Deng; Jing Xiao; Chao Liu (Journal of Molecular Histology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Regulating CH4, N2O, and NO emissions from an alkaline paddy field under rice–wheat rotation with controlled release N fertilizer - Ting Lan; Heng Zhang; Yong Han; Ouping Deng; Xiaoyan Tang; Ling Luo; Jian Zeng; Guangdeng Chen; Changquan Wang; Xuesong Gao (Environmental Science and Pollution Research, 2021)

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

Characteristics of plant growth–promoting rhizobacteria SCPG-7 and its effect on the growth of Capsicum annuum L. - Yajie Han; Shengxue Liu; Fulong Chen; Xiaolin Deng; Zhuang Miao; Zhansheng Wu; Bang-Ce Ye (Environmental Science and Pollution Research, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Comparative phosphoproteomic analysis of BR-defective mutant reveals a key role of GhSK13 in regulating cotton fiber development - Lingling Wang; Han Cheng; Fangjie Xiong; Shuya Ma; Lei Zheng; Yun Song; Kexuan Deng; Huanhuan Wu; Fuguang Li; Zuoren Yang (Science China Life Sciences, 2020)

A Novel Method for Simultaneous Removal of NO and SO2 from Marine Exhaust Gas via In-Site Combination of Ozone Oxidation and Wet Scrubbing Absorption - Zhitao Han; Tianyu Zou; Junming Wang; Jingming Dong; Yangbo Deng; Xinxiang Pan (Journal of Marine Science and Engineering, 2020)
The stringent international regulations on marine emission abatement have exerted a huge push on the development of marine desulfurization and denitrification technologies. However, for the traditional vessels driven by large two-stroke diesel engines, simultaneous removal of NOx and SO2 is still a big challenge at present. Here, a one-stage ozone oxidation combined with in-situ wet scrubbing for simultaneous removal of NO and SO2 is proposed. A series of experiments were performed based on a bench-scale reaction system. The results showed that in-situ wet scrubbing could effectively decrease flue gas temperature, and then suppress the thermal decomposition of ozone, which was beneficial for improve oxidant utilization. Meanwhile, the in-situ combination of ozone injection and wet scrubbing was in favor of improving the selectivity oxidation of NO over SO2 by ozone, which was possibly due to the high aqueous solubility of SO2 in water. Aiming to reduce the electric power consumption by an ozone generating system, O3/NO molar ratio was kept as low as possible. A complete removal of SO2 and a high NOx removal efficiency could be achieved through the introduction of other oxidative additives in scrubbing solution. This integrated system designed for marine application was of great significance.

Transient receptor potential ankyrin 1 contributes to the ATP-elicited oxidative stress and inflammation in THP-1-derived macrophage - Chao Tian; Xiaobo Han; Lang He; Feng Tang; Rongqi Huang; Zuoxian Lin; Shuai Li; Sihao Deng; Junjie Xu; Hualin Huang; Huifang Zhao; Zhiyuan Li (Molecular and Cellular Biochemistry, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Model test and numerical simulation on the dynamic stability of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Jinhui Liu; Yiliang Tu (Earthquake Engineering and Engineering Vibration, 2020)

Depletion of florfenicol and florfenicol amine in eggs of laying hens and growing pullets after oral administration - Xia Li; Lu Chen; Hui Yue; Hua Feng; Enmin Xu; Xiuli Wei; Xiaoli Han; Ligang Deng; Zengmei Li (Food Additives & Contaminants: Part A, 2020)

Bacterial community composition in soils covered by different vegetation types in the Yancheng tidal marsh - Jie Fang; Yongcui Deng; Rongxiao Che; Cheng Han; Wenhui Zhong (Environmental Science and Pollution Research, 2020)

Coupled data assimilation and parameter estimation in coupled ocean–atmosphere models: a review - Shaoqing Zhang; Zhengyu Liu; Xuefeng Zhang; Xinrong Wu; Guijun Han; Yuxin Zhao; Xiaolin Yu; Chang Liu; Yun Liu; Shu Wu; Feiyu Lu; Mingkui Li; et al. (Climate Dynamics, 2020)

Cumulative damage evolution and failure modes of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Yiliang Tu; Jun Gu (Arabian Journal of Geosciences, 2020)

Incidence and Clinical Features of TRPV4-Linked Axonal Neuropathies in a USA Cohort of Charcot–Marie–Tooth Disease Type 2 - Sheng Deng; Shawna M. E. Feely; Yong Shi; Hong Zhai; Luna Zhan; Teepu Siddique; Han-Xiang Deng; Michael E. Shy (NeuroMolecular Medicine, 2020)

Fungal community succession under influence of biochar in cow manure composting - Xin Jiang; Liting Deng; Qingxin Meng; Yu Sun; Yue Han; Xiaotong Wu; Siyuan Sheng; Haifeng Zhu; Bello Ayodeji; Ugochi Uzoamaka Egbeagu; Xiuhong Xu (Environmental Science and Pollution Research, 2020)

Model test on the bearing behaviors of the tunnel-type anchorage in soft rock with underlying weak interlayers - Yafeng Han; Xinrong Liu; Dongliang Li; Yiliang Tu; Zhiyun Deng; Dongshuang Liu; Xiangchao Wu (Bulletin of Engineering Geology and the Environment, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Isorhynchophylline enhances Nrf2 and inhibits MAPK pathway in cardiac hypertrophy - Yongtao Zhang; Yuqian Cui; Shuai Dai; Wei Deng; Hao Wang; Weidong Qin; Hongna Yang; Han Liu; Jinfeng Yue; Dawei Wu; Jing Wang; Haipeng Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Photocatalytic degradation of dye by Ag/TiO2 nanoparticles prepared with different sol–gel crystallization in the presence of effluent organic matter - Hongyu Deng; Huan He; Shijie Sun; Xintong Zhu; Dongxu Zhou; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Science and Pollution Research, 2019)

Relevance of number and physiological status of conspecifics in preventing stress-induced decreases in newly proliferated cells and neuroblasts - Li-Han Sun; Wen-Yu Tzeng; Yi-Han Liao; Wen-Ting Deng; Chianfang G. Cherng; Lung Yu (Psychopharmacology, 2019)

Comparative transcriptome analysis to identify candidate genes related to chlorogenic acid biosynthesis in Eucommia ulmoides Oliv. - Jing Ye; Wenjing Han; Peng Deng; Yangyang Jiang; Minhao Liu; Long Li; Zhouqi Li (Trees, 2019)

Morphology, trace elements, and geochronology of zircons from monzogranite in the Northeast Xing’an Block, northeastern China: constraints on the genesis of the host magma - Changzhou Deng; Guangyi Sun; Deyou Sun; Jinsheng Han; Dongguang Yang; Zongyuan Tang (Mineralogy and Petrology, 2019)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

ULK1 affects cell viability of goat Sertoli cell by modulating both autophagy and apoptosis - Jing Pang; Le Han; Zifei Liu; Jian Zheng; Jie Zhao; Kaiping Deng; Feng Wang; Yanli Zhang (In Vitro Cellular & Developmental Biology - Animal, 2019)

An experimental study of the impacts of solar radiation and temperature on mercury emission from different natural soils across China - Han Xie; Maodian Liu; Yipeng He; Huiming Lin; Chenghao Yu; Chunyan Deng; Xuejun Wang (Environmental Monitoring and Assessment, 2019)

Geospatial relation captioning for high-spatial-resolution images by using an attention-based neural network - Jie Chen; Yarong Han; Li Wan; Xing Zhou; Min Deng (International Journal of Remote Sensing, 2019)

Integrated transcriptomic and phytochemical analyses provide insights into characteristic metabolites variation in leaves of 1-year-old grafted tea (Camellia sinensis) - Jieyun Han; Mengqian Lu; Biying Zhu; Rangjian Wang; Xiaochun Wan; Wei-Wei Deng; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2019)

Autophagy mediates the secretion of macrophage migration inhibitory factor from cardiomyocytes upon serum-starvation - Jimin Wu; Xiangning Deng; Juan Gao; Wei Gao; Han Xiao; Xinyu Wang; Youyi Zhang (Science China Life Sciences, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

A Density-Changing Centrifugation Method for Efficient Separation of Free Drugs from Drug-Loaded Particulate Delivery Systems - Lu Han; Hongyan Zhan; Xun Sun; Zhi-Rong Zhang; Li Deng (The AAPS Journal, 2019)

Simulated microgravity inhibits the viability and migration of glioma via FAK/RhoA/Rock and FAK/Nek2 signaling - Banglian Deng; Rongrong Liu; Xin Tian; Zucheng Han; Jun Chen (In Vitro Cellular & Developmental Biology - Animal, 2019)

Identification of phosphorylated proteins in response to salt stress in wheat embryo and endosperm during seed germination - X. Luo; C. Han; X. Deng; D. Zhu; Y. Liu; Y. Yan (Cereal Research Communications, 2019)

Significantly increased amino acid accumulation in a novel albino branch of the tea plant (Camellia sinensis) - Mengqian Lu; Jieyun Han; Biying Zhu; Huiyan Jia; Tianyuan Yang; Rangjian Wang; Wei-Wei Deng; Zheng-Zhu Zhang (Planta, 2019)

Methylococcaceae are the dominant active aerobic methanotrophs in a Chinese tidal marsh - Yongcui Deng; Qian Gui; Marc Dumont; Cheng Han; Huan Deng; Juanli Yun; Wenhui Zhong (Environmental Science and Pollution Research, 2019)

AdipoRon, an adiponectin receptor agonist, attenuates cardiac remodeling induced by pressure overload - Ning Zhang; Wen-Ying Wei; Hai-Han Liao; Zheng Yang; Can Hu; Sha-sha Wang; Wei Deng; Qi-Zhu Tang (Journal of Molecular Medicine, 2018)

Development mechanism for the landslide at Xinlu Village, Chongqing, China - Lianheng Zhao; Shi Zuo; Dongping Deng; Zheng Han; Biao Zhao (Landslides, 2018)

Protective Effects of Quercetin Against Cadmium Chloride-Induced Oxidative Injury in Goat Sperm and Zygotes - Tingchao Mao; Chengquan Han; Biao Wei; Lu Zhao; Qing Zhang; Ruizhi Deng; Jun Liu; Yan Luo; Yong Zhang (Biological Trace Element Research, 2018)

Gallaecimonas mangrovi sp. nov., a novel bacterium isolated from mangrove sediment - Wei-Yan Zhang; Ye Yuan; Deng-Quan Su; Xiao-Ping He; Shuai-Bo Han; Slava S. Epstein; Shan He; Min Wu (Antonie van Leeuwenhoek, 2018)

The interface interaction behavior between E. coli and two kinds of fibrous minerals - Qunwei Dai; Linbao Han; Jianjun Deng; Yulian Zhao; Zheng Dang; Daoyong Tan; Faqin Dong (Environmental Science and Pollution Research, 2018)

Chrysotile and rock wool fibers induce chromosome aberrations and DNA damage in V79 lung fibroblast cells - Yan Cui; Ji Ma; Wei Ye; Zhixia Han; Faqin Dong; Jianjun Deng; Qingbi Zhang (Environmental Science and Pollution Research, 2018)

Cortical thickness reductions associate with abnormal resting-state functional connectivity in non-neuropsychiatric systemic lupus erythematosus - Chen Niu; Xiangliang Tan; Xiaojin Liu; Kai Han; Meiqi Niu; Jun Xu; Ling Zhao; Yuankui Wu; Feng Deng; Qin Huang; Xiaoyan Wu; Huiyuan Huang; et al. (Brain Imaging and Behavior, 2018)

Induction of human umbilical cord mesenchymal stem cells into tissue-forming cells in a murine model: implications for pelvic floor reconstruction - Jing Ding; Qin Han; Mou Deng; Xiao-chen Song; Chun Chen; Fang-fang Ai; Lan Zhu; Robert Chun-hua Zhao (Cell and Tissue Research, 2018)

Higher precipitation strengthens the microbial interactions in semi‐arid grassland soils - Shang Wang; Xiaobo Wang; Xingguo Han; Ye Deng (Global Ecology and Biogeography, 2018)
Aim Growing attention has been focused on the changes in the structure and diversity of microbial communities under altered precipitation pattern, but little is known about how this factor impacts microbial interactions. Our aim was to elucidate the variations of microbial interactions in semi‐arid grassland soils and determine the key factor in regulating microbial assemblies in water‐limited areas. Location A c . 3,700 km transect across three habitats (desert, desert grassland and typical grassland) in Northern China. Time period July and August 2012. Major taxa studied Total bacteria and archaea. Method The random matrix theory (RMT)‐based network inference approach was used to construct species interaction networks. The relationships between microbial network topology and environmental variables were examined by Mantel and partial Mantel tests. Results At the regional scale (across habitats), mean annual precipitation was the most important factor constraining the network structure, whereas at the local scale (within a habitat), soil conditions and plant parameters became more important, but their relative effects differed among habitats. In particular, no correlation was detected between the desert network and any environmental factors. The number of central species increased substantially in desert grassland and typical grassland networks in comparison to those in the desert network. Inter‐ and intra‐module connections, particularly negative connections, also increased in the two grassland habitats. Main conclusions Microbial networks become more complex as precipitation increases. A simple network structure (no connectors between modules, more sparsely distributed species and lower competitive links) and less association with environmental factors in the desert network indicate that microbial communities in extremely dry ecosystems are unstable and vulnerable; that is, future climate change will greatly influence microbial interactions in these extremely dry areas. Overall, our findings provide new insight into the way in which microbes respond to changing precipitation patterns by regulating their interactions in water‐limited ecosystems.

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

Cubic membrane formation supports cell survival of amoeba Chaos under starvation-induced stress - Ketpin Chong; Zakaria A. Almsherqi; Han-Ming Shen; Yuru Deng (Protoplasma, 2018)

Will elevated atmospheric CO2 boost the growth of an invasive submerged macrophyte Cabomba caroliniana under the interference of phytoplankton? - Xin Liu; Yanqing Han; Jinge Zhu; Jiancai Deng; Weiping Hu; Thomaz Edson Veloso da Silva (Environmental Science and Pollution Research, 2018)

Gene mutations and clinical phenotypes in 15 Chinese children with cryopyrin-associated periodic syndrome (CAPS) - Caifeng Li; Xiaohua Tan; Junmei Zhang; Shipeng Li; Wenxiu Mo; Tongxin Han; Weiying Kuang; Yifang Zhou; Jianghong Deng (Science China Life Sciences, 2017)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

Identification of a novel reassortant A (H9N6) virus in live poultry markets in Poyang Lake region, China - Heng Zhang; Mingbin Liu; Xiaoxu Zeng; Xiang Zhao; Zhiqiang Deng; Lei Yang; Wenbing Chen; Zi Li; Ming Jiao; Wen Xia; Bin Han; Haiying Chen; et al. (Archives of Virology, 2017)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Comparative study of the leaf transcriptomes and ionoms of Juglans regia and its wild relative species Juglans cathayensis - Zhongcheng Zhou; Muxian Han; Mei Hou; Xiaojing Deng; Rui Tian; Shuifa Min; Jinbo Zhang (Acta Physiologiae Plantarum, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

Gene mutations and clinical phenotypes in Chinese children with Blau syndrome - Caifeng Li; Junmei Zhang; Shipeng Li; Tongxin Han; Weiying Kuang; Yifang Zhou; Jianghong Deng; Xiaohua Tan (Science China Life Sciences, 2017)

Response of microbial diversity to C:N:P stoichiometry in fine root and microbial biomass following afforestation - Chengjie Ren; Ji Chen; Jian Deng; Fazhu Zhao; Xinhui Han; Gaihe Yang; Xiaogang Tong; Yongzhong Feng; Shelby Shelton; Guangxin Ren (Biology and Fertility of Soils, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

Erratum to: Newmark displacement model for landslides induced by the 2013 Ms 7.0 Lushan earthquake, China - Renmao Yuan; Qinghai Deng; Dickson Cunningham; Zhujun Han; Dongli Zhang; Bingliang Zhang (Frontiers of Earth Science, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

An Investigation of the Innate Immune Response in Bovine Mammary Epithelial Cells Challenged by Prototheca zopfii - Zhaoju Deng; Muhammad Shahid; Limei Zhang; Jian Gao; Xiaolong Gu; Shiyao Zhang; Jiaqi Zou; Séamus Fanning; Bo Han (Mycopathologia, 2016)

Newmark displacement model for landslides induced by the 2013 Ms 7.0 Lushan earthquake, China - Renmao Yuan; Qinghai Deng; Dickson Cunningham; Zhujun Han; Dongli Zhang; Bingliang Zhang (Frontiers of Earth Science, 2016)

Genome-wide association study for kernel weight-related traits using SNPs in a Chinese winter wheat population - Guangfeng Chen; Han Zhang; Zhiying Deng; Rugang Wu; Dongmei Li; Mingyou Wang; Jichun Tian (Euphytica, 2016)

Identification of a Novel Mutation in the Titin Gene in a Chinese Family with Limb-Girdle Muscular Dystrophy 2J - Wen Zheng; Han Chen; Xiong Deng; Lamei Yuan; Yan Yang; Zhi Song; Zhijian Yang; Yuan Wu; Hao Deng (Molecular Neurobiology, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Exogenous Abscisic Acid Alleviates Cadmium Toxicity by Restricting Cd2+ Influx in Populus euphratica Cells - Yansha Han; Shaojie Wang; Nan Zhao; Shurong Deng; Chenjing Zhao; Nianfei Li; Jian Sun; Rui Zhao; Huilan Yi; Xin Shen; Shaoliang Chen (Journal of Plant Growth Regulation, 2016)

Endoglucanase enzymatic modification of kraft pulp during recycling - Tao Deng; Liuliu Lu; Shipeng Gao; Ying Lin; Shuangyan Han (Biotechnology Letters, 2016)

Characterization and utilization of microsatellites in the Coffea canephora genome to assess genetic association between wild species in Kenya and cultivated coffee - Collins Ogutu; Ting Fang; Lin Yan; Lu Wang; Lifang Huang; Xiaoyang Wang; Baiquan Ma; Xianbao Deng; Albert Owiti; Aggrey Nyende; Yuepeng Han (Tree Genetics & Genomes, 2016)

Degrading river network due to urbanization in Yangtze River Delta - Longfei Han; Youpeng Xu; Chaogui Lei; Liu Yang; Xiaojun Deng; Chunsheng Hu; Guanglai Xu (Journal of Geographical Sciences, 2016)

Characterization of Prototheca zopfii Genotypes Isolated from Cases of Bovine Mastitis and Cow Barns in China - Muhammad Shahid; Tariq Ali; Limei Zhang; Rongguang Hou; Shiyao Zhang; Laidi Ding; Dandan Han; Zhaoju Deng; Abdur Rahman; Bo Han (Mycopathologia, 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Klf10 regulates odontoblast differentiation and mineralization via promoting expression of dentin matrix protein 1 and dentin sialophosphoprotein genes - Zhuo Chen; Wentong Li; Han Wang; Chunyan Wan; Daoshu Luo; Shuli Deng; Hui Chen; Shuo Chen (Cell and Tissue Research, 2016)

The diapycnal mixing in the upper Pacific estimated from GTSPP observations - Zeng’an Deng; Guanghao Wei; Ting Yu; Hongyu Wei; Linchong Kang; Luyao Han (Acta Oceanologica Sinica, 2016)

Changing structure of precipitation evolution during 1957–2013 in Yangtze River Delta, China - Longfei Han; Youpeng Xu; Liu Yang; Xiaojun Deng (Stochastic Environmental Research and Risk Assessment, 2015)

Response difference of transgenic and conventional rice (Oryza sativa) to nanoparticles (γFe2O3) - Xin Gui; Yingqing Deng; Yukui Rui; Binbin Gao; Wenhe Luo; Shili Chen; Le Van Nhan; Xuguang Li; Shutong Liu; Yaning Han; Liming Liu; Baoshan Xing (Environmental Science and Pollution Research, 2015)

Changing properties of precipitation extremes in the urban areas, Yangtze River Delta, China, during 1957–2013 - Longfei Han; Youpeng Xu; Guangbo Pan; Xiaojun Deng; Chunsheng Hu; Hongliang Xu; Hongyi Shi (Natural Hazards, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Delivery of agricultural drought information via web services - Chunming Peng; Meixia Deng; Liping Di; Weiguo Han (Earth Science Informatics, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Research on self-purification capacity of Lake Taihu - Tao Han; Hongju Zhang; Weiping Hu; Jiancai Deng; Qinqin Li; Guie Zhu (Environmental Science and Pollution Research, 2015)

Spike-frequency adaptation of a two-compartment neuron modulated by extracellular electric fields - Guosheng Yi; Jiang Wang; Kai-Ming Tsang; Xile Wei; Bin Deng; Chunxiao Han (Biological Cybernetics, 2015)

Endothelial cells-targeted soluble human Delta-like 4 suppresses both physiological and pathological ocular angiogenesis - XianChun Yan; ZiYan Yang; Yan Chen; Na Li; Li Wang; GuoRui Dou; Yuan Liu; JuanLi Duan; Lei Feng; SanMing Deng; Hua Han; Ping Zhang (Science China Life Sciences, 2015)

Glycogen synthase kinase 3β inhibition promotes human iTreg differentiation and suppressive function - Yongxiang Xia; Han Zhuo; Yunjie Lu; Lei Deng; Runqiu Jiang; Long Zhang; Qin Zhu; Liyong Pu; Xuehao Wang; Ling Lu (Immunologic Research, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Grading of Peripheral Cytopenias Caused by Nonalcoholic Cirrhotic Portal Hypertension and Its Clinical Significance - Yunfu Lv; Xiaoyu Han; Xiaoguang Gong; Qingyong Ma; Shunwu Chang; Hongfei Wu; Yejuan Li; Jie Deng (Cell Biochemistry and Biophysics, 2015)

Two Novel Exopolysaccharides from Bacillus amyloliquefaciens C-1: Antioxidation and Effect on Oxidative Stress - Haixia Yang; Jianjun Deng; Yue Yuan; Daidi Fan; Yan Zhang; Ruijuan Zhang; Bei Han (Current Microbiology, 2015)

Aberrant elastin remodeling in the lungs of O2-exposed newborn mice; primarily results from perturbed interaction between integrins and elastin - Wenli Han; Chunbao Guo; Qiutong Liu; Benli Yu; Zhaoyun Liu; Junqing Yang; Chun Deng (Cell and Tissue Research, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

HCN Channels Modulate the Activity of the Subthalamic Nucleus In Vivo - Wen-shuai Deng; Yun-Xia Jiang; Xiao-Hua Han; Yan Xue; Hua Wang; Peng Sun; Lei Chen (Journal of Molecular Neuroscience, 2015)

Combined impacts of antecedent earthquakes and droughts on disastrous debris flows - Ning-sheng Chen; Yang Lu; Hai-bo Zhou; Ming-feng Deng; Da-wei Han (Journal of Mountain Science, 2014)

The effect of temperature on the extrinsic incubation period and infection rate of dengue virus serotype 2 infection in Aedes albopictus - Fang-Zhen Xiao; Yi Zhang; Yan-Qin Deng; Si He; Han-Guo Xie; Xiao-Nong Zhou; Yan-Sheng Yan (Archives of Virology, 2014)

A Genome Scan for Quantitative Trait Loci Associated with Vibrio anguillarum Infection Resistance in Japanese Flounder (Paralichthys olivaceus) by Bulked Segregant Analysis - Lei Wang; Caixia Fan; Yang Liu; Yingping Zhang; Shoutang Liu; Deqiang Sun; Han Deng; Ying Xu; Yongsheng Tian; Xiaolin Liao; Mingshu Xie; Wenlong Li; et al. (Marine Biotechnology, 2014)

The evolution analysis of flood and drought in Huai River Basin of China based on monthly precipitation characteristics - Deng-Hua Yan; Dong-Mei Han; Gang Wang; Yong Yuan; Yong Hu; Hong-yang Fang (Natural Hazards, 2014)

Analysis of Cytosolic pH Changes in Thymocytes During Early Apoptosis with Improved Three-Channel Real-Time Fluorescence Imaging - Zhang Shu; Liu Xiaochen; Deng Chuyun; Han Man; Pan Juhua; Liao Xinghua; Qi Xin; Duan Shaojin; Ma Wanyun (Journal of Fluorescence, 2014)

Exploring how extracellular electric field modulates neuron activity through dynamical analysis of a two-compartment neuron model - Guo-Sheng Yi; Jiang Wang; Xi-Le Wei; Kai-Ming Tsang; Wai-Lok Chan; Bin Deng; Chun-Xiao Han (Journal of Computational Neuroscience, 2014)

An ephaptic transmission model of CA3 pyramidal cells: an investigation into electric field effects - Xile Wei; Yinhong Chen; Meili Lu; Bin Deng; Haitao Yu; Jiang Wang; Yanqiu Che; Chunxiao Han (Cognitive Neurodynamics, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

The domestication and dispersal of the cultivated ramie (Boehmeria nivea (L.) Gaud. in Freyc.) determined by nuclear SSR marker analysis - Liang Liao; Tongjian Li; Jin Zhang; Lingling Xu; Huisheng Deng; Xingjie Han (Genetic Resources and Crop Evolution, 2014)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)

New discovery of seafloor hydrothermal activity on the Indian Ocean Carlsberg Ridge and Southern North Atlantic Ridge—progress during the 26th Chinese COMRA cruise - Chunhui Tao; Guanghai Wu; Xianming Deng; Zhongyan Qiu; Chenhua Han; Yanmei Long (Acta Oceanologica Sinica, 2013)

SRPK1 contributes to malignancy of hepatocellular carcinoma through a possible mechanism involving PI3K/Akt - Bo Zhou; Yandong Li; Qing Deng; Haixiao Wang; Yuping Wang; Bing Cai; Ze-Guang Han (Molecular and Cellular Biochemistry, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Reticulate evolution in Ranunculus cantonensis polyploid complex and its allied species - Lingling Xu; Tongjian Li; Liang Liao; Huisheng Deng; Xingjie Han (Plant Systematics and Evolution, 2013)

Multi-scale order recurrence quantification analysis of EEG signals evoked by manual acupuncture in healthy subjects - Guosheng Yi; Jiang Wang; Hongrui Bian; Chunxiao Han; Bin Deng; Xile Wei; Huiyan Li (Cognitive Neurodynamics, 2013)

Overexpression of a poplar two-pore K+ channel enhances salinity tolerance in tobacco cells - Feifei Wang; Shurong Deng; Mingquan Ding; Jian Sun; Meijuan Wang; Huipeng Zhu; Yansha Han; Zedan Shen; Xiaoshu Jing; Fan Zhang; Yue Hu; Xin Shen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Functionalized single-walled carbon nanotubes cause reversible acute lung injury and induce fibrosis in mice - Yanli Zhang; Jiejie Deng; Yanxu Zhang; Feng Guo; Chenggang Li; Zhen Zou; Wen Xi; Jun Tang; Yang Sun; Peng Yang; Zongsheng Han; Dangsheng Li; et al. (Journal of Molecular Medicine, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Annual emissions of nitrous oxide and nitric oxide from rice-wheat rotation and vegetable fields: a case study in the Tai-Lake region, China - Jia Deng; Zaixing Zhou; Xunhua Zheng; Chunyan Liu; Zhisheng Yao; Baohua Xie; Feng Cui; Shenghui Han; Jianguo Zhu (Plant and Soil, 2012)

Long-term exposure to imatinib reduced cancer stem cell ability through induction of cell differentiation via activation of MAPK signaling in glioblastoma cells - Yucui Dong; Qinglian Han; Yan Zou; Zhenling Deng; Xinliang Lu; Xiaohua Wang; Weihua Zhang; Hua Jin; Jun Su; Tao Jiang; Huan Ren (Molecular and Cellular Biochemistry, 2012)

Identification of Cytotoxicity Intermediate Products and Degradation Pathways for Microcystins Using Low-Frequency Ultrasonic Irradiation - Jun Shi; Xu Han; Zhiliang Zhu; Huiping Deng (Water, Air, & Soil Pollution, 2012)

Summer surface layer thermal response to surface gravity waves in the Yellow Sea - Xuefeng Zhang; Guijun Han; Dongxiao Wang; Zengan Deng; Wei Li (Ocean Dynamics, 2012)

Bivariate genome-wide association study suggests that the DARC gene influences lean body mass and age at menarche - Rong Hai; Lei Zhang; YuFang Pei; LanJuan Zhao; Shu Ran; YingYing Han; XueZhen Zhu; Hui Shen; Qing Tian; HongWen Deng (Science China Life Sciences, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)

Starvation reduces the heat shock protein responses in white sturgeon larvae - Dong Han; Susie S. Y. Huang; Wei-Fang Wang; Dong-Fang Deng; Silas S. O. Hung (Environmental Biology of Fishes, 2012)

The Reanalysis of Currents and Throughflow Volume Transport in the Taiwan Strait - Ting Yu; Zengan Deng; Guijun Han; Xinrong Wu; Hongli Fu; Kejian Wu (Marine Geodesy, 2012)

Molecular characterization of LMW glutenin genes from Taeniatherum Nevski - Chang Han; Ze-Hong Yan; Shou-Fen Dai; Deng-Cai Liu; Yu-Ming Wei; You-Liang Zheng; Xiu-Jin Lan; Yuan-Ying Peng (Genetic Resources and Crop Evolution, 2011)

Medical history and the risk of biliary tract cancers in Shanghai, China: implications for a role of inflammation - Gabriella Andreotti; Enju Liu; Yu-Tang Gao; Mahboobeh Safaeian; Asif Rashid; Ming-Chang Shen; Bin-Shen Wang; Jie Deng; Tian-Quian Han; Bai-He Zhang; Ann W. Hsing (Cancer Causes & Control, 2011)

Evaluation on the two filling functions for the recovery of forest information in mountainous shadows on Landsat ETM + Image - Amir reza Shahtahmassebi; Ke Wang; Zhangquan Shen; Jinsong Deng; Wenjuan Zhu; Ning Han; Fengfang Lin; Nathan Moore (Journal of Mountain Science, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Efficient Intracellular Gene Delivery Using the Formulation Composed of Poly (L-glutamic Acid) Grafted Polyethylenimine and Histone - Jingjing Deng; Yuting Wen; Cuifeng Wang; Shirong Pan; Huaiyu Gu; Xin Zeng; Lina Han; Yuefang Zhao; Min Feng; Chuanbin Wu (Pharmaceutical Research, 2011)

Triggering of death receptor apoptotic signaling by human papillomavirus 16 E2 protein in cervical cancer cell lines is mediated by interaction with c-FLIP - Wei Wang; Yong Fang; Ni Sima; Yan Li; Wei Li; Li Li; Linfei Han; Shujie Liao; Zhiqiang Han; Qinglei Gao; Kezhen Li; Dongrui Deng; et al. (Apoptosis, 2011)

Several Important Issues in Salinity Quality Control of Argo Float - Ting Yu; Guijun Han; Changlong Guan; Zengan Deng (Marine Geodesy, 2010)

A genome-wide association analysis implicates SOX6 as a candidate gene for wrist bone mass - LiJun Tan; Rong Liu; ShuFeng Lei; Rong Pan; TieLin Yang; Han Yan; YuFang Pei; Fang Yang; Feng Zhang; Feng Pan; YinPin Zhang; HongGang Hu; et al. (Science China Life Sciences, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Analysis of Olfactory Ensheathing Glia Transplantation-Induced Repair of Spinal Cord Injury by Electrophysiological, Behavioral, and Histochemical Methods in Rats - Kai-Jun Liu; Jin Xu; Chang-Yu Yang; Han-Bo Chen; Xiang-Sheng Liu; Yong-Deng Li; Zhan-Fei Li (Journal of Molecular Neuroscience, 2010)

Overexpressing cellular repressor of E1A-stimulated genes protects mesenchymal stem cells against hypoxia- and serum deprivation-induced apoptosis by activation of PI3K/Akt - Jie Deng; Yaling Han; Chenhui Yan; XIaoxiang Tian; Jie Tao; Jian Kang; Shaohua Li (Apoptosis, 2010)

Structural and expressional analysis of the B-hordein genes in Tibetan hull-less barley - Zhaoxue Han; Fang Wu; Guangbing Deng; Gang Qian; Maoqun Yu; Yulin Jia (Genetica, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Ivermectin inhibits LPS-induced production of inflammatory cytokines and improves LPS-induced survival in mice - X. Zhang; Y. Song; X. Ci; N. An; Y. Ju; H. Li; X. Wang; C. Han; J. Cui; X. Deng (Inflammation Research, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Mesozoic paleogeography and tectonic evolution of South China Sea and adjacent areas in the context of Tethyan and Paleo‐Pacific interconnections - Di Zhou; Zhen Sun; Han‐zong Chen; He‐hua Xu; Wan‐yin Wang; Xiong Pang; Dong‐sheng Cai; Deng‐ke Hu (Island Arc, 2008)
During the Mesozoic era, the South China Sea and its environs were located at the south‐eastern margin of the Eurasian continent. There has been hot debate on the influences of Tethyan and Paleo‐Pacific tectonics to the Mesozoic evolution of the area. This paper compiles lithofacies maps of six time slices and discusses the paleogeographic and tectonic evolution of the area based on this compilation and other data on structural deformation and magmatism. In the Early Triassic, the Paleotethys Ocean extended eastward to the study area through the Song Da passage. Then a significant east–west differential evolution began. In the Late Triassic, the western area uplifted as a result of the collision between the Indosinian and South China blocks during the Indosinian orogeny, and the Song Da passage has closed since then. Meanwhile, a transgression of Paleo‐Pacific waters occurred in the eastern and south‐eastern portions of the area, forming the ‘East Guangdong–North‐west Borneo Sea’. In the Early Jurassic, seawater transgression was even more pronounced, resulting into the connection of this sea with the Mesotethys Ocean to the west. Large quantities of Tethyan water carrying Tethyan organisms entered the area. In the Middle Jurassic, a short‐lived transgression occurred in the eastern Mesotethys and resulted in the formation of the ‘Yunnan–Burma Sea’. The Late Jurassic to Early Cretaceous was the climax of the subduction of both the Mesotethys and Paleo‐Pacific towards the Eurasian continent. This led to the formation of the great ‘Circum South‐east Asia Subduction–Accretion Zone’ in the Middle or Late Cretaceous. This paper also presents various lines of evidence for a newly recognized segment of this Mesozoic subduction–accretion zone buried under Cenozoic sediments in the north‐eastern South China Sea.

No changes in densities of cannabinoid receptors in the superior temporal gyrus in schizophrenia - Chao Deng; Mei Han; Xu-Feng Huang (Neuroscience Bulletin, 2007)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

A Pilot Study of Transcription Unit Analysis in Rice Using Oligonucleotide Tiling-path Microarray - Viktor Stolc; Lei Li; Xiangfeng Wang; Xueyong Li; Ning Su; Waraporn Tongprasit; Bin Han; Yongbiao Xue; Jiayang Li; Michael Snyder; Mark Gerstein; Jun Wang; et al. (Plant Molecular Biology, 2005)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)

Production of transgenic creeping bentgrass Agrostis stolonifera var. palustris plants by Agrobacterium tumefaciens-mediated transformation using hygromycin selection - Ning Han; Dong Chen; Hong-Wu Bian; Min-Juan Deng; Mu-Yuan Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

3,4,5,6-Tetrahydroxyxanthone prevents vascular endothelial cell apoptosis induced by high glucose - Zhong Dai; Duan-Fang Liao; De-Jian Jiang; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide - Zhi-Hong Zhou; Jun Peng; Feng Ye; Nian-Sheng Li; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Erratum: Involvement of capsaicin-sensitive sensory nerves in early and delayed cardioprotection induced by a brief ischaemia of the small intestine - Yuan-Jian Li; Zi-Lue Tang; Wen Dai; Han-Wu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)